Large-scale laboratory study on geosynthetic interlayers to improve performance of asphalt overlays on jointed concrete pavements - Mozaher Ul Kabir; Jie Han; Md.Wasif Zaman; Robert L. Parsons; Sarper Demirdogen (Transportation Geotechnics, 2026)

A pilot autism case-control study of pesticides and plasticizers in shed baby teeth - Lynne P. Heilbrun; Inkyu Han; Anabel Rodriguez; L. Aubree Shay; David Gimeno Ruiz de Porras (Neurotoxicology and Teratology, 2026)

Linking ambient fire emissions to respiratory effects using gelatin filter sampling - Olivia C.G. Lampe; Tate J. Matthews; Akshat Verma; Bowie P. Lam; Eva C.M. Vitucci; Carolyn L. Cannon; Arum Han; Shankararaman Chellam; Natalie M. Johnson (Journal of Hazardous Materials, 2026)

Present-Day Sea Level Variations in Coastal Areas from Daily to Multidecadal Time Scales: Observations and Causes - A. Cazenave; R. Almar; P. Almeida; N. K. Ayoub; J. H. Bettencourt; F. Birol; W. Han; M. Herrmann; S. Jevrejeva; L. Leclercq; F. Niño; J. Oelsmann; et al. (Surveys in Geophysics, 2026)

Retraction notice to “Exposure to ambient fine particles and neuropsychiatric symptoms in cognitive disorder: A repeated measure analysis from the CREDOS (Clinical Research Center for Dementia of South Korea) study” [Sci. Total Environ. 668 (2019) 411–418] - Hyewon Lee; Jae Myeong Kang; Woojae Myung; Junbae Choi; Chunsoo Lee; Duk L. Na; Seong Yoon Kim; Jae-Hong Lee; Seol-Heui Han; Seong Hye Choi; Sang Yun Kim; Seong-Jin Cho; et al. (Science of The Total Environment, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Eight recommendations to enhance biodiversity outcomes of nature-based solutions at multiple scales - Charles B. van Rees; Collin VanBuren; Lori A. Han; Andrew Altieri; Matt Bilskie; James E. Byers; Jon Calabria; Matthew L. Chambers; Daniel J. Coleman; Katie Foster; Aliza Leit; Alec Nelson; et al. (Journal of Environmental Management, 2026)

Calving Mechanisms of Lake-Terminating Glaciers in the Southeastern Tibetan Plateau - Menger Peng; Wenfeng Chen; Wei Yang; Jonathan L. Carrivick; Yushan Zhou; Xiaoran Han; Guoqing Zhang (Journal of Earth Science, 2026)

Combined effects of potassium phosphate catalysts and alcohol cosolvent on biocrude production from hydrothermal liquefaction of microalgae - Joon-Kyo Kim; Hana Chrenka; André L. Boehman; Taehoon Han (Algal Research, 2026)

Behavioural thermoregulation segregates sick and healthy fish to enable selective treatment - Massiel F. Copara Chino; Jayoon Lee; Yujin Han; Julia G. Neyedly; Matthew L. Michnik; Patrick Whittaker; Kathryn Smith; Keith B. Tierney; Yamila Carpio; Mario P. Estrada; Mark D. Fast; Brian Dixon; et al. (Aquaculture, 2026)

Seasonality and aerosol microenvironment-associated processing of organic aerosol in a humid inland city - Hyo-Won Lee; Ji-Won Jeon; Young-Ji Han; Seung-Ha Lee; Hyun-Gu Jung; Seung-Hwan Cha; Ha-Yoon Jeong; Jung-Min Park; Jefferey L. Collett Jr. (Journal of Hazardous Materials, 2026)

Eelgrass (Zostera marina) can tolerate salinity fluctuations - Katrin Rehlmeyer; Dindi Hiddink Verberne; Ellis J. Weinberg; Wilhelmina F. van Dorp; Maite L. Vogel; Oscar Franken; Hans van Veen; Han Olff; Tjisse van der Heide; Laura L. Govers (Journal of Experimental Marine Biology and Ecology, 2026)

Synergistic and antagonistic interaction effects during the co-gasification of polyethylene and polystyrene in supercritical water - Hengda Han; Saumitra Saxena; Ribhu Gautam; Mengyan Wang; Fabiyan Angikath; Frederick L. Dryer; Bassam Dally (Fuel, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Average trace element composition of the upper continental crust derived from an integrated study of sedimentary and igneous rocks - Kang Chen; Pengyuan Han; Roberta L. Rudnick; Jingliang Guo; Zhaochu Hu (Geochimica et Cosmochimica Acta, 2026)

Average major element composition of the upper continental crust derived from an integrated study of sedimentary and igneous rocks - Peng-Yuan Han; Kang Chen; Roberta L. Rudnick; Zhao-Chu Hu (Geochimica et Cosmochimica Acta, 2026)

Divergent edaphic filters drive ecosystem-specific microbiome assembly and metabolic strategies in Northern China's transitional zone - Zhaojuan Zhang; Songning Guo; Xin Li; Zifei Wang; Xiao Han; Jiaxin Li; Zhuang Li; Jing Zhao; Steven L. Stephenson; V.I. Gmoshinskiy; A.V. Kurakov; Yu Li; et al. (Environmental Research, 2026)

Early development of stem units and the modular organization of the branch in Norway spruce - Carol L. Wenzel; Anson Mo; Bonita Chan; Anny Xia; Chantelle Westgate; Rebecca Saunders; Han Han Ly; David M. Holloway (Trees, 2026)

Quantification and visualization of 3D facial aging in individuals of European ancestry - Yi Fan; Harold Matthews; Chenda Meng; Nina Claessens; Seth M. Weinberg; Mary L. Marazita; Susan Walsh; Mark D. Shriver; Anthony Penington; Marie A. Cornelis; Paolo M. Cattaneo; Tianmin Xu; et al. (GeroScience, 2026)
Facial features undergo continuous transformations across the lifespan. This study quantified and visualized the effects of aging on facial morphology in individuals of European ancestry. Three-dimensional facial photographs of 4,038 individuals (1,455 males and 2,583 females), aged 5 to 85 years and of European descent, were analyzed. Morphological changes in the face were modeled using kernel linear regression, with a focus on age-related changes. Age- and sex-specific expected facial shapes were generated for individuals aged 10 to 60 years in 5-year intervals. Changes in the face were analyzed in the sagittal, vertical, and horizontal directions, with linear distances and angular variations in the upper, middle, and lower regions of the face evaluated. Our results show that facial shape changes decelerate progressively after the age of 25 for both males and females. Facial aging is characterized by the loss of fullness in the forehead, sunken temples, formation of eye bags, deepening nasolabial folds, cheek hollowness and thinning, lengthening, and retrusion of the lips. Notable changes begin in the 30s, with the most pronounced alterations occurring in the 40s and 50s, intensifying in the 50s and 60s. Although the overall aging trajectory is similar in males and females, the magnitude and rate of change demonstrate sexual dimorphism. This study provides comprehensive insights into age-related facial morphological changes in healthy individuals of European ancestry using 3D photogrammetric analysis. These findings have important implications for clinical disciplines such as dentistry, plastic and maxillofacial surgery, and forensic medicine.

A critical review of potential modifiers of air pollutant associations with dementia and related outcomes - JeongWon Han; Yina Li; Sangji Lee; Katie M. Lynch; Erin E. Bennett; Qi Ying; Eun Sug Park; Richard L. Smith; James D. Stewart; Eric A. Whitsel; Melinda C. Power; Xiaohui Xu (NeuroToxicology, 2026)

Geothermal resource identification in Australia using shallow groundwater temperature data - Y. Han; L. T. White; W. G. P. Kumari; T. Murray (Australian Journal of Earth Sciences, 2026)

Comparative neurotoxic effects of PFOA and GenX in hiPSC-derived cortical neurons - Han Zhao; Junkai Xie; Shichen Wu; Xihui Zhao; Serena Yu; Jennifer L. Freeman; Jean-Christophe Rochet; Chongli Yuan (Journal of Hazardous Materials, 2026)

How does the built environment affect obesity? A review from the perspective of urban planning - H. Wu; G. Han; L. Yang; R. Liang (International Journal of Environmental Science and Technology, 2026)

Disentangling the life-history costs of direct male-male competition and sperm production - Fatema Akhter; Megan L. Head; Michael D. Jennions; Meng-Han Joseph Chung (Evolutionary Ecology, 2026)
To achieve reproductive success, males typically invest more than their rivals to win fights and secure mating opportunities. Male-male competition can then continue after copulation as sperm competition if females mate multiply. While male reproduction often comes at the expense of other fitness-related traits (e.g., growth, immunity), the relative costs of different components of male reproduction (e.g., fighting rivals or sperm production) are unclear. Addressing this oversight is challenging due to the inherent correlation between different reproductive activities: a male must fight and mate successfully before investing in sperm competition. Here, we conducted an experiment in Gambusia holbrooki to estimate the life-history costs of different components of reproduction. To quantify the cost of male-male fighting, we compared life-history traits of males in the presence and absence of rivals. To quantify the cost of sperm investment, we compared life-history traits in males that either could or could not release sperm (following ablation surgery) when in the presence of rivals. Males that fought with rivals for eight weeks did not show reduced growth, immune response, sperm count or sperm velocity than males that had not fought rivals. Interestingly, males that fought rivals spent significantly less time following females but still made the same number of mating attempts, suggesting increased mating efficiency. Conversely, males that repeatedly ejaculated over eight weeks produced significantly fewer sperm than those that could not ejaculate because of ablation of the tip of their gonopodium. Greater past sperm investment due to the inability to ejaculate increased the time spent following females, but did not affect the number of mating attempts. Our findings show that sperm investment in the presence of rivals reduces a male’s future ability to produce sperm, whereas no life-history costs of physical fighting were detected.

Analysis of Helium Monte Carlo Data for the ISS-CREAM Instrument - A. Bagga; S. Aggarwal; Y. Amare; D. Angelaszek; D.P. Bowman; Y.C. Chen; G.H. Choi; M. Copley; L. Derome; Z.M. Dorris; L. Eraud; J.H. Han; et al. (Advances in Space Research, 2026)

Microbial Responses to Warming Reduce Deep Blue Carbon Storage - Leilei Xiao; Jian Liu; Genevieve L. Noyce; Jaehyun Lee; Carlos M. Duarte; Meng Zhou; Min Luo; Ruifeng Sun; Run Dang; Lifeng Zhou; Lirong Zhang; Chuancheng Fu; et al. (Global Change Biology, 2026)
Coastal wetlands are critical blue carbon reservoirs, yet the depth‐resolved impacts of warming on belowground carbon dynamics remain poorly understood. Over the course of an 8‐year in situ experiment, we investigated plant‐derived carbon inputs, soil carbon losses via respiration, and microbially mediated carbon fixation across a 60 cm soil profile under a projected 2°C atmospheric warming scenario. Plant carbon fixation (above‐ and belowground net primary productivity) and soil respiration exhibited synchronized responses to warming, with an initial increase, followed by a decline in the mid‐term, and no significant response in the later stages. Soil and microbial respiration stabilized after prolonged exposure to elevated temperatures, as these processes were constrained by substrate availability. In contrast, phospholipid fatty acid profiling, amino sugar biomarkers, and metagenome‐assembled genomes consistently indicated a greater than one‐third reduction in microbial carbon fixation within subsoils (40–60 cm). Our fully factorial, depth‐stratified warming design reveals the particular vulnerability of deep soil microbial carbon retention to long‐term climate warming, independent of shifts in plant input or respiratory carbon loss. This work highlights underappreciated pathways influencing soil blue carbon dynamics in a changing world.

Litter cellulose modulates dissolved organic carbon to drive co-denitrification contribution and nitrous oxide emissions in tea plantation soils - Zhe Xu; Ziheng Zou; Emily Cooledge; Sujin Feng; Pinshang Xu; Jinbo Zhang; Yubing Dong; Jinyang Wang; Shuwei Liu; Zhaoqiang Han; Christoph Müller; Davey L. Jones; et al. (Journal of Environmental Management, 2026)

Comparisons of industrial emission signatures recorded by spheroidal carbonaceous particles and fossil fuel soot from maar lake sediments in Northeastern and Southeastern China - Huijia Zhang; Yongming Han; Yalan Tang; Ulrike Dusek; Dewen Lei; Sarah L. Roberts; Neil L. Rose; Dongna Yan (Environmental Research, 2026)

Reconstructing initial VOC concentrations to reveal their role in ozone formation - Se-In Hong; Jeffrey L. Collett; Young-Ji Han (Atmospheric Environment, 2026)

Impacts of climate and land-use change on ecosystem services in the agro-pastoral ecotone of western Liaoning - Y. Li; D. Ye; X. Han; S. Xia; J. Jin; X. Jiang; L. Lv (International Journal of Environmental Science and Technology, 2026)

Peptide-functionalized nanoparticles for brain-targeted therapeutics - Sophia Tang; Emily L. Han; Michael J. Mitchell (Drug Delivery and Translational Research, 2026)
Despite the rapid development of nanoparticle (NP)-based drug delivery systems, intravenous delivery of drugs to the brain remains a major challenge due to various biological barriers. To achieve therapeutic effects, NP-encapsulated drugs must avoid accumulation in off-target organs and selectively deliver to the brain, successfully cross the blood–brain barrier (BBB), and reach the target cells in the brain. Conjugating receptor-specific ligands to the surface of NPs is a promising technique for engineering NPs to overcome these barriers. Specifically, peptides as brain-targeting ligands have been of increasing interest given their ease of synthesis, low cytotoxicity, and strong affinity to target proteins. The success of peptides as targeting ligands is largely due to the diverse strategies of designing and modifying peptides with favorable properties, including membrane permeability and multi-receptor targeting. Here, we review the design and implementation of peptide-functionalized NP systems for neurological disease applications. We also explore advances in rational peptide design strategies for brain targeting, including using generative deep-learning models to computationally design new peptides. Graphical Abstract

Alpha-defensins promote macrophage inflammatory activation via RNF31 signaling - Jungnam Lee; Naweed Mohammad; Seyoung Mun; Kyudong Han; Tammy Flagg-Dowie; Maria Magallon; Mark L. Brantly; Karina A. Serban (Genes & Genomics, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Experimental study on shear bond strength and bearing capacity of lightweight cellular concrete fill around plastic pipes - Yu-qiu Ye; Jie Han; Brad Dolton; Robert L. Parsons (Geotextiles and Geomembranes, 2026)

Functional analysis of wssv025 gene in the pathogenicity of white spot syndrome virus in Penaeus monodon - Shanel G. Manito; Cong-Yan Chen; Brandon Rafael de Jesús Castillo-Corea; Mary Nia M. Santos; Casiano H. Choresca; Fiona L. Pedroso; Christopher Marlowe Caipang; Han-Ching Wang; Fernand F. Fagutao (Fish & Shellfish Immunology, 2026)

Cumulative environmental exposures adversely impact social behaviour and are associated with dysregulation of genes and proteins involved in epigenetic, ribosomal, and immune regulation in male mice - Morgan C. Bucknor; Brooke A. Keating; Velda X. Han; Brian S. Gloss; Pinki Dey; Nader Aryamanesh; Lee L. Marshall; Mark E. Graham; Ruwani Dissanayake; Xianzhong Lau; Shrujna Patel; Stela P. Petkova; et al. (Inflammation Research, 2026)
Objective This study investigated how cumulative environmental exposures influence offspring behaviour and inflammation-related molecular signatures in the brain and peripheral immune system. Methods A novel "triple-hit" mouse model was developed using C57Bl/6JAusB mice (N = 70), combining preconceptual social stress, antenatal high-fat diet, and a postnatal immune challenge (poly(I:C), 10 mg/kg). At 12 weeks, offspring underwent behavioural tests relevant to neurodevelopmental disorders (NDDs), including the Elevated Plus Maze, 3-Chamber Social Preference, Self-Grooming, and Marble Burying. A composite NDD-risk index was calculated. Single-cell RNA sequencing (scRNA-seq) and bulk proteomics were performed on male triple-hit offspring to identify differentially expressed genes and proteins associated with inflammatory pathways. Results Male triple-hit offspring showed elevated NDD-related behavioural risk and social deficits, not observed in females. scRNA-seq revealed altered inflammatory and ribosomal pathways in brain glia and peripheral immune cells. Proteomic analysis showed decreased abundance of proteins involved in inflammation, translation, chromatin remodelling, and synaptic function in both brain and blood. Conclusion Combined environmental stressors may drive male-specific behavioural and inflammatory changes relevant to NDDs. The identification of overlapping inflammatory signatures in brain and peripheral immune cells supports a role for shared immune mechanisms in brain–immune axis dysfunction. However, these pathway-level findings should be interpreted as preliminary hypotheses and warrant independent validation to confirm their mechanistic significance.

Red mud-mediated CO2 capture for enhanced carbon reduction and waste-to-resource: A review - Yanxiu Wang; Anqi Yang; Fan Wang; Dandan Huang; Ling Zhang; Chengwen Wang; Li Wang; Haisheng Han; Wei Sun; John L Zhou (Minerals Engineering, 2026)

PM2.5 exposure risks in urban outdoor jogging: multiple environmental determinants and mitigation strategies - L. Han; Y. J. Qi; L. Luo; W. Ding; K. Li; W. Li; L. Y. Tang (International Journal of Environmental Science and Technology, 2026)

Monitoring, characterization, and mitigation of nitrous oxide emissions from Chinese orchards - Pinshang Xu; Ziheng Zou; Guoliang Zhang; Zhutao Li; Zhaoqiang Han; Davey L. Jones; Jinyang Wang (Agriculture, Ecosystems & Environment, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Comprehensive life cycle carbon emission estimation of coalfield spontaneous combustion using time series thermal infrared remote sensing - Jinchang Deng; Bobo Shi; José L. Torero Cullen; Yong Xue; Liying Han (Journal of Cleaner Production, 2025)

Long-term moderate substitution of organic manure for chemical fertilizers enhances greenhouse vegetable production sustainability - Le Han; Xin Zhang; Caroline L. Peacock; Ji Li; Hefa Yang; Kelin Hu (Journal of Environmental Management, 2025)

Enhancing carbon storage through proactively managing fire-prone coniferous mountain forests - Weichao Guo; Mohammad Safeeq; Guotao Cui; Philip C. Myint; Panmei Jiang; Han Guo; Michael L. Goulden; Kristen D. Emmett; Stephen C. Hart; Roger C. Bales (Ecological Modelling, 2025)

Harnessing dental stem cell-extracellular vesicles for osteogenesis, immunomodulation, angiogenesis, and neurogenesis during bone regeneration - Xi Xiang; Jianwen Li; Danyuan Xie; Keyu Lv; Hanyang Yu; Xinwei Han; Ying Ruan; Tingting Sun; Xuguang Gao; Youguang Lu; Janak L. Pathak; Sujuan Zeng (Chemical Engineering Journal, 2025)

Exopolysaccharides from Rhizobium tropici improve flooding tolerance of Zea mays seedlings: Insights from a controlled pot study - Liang Xiao; Xinyun Xie; Steve L. Larson; John H. Ballard; Qinku Zhang; Jing Nie; Huimin Zhang; Guodong Yuan; Fengxiang X. Han (Plant and Soil, 2025)

Laboratory Evaluation of Field Moisture Capacity of Silty Sands with Varying Fines Content - Md. Wasif Zaman; Jie Han; Mozaher Ul Kabir; Robert L. Parsons (Geotechnical and Geological Engineering, 2025)

Lower Triassic conodont succession and carbon isotope profile from Zaluch, Salt Range, Pakistan - Chen Han; Martyn L. Golding; Laishi Zhao; Shunling Wu; He Zhao; Zhengyi Lyu; Zhong-Qiang Chen; Irfan U. Jan; Abdullah Khan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Towards high-performance buildings for thermal resilience and health - Yalin Lu; Nan Ma; Alpha Yacob Arsano; Nathan Brown; Jihoon Chung; Aysegul Demir Dilsiz; Bing Dong; Ellen Franconi; Xu Han; Zixin Jiang; Nathaniel L Jones; Mili Kyropoulou; et al. (Energy and Buildings, 2025)

Metal-organic frameworks based solid-state electrolytes for high-performance lithium metal batteries - Zhenjie Dai; Yuyu Su; Dan Liu; Qi Han; Tamar L. Greaves; Weiwei Lei; Zongjian Liu; Zhengfei Chen (Chemical Engineering Journal, 2025)

Fetal response to maternal exposures of environmental chemicals: Utility of a four-cell human feto-maternal interface organ-on-chip - Haley L. Moyer; SungJin Kim; Bowie P. Lam; Lauren S. Richardson; Han-Hsuan D. Tsai; Lucie C. Ford; Hsing-Chieh C. Lin; Weihsueh A. Chiu; Ramkumar Menon; Arum Han; Ivan Rusyn (Chemico-Biological Interactions, 2025)

Deep neural networks autonomously learn and utilize critical environmental conditions to capture the impacts of weather on spring wheat performance - Ryan L. Benke; Linqian Han; Kimberly A. Garland-Campbell; Xianran Li (Computers and Electronics in Agriculture, 2025)

Authigenic CaCO3 precipitation contributes to the stabilization of algal-derived organic carbon in karst lake - Yingxun Du; Cheng Zhao; Xuexin Han; Shilin An; Zhendu Mao; Fan Xun; Ding He; Yongdong Zhang; Muhua Feng; Wenlei Luo; Qinglong L. Wu; Peng Xing (Water Research, 2025)

Determination of household wastewater PFAS composition and concentrations via neighborhood sampling - Omobayo A. Salawu; Ziwei Han; Naomi L. Senehi; Shannon L. Roback; Adeyemi S. Adeleye (Journal of Hazardous Materials, 2025)

Quantitative analysis of PM2.5 oxidative potential: Insights into the role of organic compounds and sources - Ji-Hyeon Koo; Sung-Won Park; Hyo-Won Lee; Pyung-Rae Kim; Ji-Won Jeon; Kyung-Hwan Kwak; Seung-Muk Yi; Jeffrey L. Collett; Young-Ji Han (Journal of Hazardous Materials, 2025)

Provenance analysis of late Pleistocene sediment from IODP site U1477 reveals climate and river basin dynamics in the Zambezi river catchment - Youhong Gao; Hucai Zhang; Xiaonan Zhang; Lizeng Duan; Huayong Li; Ian R. Hall; Sidney R. Hemming; Leah J. LeVay; Junsheng Nie; Xibin Han; S. Barker; M.A. Berke; et al. (Gondwana Research, 2025)

Fine root trait dynamics and their relationships with productivity across grasslands under extreme drought - Yuan Shi; Taofeek O. Muraina; Saheed O. Jimoh; Niwu Te; Lin Song; Jiaqi Chen; Hongqiang Wang; Qiang Yu; Xiaoan Zuo; Xingguo Han; Wentao Luo; Scott L. Collins (Oecologia, 2025)

Marine Benthic Community Assembly Is Taxonomically Stochastic but Functionally Deterministic in a Dynamic Coastal Sea - Milenka Sloots; Oscar Franken; Kasper J. Meijer; Tjisse van der Heide; Laura L. Govers; Han Olff (Ecology Letters, 2025)
Understanding the balance between deterministic and stochastic processes in community assembly is crucial for interpreting ecological community dynamics. Moreover, it provides perspective for conservation and management actions, as deterministic processes can be subject to targeted interventions, but stochastic processes are less manageable. Through a spatially explicit macrozoobenthic monitoring campaign consisting of 1323 sampling locations in the Dutch Wadden Sea, we examined the relative importance of deterministic and stochastic processes, including the role of hydrodynamic disturbance gradients. We found species‐based community assembly to be mainly driven by stochastic processes, while trait‐based assembly was more deterministic and environmentally driven. Environmental disturbance levels minimally affected the relative importance of stochastic and deterministic processes. For coastal benthic ecosystems, we therefore recommend management actions to target specific desired functional groups rather than specific changes in community composition.

Reconstructing historical catch trends of threatened sharks and rays based on fisher ecological knowledge - Guido Leurs; Rima W. Jabado; Assana Camará; Lilísio Dos Santos; Diosnes Manuel Nonque; Thije J. Zuidewind; Iça Barry; Pierre Campredon; Benja Blaschke; Karin de Boer; Nadia Hijner; Han Olff; et al. (Conservation Biology, 2025)
Small‐scale fisheries often lack historical shark and ray catch information, hampering their management. We reconstructed historical catch trends and current fishing pressure by combining local ecological knowledge, satellite‐based vessel counts, and a short‐term landing‐site survey. To test the effectiveness of this method, we focused on the Bijagós Archipelago (Guinea‐Bissau, West Africa), where historical fisheries data are lacking. Benthic rays (stingrays [Dasyatidae] and butterfly rays [ Gymnura spp.]), benthopelagic rays (duckbill eagle rays [ Aetomylaeus bovinus ] and cownose rays [ Rhinoptera marginata ]), guitarfish ( Glaucostegus and Rhinobatos spp.), requiem sharks (Carcharhinidae), and hammerhead sharks ( Sphyrna spp.) declined in abundance by 81.5–96.7% (species dependent) from 1960 to 2020. Fishing effort increased annually: fishing trip duration by 42.0% (SE 3.4), numbers of fishing vessels at sea as perceived by fishers by 36.3% (1.0) (1960–2020), and number of vessels by 12.0% (1.1) (2007–2022). We estimated that in 2020, fishing vessels collectively captured 61–264 sharks and 522–2194 rays per day in the archipelago, depending on the proportion of the fishing fleet that was active (i.e., low fleet activity of 18% and high fleet activity of 80%). We advocate for reducing shark and ray catches by regulating fleet size, reinforcing boundaries of protected areas, and collecting fisher‐dependent information on shark and ray landings to safeguard these vulnerable species and coastal livelihoods. We demonstrated the effectiveness of using this 3‐pronged approach to provide baseline data on shark fisheries, a common challenge in areas with small‐scale fisheries and limited research capacity.

P31-21 Detection Methods for Injection-Induced Pseudoallergic Reactions - C. Liu; Y. Yi; C. Li; Y. Zhao; Y. Zhang; J. Han; J. Tian; C. Pan; L. Wang; S. Liu; L. Ma; A. Liang (Toxicology Letters, 2025)

Toward more accurate quantification: A review of global large river basin management policies - Yi-Lin Zhao; Han-Jun Sun; Jie Ding; Zhen Hong; Ji-Wei Pang; Guene L. Razack; Nan-Qi Ren; Shan-Shan Yang (Journal of Environmental Management, 2025)

Seismic observations from injection experiments and a recharge event in a karst aquifer: potential compressed air pocket release - Andrew J. Luhmann; Susan L. Bilek; Matthew D. Covington; Ronni Grapenthin; Han Byul Woo; Jacob Alexander Gochenour; E. Calvin Alexander; Scott C. Alexander; Martin R. Larsen (Hydrogeology Journal, 2025)
After deploying a seismic network above a karst aquifer that feeds Bear Spring in Minnesota, USA, three injection experiments were conducted, which involved pouring ~10,000 L of water just above an overflow spring to induce and characterize ambient seismic noise from subsurface water flow. A rainstorm event followed the second experiment and caused the overflow spring to start flowing with meters of water level rise, increasing the total spring discharge (perennial and overflow emanations) from ~100 to 300 L/s. Water level, electrical conductivity, and temperature data were used to estimate the conduit hydraulic diameter of ~0.06 m from the second injection experiment and ~0.5 m from the recharge event, which suggested both open channel and full pipe conduit flow. The rainstorm led to the largest seismic signals over a 5 s period while water levels rose, producing ground motion up to ~0.5 mm/s, possible oscillatory behavior, and 1–150 J of radiated seismic energy at frequencies of ~30–50 and 70–90 Hz (similar to signal frequencies when the large water slug from the second injection experiment reached a sump or water-filled passage). The seismic sources originated from multiple directions. The calculations suggest these signals came from conduits with air pockets that were compressed from rising water levels and later released via ventilation pathways. Seismic records of this process enable identification of the change in mode of water level propagation and potential delineation of unknown subsurface pathways, facilitating karst aquifer characterization beyond what is possible with traditional monitoring strategies.

Association of urinary phthalate metabolite concentrations with inflammatory biomarker levels among pregnant women - Han Han; Sarah Grill; Xilin Shen; Paige L. Williams; Tamarra James-Todd; Jennifer B. Ford; Kathryn M. Rexrode; Antonia M. Calafat; Jorge E. Chavarro; Russ Hauser; Lidia Mínguez-Alarcón (Environmental Research, 2025)

Quantitative comparison of seasonal and diurnal characteristics for urban heat using meteorological monitoring data - Y. Gao; J. Zhao; L. Han (International Journal of Environmental Science and Technology, 2025)

Deep transfer learning for spatiotemporal mapping of PM2.5 nitrate across China: Addressing small data challenges in environmental machine learning - Xi Zheng; Haiyan Meng; Zixiang Zhao; Xinyi Liu; Li Zhou; Michael L. Grieneisen; Han Zhang; Yu Zhan; Fumo Yang (Journal of Hazardous Materials, 2025)

Correction to: Lifespan effects in male UM‑HET3 mice treated with sodium thiosulfate, 16-hydroxyestradiol, and late‑start canagliflozin - Richard A. Miller; David E. Harrison; Gino A. Cortopassi; Ishmael Dehghan; Elizabeth Fernandez; Michael Garratt; John G. Geisler; Brett C. Ginsburg; Melissa L. Han; Catherine C. Kaczorowski; Navasuja Kumar; Scott F. Leiser; et al. (GeroScience, 2025)

Unexpected Sr enrichment in karst lacustrine sediments associated with warming and rapid socio-economic development - Xiang Gu; Peng Xing; Cheng Zhao; Xiaotong Han; Di Xu; Qinglong L. Wu; Fengchang Wu (Journal of Cleaner Production, 2025)

Properties of inflowing Pacific and Atlantic water govern total and methylated mercury profiles in the Arctic Ocean - Sangwoo Eom; Anne L. Soerensen; Tae Siek Rhee; Jong Kuk Hong; Purena Son; Tae Keun Rho; Seunghee Han (Environmental Pollution, 2025)

Exopolysaccharides from Rhizobium tropici mitigate Al phytotoxicity in Triticum aestivum - Huimin Zhang; Xinyun Xie; Steve L. Larson; John H. Ballard; Kauri A. Runge; Yan Meng; Subrata Chandra Roy; Saiful M. Islam; Fengxiang X. Han (Plant and Soil, 2025)

Synthesis of Population Trends Reveals Seascape‐Wide Reorganisation of Biodiversity From Microalgae to Birds - Anika Happe; Kasper J. Meijer; Jan‐Claas Dajka; Oscar Franken; Holger Haslob; Laura L. Govers; Michael Kleyer; Annebelle C. M. Kok; Lucie Kuczynski; Kertu Lõhmus; Sancia E. T. van der Meij; Han Olff; et al. (Global Change Biology, 2025)
Many monitoring programs aim to understand regional biodiversity patterns in relation to global and regional conservation targets, using either community‐wide biodiversity metrics to describe the community status or trends of pre‐selected “key” species as biodiversity change indicators. However, the former often lacks information on which species are changing, and the latter is heavily skewed towards specific taxa, potentially overlooking changes in other, functionally important taxa. We gathered an extensive set of monitoring data with over 3000 population trends (ranging from 5 to 91 years in duration) for a wide range of taxa across the Wadden Sea. We combined a systematic and quantitative categorization of population trends (weighted vote count) with a meta‐analysis on different taxonomic levels. This allowed the first cross‐taxa synopsis of species declines and increases and determined their directionalities throughout time. Our meta‐analysis showed an overall decrease in population size for fish, zooplankton, and plant species, while birds showed an overall increase. However, these increases mask recent negative trends within specific bird groups since the late 1990s. In contrast, fish populations exhibited declines over the entire monitoring period. Species with declining populations (losers) were phylogenetically related, whereas species with increasing populations (winners) represented various organismal groups. Directionality and onsets of change in population trends were temporally synchronized throughout several groups, such as bivalves, fish, and birds, and may provide warning signals for future local extinctions in these taxa. Our analysis moves beyond typical indicator species by including the entire species inventory of the system. Basal trophic levels of aquatic ecosystems, such as zooplankton and phytoplankton, are often missing from policy assessments but are among the most important organism groups for ecosystem functioning. Here, we show that without additional monitoring effort, a systematic analysis of population trends adds to our understanding of trophic and compositional restructuring of ecosystems.

The Cerebellar Neuropsychiatric Rating Scale in the Spinocerebellar Ataxias - Anna L. Burt; Maureen P. Daly; Janet C. Sherman; Jeremy D. Schmahmann; Susan L. Perlman; Liana S. Rosenthal; Sheng-Han Kuo; Tetsuo Ashizawa; Theresa Zesiewicz; Cameron Dietiker; Puneet Opal; Antoine Duquette; et al. (The Cerebellum, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Prediction of gully erosion susceptibility through the lens of the SHapley Additive exPlanations (SHAP) method using a stacking ensemble model - Jeongho Han; Jorge A. Guzman; Maria L. Chu (Journal of Environmental Management, 2025)

Green manuring combined with optimal water management achieves a triple-win for paddy soil quality, rice productivity, and environmental benefits - Guopeng Zhou; Zhengbo Ma; Shang Han; Danna Chang; Jinxin Sun; Han Liu; Guodong Zhou; Qingxu Ma; Jia Liu; Ji Wu; David R. Chadwick; Davey L. Jones; et al. (Agriculture, Ecosystems & Environment, 2025)

Do biopores created by perennial fodder crops improve the growth of subsequent annual crops? A synthesis of multiple field experiments - Dominik Behrend; Miriam Athmann; Eusun Han; Paul Martin Küpper; Ute Perkons; Sara L. Bauke; Ulrich Köpke; Timo Kautz; Thomas Gaiser; Sabine J. Seidel (Field Crops Research, 2025)

Warming effects on pelagic carbon metabolism is related to substrate composition and bacterioplankton community history - Zhendu Mao; Yixuan Han; Fan Xun; Shilin An; Biao Li; Yujing Wang; He Chen; Qinglong L. Wu; Peng Xing (Water Research, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Thermodynamic analysis of the effect of palm stearin on fully hydrogenated soybean oil coatings in granular micronutrient premixes - Y.K. Kiki Chan; Fletcher Han; Yu-Ling Cheng; Levente L. Diosady (Food Chemistry, 2025)

Grassland bud and shoot demographic responses to single and recurrent droughts vary across an aridity gradient - Niwu Te; Robert J. Griffin‐Nolan; Ingrid J. Slette; Yuan Shi; Lin Song; Jiaqi Chen; Hongqiang Wang; Jianqiang Qian; Qiang Yu; Zhengwen Wang; Xiaotao Lü; Xingguo Han; et al. (Ecology, 2025)
Clonal demographic traits play important roles in regulating community dynamics. Yet, it remains unclear how the responses of these clonal traits to drought might depend on previous drought exposure, and how drought responses vary among grasslands. We conducted a repeated drought experiment across four grasslands along an aridity gradient in northern China. We assessed the effects of single (precipitation reduction in 2021–2022) versus recurrent (precipitation reduction in 2015–2018 and 2021–2022) drought on bud density, shoot density, and the ratio of bud to shoot density. Drought reduced bud density at all grasslands and shoot density at most grasslands. Drought reduced the ratio of bud‐to‐shoot density only in the most arid grasslands. Recurrent drought had larger negative effects than a single drought on bud density and composition of bud and shoot at only one of four grasslands, and on shoot density at two of four grasslands. Our results suggest that previous drought exposure can alter the response of plant clonal demographic traits to subsequent drought in some but not all grasslands, and that responses can vary with mean climate.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Epilimnetic oligotrophication increases contribution of oxic methane production to atmospheric methane flux from stratified lakes - Fan Xun; Muhua Feng; Cheng Zhao; Wenlei Luo; Xiaotong Han; Zhen Ci; Yifan Yin; Rong Wang; Qinglong L. Wu; Hans-Peter Grossart; Peng Xing (Water Research, 2025)

Layer symmetry and irradiation dominate the oxidation capability of birnessite on biogenic isoprene - Zhengyan Han; Xuehua Zou; Haibo Liu; Tianhu Chen; Can Wang; Ping Zhang; Dong Chen; Yuefei Zhou; Qiaoqin Xie; Qimengzi Wang; Jinyong Chen; Aidi Huang; et al. (Science of The Total Environment, 2024)

Interpretable regional meteorological feature extraction enhances deep learning for extended 120-h PM2.5 forecasting - Xinyi Liu; Xueting Pu; Chengwei Lu; Han Zhang; Tao Li; Michael L. Grieneisen; Jucheng Li; Ning Ma; Chang Yan; Yu Zhan; Fumo Yang (Journal of Cleaner Production, 2024)

Laboratory evaluation of wicking geotextile for moisture reduction in silty sands at different fines contents - Md Wasif Zaman; Jie Han; Mozaher Ul Kabir; Robert L. Parsons (Geotextiles and Geomembranes, 2024)

Methylparaben changes the community composition, structure, and assembly processes of free-living bacteria, phytoplankton, and zooplankton - Man Wang; Shengxing Wang; Huabing Li; Zhendu Mao; Yiwei Lu; Yunshan Cheng; Xiaotong Han; Yujing Wang; Yanru Liu; Shiqiang Wan; Li-Jun Zhou; Qinglong L. Wu (Environmental Research, 2024)

Kidney tissue loading reduces the critical cooling/warming rates of cryoprotective solutions - Zonghu Han; Lakshya Gangwar; Bat-Erdene Namsrai; Joseph S. Rao; Michael L. Etheridge; Jeunghwan Choi; Erik B. Finger; John C. Bischof (Cryobiology, 2024)

Kidney tissue loading reduces the critical cooling and warming rates of VS55 and VMP cryoprotective solutions - Zonghu Han; Lakshya Gangwar; Bat-Erdene Namsrai; Joseph Sushil Rao; Cameron Scheithauer; Michael L. Etheridge; Erik B. Finger; John C. Bischof; Jeunghwan Choi (Cryobiology, 2024)

ACVR1/ALK2-p21 signaling axis modulates proliferation of the venous endothelium in the retinal vasculature - Boryeong Pak; Minjung Kim; Orjin Han; Heon-Woo Lee; Alexandre Dubrac; Woosoung Choi; Jee Myung Yang; Kevin Boyé; Heewon Cho; Kathryn M. Citrin; Injune Kim; Anne Eichmann; et al. (Angiogenesis, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Unraveling the Potential of Solid-State Hydrogen Storage Materials: Insights from First Principle Calculations - Yaohui Xu; Yang Zhou; Chaoqun Li; Shuai Dong; Hao Liu; Weijie Yang; Yuting Li; Han Jiang; Zhao Ding; Hao Li; Leon L. Shaw (Fuel, 2024)

Effect of solid-state fermentation on the functionality, digestibility, and volatile profiles of pulse protein isolates - Andrea K. Stone; Dai Shi; Enyu Liu; Zahra Jafarian; Caishuang Xu; Aarti Bhagwat; Yuping Lu; Leonid Akhov; Jessica Gerein; Xiumei Han; L. Irina Zaharia; Nandhakishore Rajagopalan; et al. (Food Bioscience, 2024)

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Purkinje Cell Dendritic Swellings: A Postmortem Study of Essential Tremor and Other Cerebellar Degenerative Disorders - Elan D. Louis; Sheng-Han Kuo; Phyllis L. Faust (The Cerebellum, 2024)

Cytotoxicity and cell membrane interactions of choline-based ionic liquids: Comparing amino acids, acetate, and geranate anions - Mohamad El Mohamad; Qi Han; Brendan Dyett; Haitao Yu; Sara Edgecomb; Mercedes C. Pride; Claylee M. Chism; Angela Roberts; Deauntaye Jones; Eden E.L. Tanner; Calum J. Drummond; Tamar L. Greaves; et al. (Chemosphere, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Proximity Labelling Confirms the Involvement of Papain-Like Cysteine Proteases and Chaperones in Cyclotide Biosynthesis - Meng-Han Lee; Mark A. Jackson; Fabian B. H. Rehm; Deborah S. Barkauskas; Wing L. Ho; Kuok Yap; David J. Craik; Edward K. Gilding (Plant Molecular Biology Reporter, 2024)
Cyclotides are disulfide-rich insecticidal peptides from plants that harbour a cyclic cystine knot motif that imparts them with high stability. Like most ribosomally encoded peptides, cyclotides are produced as precursor proteins that are subsequently processed to maturity through proteolytic activity. Although the final maturation of the prototypic cyclotide kalata B1 (kB1) is known to involve asparaginyl endopeptidases, the role of the in planta folding machinery is less well characterized, as is also the case for in planta N-terminal processing enzyme(s). Here, we used proximity labelling to identify proteins involved in the biosynthesis of kB1 in both a cyclotide-bearing plant species, Petunia × hybrida [Regel], and in Nicotiana benthamiana [Domin] that does not naturally produce cyclotides. Together, several ER resident chaperones, protein disulfide isomerases, a papain-like cysteine protease, and an asparaginyl endopeptidase were identified in the kB1 interactome. We found that overexpression of the identified papain-like cysteine protease resulted in an improvement in the yield of cyclic kB1, while this was not the case for the overexpression of protein disulfide isomerases, despite their interaction being verified using bimolecular fluorescence complementation. Together, these results provide a significant advance in our understanding of the role of auxiliary biosynthetic elements for heterologous cyclotide production in plants.

Palaeontological signatures of the Anthropocene are distinct from those of previous epochs - Mark Williams; Jan Zalasiewicz; Anthony D. Barnosky; Reinhold Leinfelder; Martin J. Head; Colin N. Waters; Francine M.G. McCarthy; Alejandro Cearreta; David C. Aldridge; Mary McGann; Paul B. Hamilton; Colin P. Summerhayes; et al. (Earth-Science Reviews, 2024)

Human atherosclerotic plaque transcriptomics reveals endothelial beta-2 spectrin as a potential regulator a leaky plaque microvasculature phenotype - Timo Rademakers; Marco Manca; Han Jin; Tanguy Orban; Ljubica Matic Perisic; Hubertus J. M. Frissen; Frank Rühle; Petra Hautvast; Jos van Rijssel; Kim van Kuijk; Barend M. E. Mees; Carine J. Peutz-Kootstra; et al. (Angiogenesis, 2024)
The presence of atherosclerotic plaque vessels is a critical factor in plaque destabilization. This may be attributable to the leaky phenotype of these microvessels, although direct proof for this notion is lacking. In this study, we investigated molecular and cellular patterns of stable and hemorrhaged human plaque to identify novel drivers of intraplaque vessel dysfunction. From transcriptome data of a human atherosclerotic lesion cohort, we reconstructed a co-expression network, identifying a gene module strongly and selectively correlated with both plaque microvascular density and inflammation. Spectrin Beta Non-Erythrocytic 1 ( sptbn1 ) was identified as one of the central hubs of this module (along with zeb1 and dock1 ) and was selected for further study based on its predominant endothelial expression. Silencing of sptbn1 enhanced leukocyte transmigration and vascular permeability in vitro, characterized by an increased number of focal adhesions and reduced junctional VE-cadherin. In vivo, sptbn1 knockdown in zebrafish impaired the development of the caudal vein plexus. Mechanistically, increased substrate stiffness was associated with sptbn1 downregulation in endothelial cells in vitro and in human vessels. Plaque SPTBN1 mRNA and protein expression were found to correlate with an enhanced presence of intraplaque hemorrhage and future cardiovascular disease (CVD) events during follow-up. In conclusion, we identify SPTBN1 as a central hub gene in a gene program correlating with plaque vascularisation. SPTBN1 was regulated by substrate stiffness in vitro while silencing blocked vascular development in vivo, and compromised barrier function in vitro. Together, SPTBN1 is identified as a new potential regulator of the leaky phenotype of atherosclerotic plaque microvessels.

Correction to: Lifespan effects in male UM‑HET3 mice treated with sodium thiosulfate, 16‑hydroxyestriol, and late‑start canagliflozin - Richard A. Miller; David E. Harrison; Gino A. Cortopassi; Ishmael Dehghan; Elizabeth Fernandez; Michael Garratt; John G. Geisler; Brett C. Ginsburg; Melissa L. Han; Nisi Jiang; Catherine C. Kaczorowski; Navasuja Kumar; et al. (GeroScience, 2024)

The effect of turbidity on female mate choice in the guppy, Poecilia reticulata - Shreya Venkatesan; Meng-Han Joseph Chung; Diego Moura-Campos; Megan L. Head (Animal Behaviour, 2024)

Major source categories of PM2.5 oxidative potential in wintertime Beijing and surroundings based on online dithiothreitol-based field measurements - Rico K.Y. Cheung; Lu Qi; Manousos I. Manousakas; Joseph V. Puthussery; Yan Zheng; Theodore K. Koenig; Tianqu Cui; Tiantian Wang; Yanli Ge; Gaoyuan Wei; Yu Kuang; Mengshuang Sheng; et al. (Science of The Total Environment, 2024)

Biomarker and proteome analysis of milk from dairy cows with clinical mastitis: Determining the effect of different bacterial pathogens on the response to infection - Emily L. O'Reilly; Lorenzo Viora; Francisco Malcata; P. Theo Pepler; Ruth Zadoks; Nicola Brady; Han Quang Hanh; Mark McLaughlin; Anita Horvatic; Andrea Gelemanovic; Josipa Kules; Vladimir Mrljak; et al. (Research in Veterinary Science, 2024)

Needle and bud scale development in Picea abies - Carol L. Wenzel; Anny Y. Xia; Rebecca Saunders; Han Han Ly; Anson Mo; David M. Holloway (Trees, 2024)

Bioturbation by Benthic Stingrays Alters the Biogeomorphology of Tidal Flats - Janne Nauta; Guido Leurs; Brian O. Nieuwenhuis; Donné R. A. H. Mathijssen; Han Olff; Tjeerd J. Bouma; Daphne van der Wal; Nadia Hijner; Aissa Regalla; Samuel Ledo Pontes; Laura L. Govers (Ecosystems, 2024)
Fishing-down-marine-food-webs has resulted in alarming declines of various species worldwide. Benthic rays are one examples of such overexploited species. On tidal flats, these rays are highly abundant and play an ecologically important role. They use tidal flats as refuge, feeding and resting grounds, during which they bury into the sediment, which results in sediment bioturbation. Changes in bioturbation intensity, following ray removal, may affect the biogeomorphology of tidal flats with possible cascading effects on the macrozoobenthic community. However, it is poorly understood how these indirect effects could influence ecosystem function. We therefore studied the geomorphic impact of benthic rays (specifically the pearl whipray/stingray Fontitrygon margaritella ) on the tropical tidal flats of the Bijagós Archipelago, Guinea-Bissau, on a landscape scale. We investigated 1) bioturbation rates by rays using drone and ground surveys, 2) the spatial distribution of ray pits on multiple tidal flats, 3) the impact of rays on sediment properties and macrozoobenthos by experimental exclusion (15 months). Benthic rays bioturbated 3.7 ± 0.35% of the tidal flat’s sediment surface per day over one single 24-h period, which equals a complete top-sediment-surface turnover every 27 days. The spatial distribution of ray pits was affected by tidal flat geomorphology since pits decayed faster at areas exposed to strong hydrodynamic forces. Predator exclusion altered sediment properties, leading to changes in sedimentation (− 17%) and erosion (− 43%) rates. In addition, macrozoobenthic species composition changed, marked by an increase in Capitellidae worms and a greater biomass of Malacostraca over time. These changes indicated substantial effects of ray bioturbation on the biotic and geomorphic landscape of tidal flats. Overall, we conclude that changing abundances of benthic rays can have clear landscape-wide geomorphological effects on intertidal ecosystems. These indirect consequences of fisheries should be incorporated in integrative management plans to preserve tidal flats and connected ecosystems.

Quantitative Applications of Weather Satellite Data for Nowcasting: Progress and Challenges - Jun Li; Jing Zheng; Bo Li; Min Min; Yanan Liu; Chian-Yi Liu; Zhenglong Li; W. Paul Menzel; Timothy J. Schmit; John L. Cintineo; Scott Lindstrom; Scott Bachmeier; et al. (Journal of Meteorological Research, 2024)

Reintroduction of self-facilitating feedbacks could advance subtidal eelgrass (Zostera marina) restoration in the Dutch Wadden Sea - Katrin Rehlmeyer; Oscar Franken; Tjisse van der Heide; Sander J. Holthuijsen; Kasper J. Meijer; Han Olff; Wouter Lengkeek; Karin Didderen; Laura L. Govers (Frontiers in Marine Science, 2024)
Extensive subtidal eelgrass ( Zostera marina ) meadows (~150 km 2 ) once grew in the Dutch Wadden Sea, supporting diverse species communities, but disappeared in the 1930s and have been absent ever since. Identifying the most critical bottlenecks for eelgrass survival is a crucial first step for reintroduction through active restoration measures. Seagrasses are ecosystem engineers, inducing self-facilitating feedbacks that ameliorate stressful conditions. Consequently, once seagrass, including its self-facilitating feedbacks, is lost, reintroduction can be challenging. Therefore, we aimed to test whether 1) sediment stabilization and 2) hydrodynamic stress relief would facilitate eelgrass survival in a field experiment replicated at two sites in the Dutch Wadden Sea. We induced feedbacks using biodegradable root-mimicking structures (BESE-elements) and sandbag barriers. Root mimics had a significant positive effect, increasing the chances of short-term survival by +67% compared to controls. Contrary to our expectations, barriers decreased short-term survival probabilities by -26%, likely due to hydrodynamic turbulence created by the barrier edges, leading to high erosion rates (-14 cm). Site selection proved crucial as short-term survival was entirely negated on one of the two study sites after five weeks due to high floating and epiphytic macroalgae loads. No long-term survival occurred, as plants died at the other site two weeks later. Overall, we found that sediment stabilization by root-mimicking structures was promising, whereas manipulating hydrodynamic forces using sandbag barriers had adverse effects. A mechanistic understanding of transplant failures is required before attempting large-scale restoration. Our study indicates that for seagrass restoration in the Wadden Sea, one should carefully consider 1) the reintroduction of positive feedbacks through restoration tools, 2) donor population choice and transplantation timing, and 3) site selection based on local biotic and abiotic conditions. Optimizing these restoration facets might lower additive stress to a degree that allows long-term survival.

Consensus Paper: Cerebellum and Reward - Mario Manto; Michael Adamaszek; Richard Apps; Erik Carlson; Julian Guarque-Chabrera; Elien Heleven; Shinji Kakei; Kamran Khodakhah; Sheng-Han Kuo; Chi-Ying R. Lin; Mati Joshua; Marta Miquel; et al. (The Cerebellum, 2024)

Lifespan effects in male UM-HET3 mice treated with sodium thiosulfate, 16-hydroxyestriol, and late-start canagliflozin - Richard A. Miller; David E. Harrison; Gino A. Cortopassi; Ishmael Dehghan; Elizabeth Fernandez; Michael Garratt; John G. Geisler; Brett C. Ginsburg; Melissa L. Han; Catherine C. Kaczorowski; Navasuja Kumar; Scott F. Leiser; et al. (GeroScience, 2024)

Content Validity of the Modified Functional Scale for the Assessment and Rating of Ataxia (f-SARA) Instrument in Spinocerebellar Ataxia - Michele Potashman; Katja Rudell; Ivanna Pavisic; Naomi Suminski; Rinchen Doma; Maggie Heinrich; Linda Abetz-Webb; Melissa Wolfe Beiner; Sheng-Han Kuo; Liana S. Rosenthal; Theresa Zesiwicz; Terry D. Fife; et al. (The Cerebellum, 2024)
The functional Scale for the Assessment and Rating of Ataxia (f-SARA) assesses Gait, Stance, Sitting, and Speech. It was developed as a potentially clinically meaningful measure of spinocerebellar ataxia (SCA) progression for clinical trial use. Here, we evaluated content validity of the f-SARA. Qualitative interviews were conducted among individuals with SCA1 ( n = 1) and SCA3 ( n = 6) and healthcare professionals (HCPs) with SCA expertise (USA, n = 5; Europe, n = 3). Interviews evaluated symptoms and signs of SCA and relevance of f-SARA concepts for SCA. HCP cognitive debriefing was conducted. Interviews were recorded, transcribed, coded, and analyzed by ATLAS.TI software. Individuals with SCA1 and 3 reported 85 symptoms, signs, and impacts of SCA. All indicated difficulties with walking, stance, balance, speech, fatigue, emotions, and work. All individuals with SCA1 and 3 considered Gait, Stance, and Speech relevant f-SARA concepts; 3 considered Sitting relevant (42.9%). All HCPs considered Gait and Speech relevant; 5 (62.5%) indicated Stance was relevant. Sitting was considered a late-stage disease indicator. Most HCPs suggested inclusion of appendicular items would enhance clinical relevance. Cognitive debriefing supported clarity and comprehension of f-SARA. Maintaining current abilities on f-SARA items for 1 year was considered meaningful for most individuals with SCA1 and 3. All HCPs considered meaningful changes as stability in f-SARA score over 1–2 years, 1–2-point change in total f-SARA score, and deviation from natural history. These results support content validity of f-SARA for assessing SCA disease progression in clinical trials.

Dynamic land cover evapotranspiration model algorithm: DyLEMa - Jeongho Han; Jorge A. Guzman; Maria L. Chu (Computers and Electronics in Agriculture, 2024)

Mechanism of organic phosphorus transformation and its impact on the primary production in a deep oligotrophic plateau lake during stratification - Xiaotong Han; Fan Xun; Xianlong Zhu; Cheng Zhao; Wenlei Luo; Yanru Liu; Man Wang; Di Xu; Shiqiang Wan; Qinglong L. Wu; Peng Xing (Water Research, 2024)

Cancellation of resonance for elastically supported beams subjected to successive moving loads: Optimal design condition for bridges - Y.B. Yang; L. Chen; Z.L. Wang; Z.Y. Liu; Ding-Han Liu; H. Yao; Y. Zheng (Engineering Structures, 2024)

Mutual facilitation between foundation species Mytilus edulis and Lanice conchilega promotes habitat heterogeneity on tidal flats - Janne Nauta; Kasper J. Meijer; Lissie W. de Groot; Valérie C. Reijers; Tjeerd J. Bouma; Daphne van der Wal; Han Olff; Sander J. Holthuijsen; Allert I. Bijleveld; Henk W. van der Veer; Oscar Franken; Laura L. Govers (Frontiers in Marine Science, 2024)
Foundation species that modify their habitat can facilitate other species, including other foundation species. Most studies focus solely on a single foundation species, overlooking such facilitation cascades. In this study, we investigated the interactions between the two coastal foundation species Mytilus edulis (blue mussel) and Lanice conchilega (sand mason worm). We investigated whether these species engage in facilitative interactions or if their association simply reflects a shared ecological niche on the soft-sediment intertidal flats of the Dutch Wadden Sea. To do so, we performed species distribution modeling, manipulative field experiments, and field surveys. We found a positive association between both foundation species, with a 2.45 times higher occurrence of both species compared to a random distribution. In addition, these species partially occupied the same ecological niche. We demonstrated that L. conchilega provided settlement substrate for M. edulis spat, increasing densities by 400 times compared to bare plots. Furthermore, M. edulis reefs facilitated L. conchilega occurrence in the wake of the reef. Biogenic reef development revealed that this interspecific facilitation resulted in spatial habitat heterogeneity. Therefore, we conclude that interspecific facilitation can significantly enhance the occurrence of these two important intertidal foundation species. Acknowledgment of such complex facilitation interactions has an untapped potential for improving the success of restoration and conservation programs.

Lower soil nitrogen-oxide emissions associated with enhanced denitrification under replacing mineral fertilizer with manure in orchard soils - Pinshang Xu; Zhutao Li; Shumin Guo; Davey L. Jones; Jinyang Wang; Zhaoqiang Han; Jianwen Zou (Science of The Total Environment, 2024)

Spontaneous rupture of the right aortic sinus resulting in a sterile aorto-atrial fistula in a pet rabbit (Oryctolagus cuniculus) - L. Cheung; B.A. Scansen; R. Baden; C.Q. Sloan; M. Garcia; S. Han; M.J. Sadar (Journal of Veterinary Cardiology, 2024)

MOFs-Based Materials for Solid-State Hydrogen Storage: Strategies and Perspectives - Yuting Li; Qifei Guo; Zhao Ding; Han Jiang; Hang Yang; Wenjia Du; Yang Zheng; Kaifu Huo; Leon L. Shaw (Chemical Engineering Journal, 2024)

Farmland abandonment and vegetation succession mediate soil properties but are determined by the duration of conversion - Xiheng Lv; Qiang Tang; Chen Han; Minxin Song; Chuan Yuan; Qingyuan Yang; Jie Wei; Xiubin He; Adrian L. Collins (CATENA, 2024)

Diffusion kinetic processes and release risks of trace metals in plateau lacustrine sediments - Xiang Gu; Xiaotong Han; Peng Xing; Di Xu; Shiqiang Wan; Qinglong L. Wu; Fengchang Wu (Journal of Hazardous Materials, 2024)

The impact of marital status on tumor aggressiveness, treatment, and screening among black and white men diagnosed with prostate cancer - Saira Khan; Lindsay Fuzzell; Marvin Langston; Yunan Han; Justin X. Moore; Keon Gilbert; Siobhan Sutcliffe; Jeannette T. Bensen; James L. Mohler; Elizabeth T.H. Fontham; Lixin Song; Marquita W. Lewis-Thames (Cancer Causes & Control, 2024)

The dual roles of dissimilatory iron reduction in the carbon cycle: The “iron mesh” effect can increase inorganic carbon sequestration - Cheng Zhao; Fan Xun; Biao Li; Xiaotong Han; Huan Liu; Yingxun Du; Qinglong L. Wu; Peng Xing (Global Change Biology, 2024)
Dissimilatory iron reduction (DIR) can drive the release of organic carbon (OC) as carbon dioxide (CO 2 ) by mediating electron transfer between organic compounds and microbes. However, DIR is also crucial for carbon sequestration, which can affect inorganic‐carbon redistribution via iron abiotic–phase transformation. The formation conditions of modern carbonate‐bearing iron minerals (IC Fe ) and their potential as a CO 2 sink are still unclear. A natural environment with modern IC Fe , such as karst lake sediment, could be a good analog to explore the regulation of microbial iron reduction and sequential mineral formation. We find that high porosity is conducive to electron transport and dissimilatory iron‐reducing bacteria activity, which can increase the iron reduction rate. The iron‐rich environment with high calcium and OC can form a large sediment pore structure to support rapid DIR, which is conducive to the formation and growth of IC Fe . Our results further demonstrate that the minimum DIR threshold suitable for IC Fe formation is 6.65 μmol g −1 dw day −1 . DIR is the dominant pathway (average 66.93%) of organic anaerobic mineralization, and the abiotic‐phase transformation of Fe 2+ reduces CO 2 emissions by ~41.79%. Our findings indicate that as part of the carbon cycle, DIR not only drives mineralization reactions but also traps carbon, increasing the stability of carbon sinks. Considering the wide geographic distribution of DIR and IC Fe , our findings suggest that the “iron mesh” effect may become an increasingly important vector of carbon sequestration.

Corrigendum to “Elevated parkinsonism pathological markers in dopaminergic neurons with developmental exposure to atrazine” [Sci. Total Environ. 908 2024: Article 168307] - Han Zhao; Junkai Xie; Shichen Wu; Xihui Zhao; Oscar F. Sánchez; Sehong Min; Sayan Dutta; Jean-Christophe Rochet; Jennifer L. Freeman; Chongli Yuan (Science of The Total Environment, 2024)

Lower to Middle Triassic conodont biostratigraphy and carbonate carbon isotope chemostratigraphy of the Zuodeng area, Guangxi, South China, and its relevance for stratigraphic correlation from the Induan to the Anisian - Shunling Wu; Martyn L. Golding; He Zhao; Chen Han; Xiumei Zhang; Zhong-Qiang Chen; Zhengyi Lyu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Cross-shelf processes of terrigenous organic matter drive mercury speciation on the east siberian shelf in the Arctic Ocean - Jihee Kim; Anne L. Soerensen; Hakwon Jeong; Seorin Jeong; Eunsuk Kim; Yung Mi Lee; Young Keun Jin; Tae Siek Rhee; Jong Kuk Hong; Seunghee Han (Environmental Pollution, 2024)

Effectiveness and potential mechanism of hydrothermal modification of attapulgite for cadmium passivation in soil - G. Ma; J. Ren; L. Tao; X. Han; C. Liao; Y. Zhou; J. Ding; Y. Zhou; K. Bi (International Journal of Environmental Science and Technology, 2024)

Grassland sensitivity to drought is related to functional composition across E ast A sia and N orth A merica - Lin Song; Robert J. Griffin‐Nolan; Taofeek O. Muraina; Jiaqi Chen; Niwu Te; Yuan Shi; Kenneth D. Whitney; Bingchuan Zhang; Qiang Yu; Melinda D. Smith; Xiaoan Zuo; Zhengwen Wang; et al. (Ecology, 2024)
Plant traits can be helpful for understanding grassland ecosystem responses to climate extremes, such as severe drought. However, intercontinental comparisons of how drought affects plant functional traits and ecosystem functioning are rare. The Extreme Drought in Grasslands experiment (EDGE) was established across the major grassland types in East Asia and North America (six sites on each continent) to measure variability in grassland ecosystem sensitivity to extreme, prolonged drought. At all sites, we quantified community‐weighted mean functional composition and functional diversity of two leaf economic traits, specific leaf area and leaf nitrogen content, in response to drought. We found that experimental drought significantly increased community‐weighted means of specific leaf area and leaf nitrogen content at all North American sites and at the wetter East Asian sites, but drought decreased community‐weighted means of these traits at moderate to dry East Asian sites. Drought significantly decreased functional richness but increased functional evenness and dispersion at most East Asian and North American sites. Ecosystem drought sensitivity (percentage reduction in aboveground net primary productivity) positively correlated with community‐weighted means of specific leaf area and leaf nitrogen content and negatively correlated with functional diversity (i.e., richness) on an intercontinental scale, but results differed within regions. These findings highlight both broad generalities but also unique responses to drought of community‐weighted trait means as well as their functional diversity across grassland ecosystems.

Early-Life Social Determinants of SCA6 Age at Onset, Severity, and Progression - Tiffany X. Chen; Hannah L. Casey; Chi-Ying R. Lin; Theresa A. Boyle; Jeremy D. Schmahmann; Gilbert J. L’Italien; Sheng-Han Kuo; Christopher M. Gomez (The Cerebellum, 2024)
SCA6 patients with the same size CAG repeat allele can vary significantly in age at onset (AAO) and clinical progression. The specific external factors affecting SCA6 have yet to be investigated. We assessed the effect of early life events on AAO, severity, and progression in SCA6 patients using a social determinant of health approach. We performed a survey of biological and social factors in SCA6 patients enrolled in the SCA6 Network at the University of Chicago. AAO of ataxia symptoms and patient-reported outcome measure (PROM) of ataxia were used as primary outcome measures. Least absolute shrinkage and selection operation (LASSO) regressions were used to identify which early life factors are predictive of SCA6 AAO, severity, and progression. Multiple linear regression models were then used to assess the degree to which these determinants influence SCA6 health outcomes. A total of 105 participants with genetically confirmed SCA6 completed the assessments. SCA6 participants with maternal difficulty during pregnancy, active participation in school sports, and/or longer CAG repeats were determined to have earlier AAO. We found a 13.44-year earlier AAO for those with maternal difficulty in pregnancy than those without ( p = 0.008) and a 12.31-year earlier AAO for those active in school sports than those who were not ( p < 0.001). Higher education attainment was associated with decreased SCA6 severity and slower progression. Early life biological and social factors can have a strong influence on the SCA6 disease course, indicating that non-genetic factors can contribute significantly to SCA6 health outcomes.

The Cerebellar Cognitive Affective/Schmahmann Syndrome Scale in Spinocerebellar Ataxias - Louisa P. Selvadurai; Susan L. Perlman; Tetsuo Ashizawa; George R. Wilmot; Chiadi U. Onyike; Liana S. Rosenthal; Vikram G. Shakkottai; Henry L. Paulson; Sub H. Subramony; Khalaf O. Bushara; Sheng-Han Kuo; Cameron Dietiker; et al. (The Cerebellum, 2024)

Elevated parkinsonism pathological markers in dopaminergic neurons with developmental exposure to atrazine - Han Zhao; Junkai Xie; Shichen Wu; Xihui Zhao; Oscar F. Sánchez; Sehong Min; Jean-Christophe Rochet; Jennifer L. Freeman; Chongli Yuan (Science of The Total Environment, 2024)

Effect of wastewater collection and concentration methods on assessment of viral diversity - Yabing Li; Brijen Miyani; Kevin L. Childs; Shin-Han Shiu; Irene Xagoraraki (Science of The Total Environment, 2024)

Upper Triassic (middle Norian) conodont biostratigraphy succession from Qamdo, eastern Tibet - Zhengyi Lyu; Martyn L. Golding; He Zhao; Huazhou Yao; Xiangdong Wang; Lei Zhang; Yangui Li; Chen Han (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Effect of micro-fin tube geometry parameters on evaporator material savings - M.A. Kedzierski; L. Lin; K. Han (International Journal of Refrigeration, 2024)

The impact of inter- and intra-species spore density on germination of the food spoilage fungus Aspergillus niger - Maryam Ijadpanahsaravi; L. Basten Snoek; Wieke R. Teertstra; Han A.B. Wösten (International Journal of Food Microbiology, 2024)

Public tap water perceptions and potable reuse acceptance: A cognitive dissonance theoretical understanding - Jesse L. Barnes; Anjala S. Krishen; Han-fen Hu (Journal of Cleaner Production, 2023)

Model-guided design and optimization of CPA perfusion protocols for whole organ cryopreservation - Zonghu Han; Joseph S. Rao; Srivasupradha Ramesh; Jan Hergesell; Bat-Erdene Namsrai; Michael L. Etheridge; Erik B. Finger; John C. Bischof (Cryobiology, 2023)

SUCCESSFUL TRANSPLANT OF KIDNEYS AFTER VITRIFICATION AND NANOWARMING - Zonghu Han; Joseph S. Rao; Lakshya Gangwar; Bat-Erdene Namsrai; Jacqueline Pasek-Allen; Michael L. Etheridge; Erik B. Finger; John C. Bischof (Cryobiology, 2023)

Assessing cellular and organ-level health, viability, and function of vitrified kidneys and islets for transplantation - Joseph Sushil Rao; Zonghu Han; Li Zhan; Michael L. Ethridge; John C. Bischof; Erik B. Finger (Cryobiology, 2023)

Heterogeneity of increased biological age in type 2 diabetes correlates with differential tissue DNA methylation, biological variables, and pharmacological treatments - Briana N. Cortez; Hui Pan; Samuel Hinthorn; Han Sun; Nicola Neretti; Anna L. Gloyn; Cristina Aguayo-Mazzucato (GeroScience, 2023)

DNA methylation mediates overgrazing-induced clonal transgenerational plasticity - Jingjing Yin; Weibo Ren; Ellen L. Fry; Siyuan Sun; Huijie Han; Fenghui Guo (Science of The Total Environment, 2023)

Optimization of A2O–MBR–BAF–O3 combination process for domestic wastewater - L. Huang; J. Han; G. Wang; Y. Hou; Z. Li; F. Yi (International Journal of Environmental Science and Technology, 2023)

Integrated biochemostratigraphy of the Permian-Triassic boundary interval and Lower Triassic succession in the eastern Cimmerian continent (Baoshan block, West Yunnan, southwest China) - Shunling Wu; Chen Han; Martyn L. Golding; Zhong-Qiang Chen; Zhengyi Lyu; Laishi Zhao (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Model-Guided Design and Optimization of CPA Perfusion Protocols for Whole Organ Cryopreservation - Zonghu Han; Joseph Sushil Rao; Srivasupradha Ramesh; Jan Hergesell; Bat-Erdene Namsrai; Michael L. Etheridge; Erik B. Finger; John C. Bischof (Annals of Biomedical Engineering, 2023)
Vitrification could enable long-term organ preservation, but only after loading high-concentration, potentially toxic cryoprotective agents (CPAs) by perfusion. In this paper, we combine a two-compartment Krogh cylinder model with a toxicity cost function to theoretically optimize the loading of CPA (VMP) in rat kidneys as a model system. First, based on kidney perfusion experiments, we systematically derived the parameters for a CPA transport loading model, including the following: V b = 86.0% ( r a = 3.86 μm), L p = 1.5 × 10 –14 m 3 /(N·s), ω = 7.0 × 10 –13 mol/(N·s), σ = 0.10. Next, we measured the toxicity cost function model parameters as α = 3.12 and β = 9.39 × 10 –6 . Combining these models, we developed an improved kidney-loading protocol predicted to achieve vitrification while minimizing toxicity. The optimized protocol resulted in shorter exposure (25 min or 18.5% less) than the gold standard kidney-loading protocol for VMP, which had been developed based on decades of empirical practice. After testing both protocols on rat kidneys, we found comparable physical and biological outcomes. While we did not dramatically reduce toxicity, we did reduce the time. As our approach is now validated, it can be used on other organs lacking defined toxicity data to reduce CPA exposure time and provide a rapid path toward developing CPA perfusion protocols for other organs and CPAs.

Multiple spectroscopic insights into the interaction mechanisms between proteins and humic acid - Bo Gong; Wei Chen; Patrick H.-L. Sit; Xian-Wei Liu; Chen Qian; Han-Qing Yu (Water Research, 2023)

P09-32: The mechanism of PGE2 on apoptosis of rat ovarian granulosa cells induced by MEHP - S. Ren; X. Han; X. Li; X. Li; L. Ye (Toxicology Letters, 2023)

Learnings from rapid response efforts to remotely detect landslides triggered by the August 2021 Nippes earthquake and Tropical Storm Grace in Haiti - Pukar Amatya; Corey Scheip; Aline Déprez; Jean-Philippe Malet; Stephen L. Slaughter; Alexander L. Handwerger; Robert Emberson; Dalia Kirschbaum; Julien Jean-Baptiste; Mong-Han Huang; Marin K. Clark; Dimitrios Zekkos; et al. (Natural Hazards, 2023)
On August 14, 2021, a Mw 7.2 earthquake struck the Tiburon Peninsula of western Haiti triggering thousands of landslides. Three days after the earthquake on August 17, 2021, Tropical Storm Grace crossed shallow waters offshore of southern Haiti triggering more landslides worsening the situation. In the aftermath of these events, several organizations with disaster response capabilities or programs activated to provide information on the location of landslides to first responders on the ground. Utilizing remote sensing to support rapid response, one organization manually mapped initiation point of landslides and three automatically detected landslides. The 2021 Haiti event also provided a unique opportunity to test different automated landslide detection methods that utilized both SAR and optical data in a rapid response scenario where rapid situational awareness was critical. As the methods used are highly replicable, the main goal of this study is to summarize the landslide rapid response products released by the organizations, detection methods, quantify accuracy and provide guidelines on how some of the shortcomings encountered in this effort might be addressed in the future. To support this validation, a manually mapped polygon-based landslide inventory covering the entire affected area was created and is also released through this effort.

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Pre-differentiation GenX exposure induced neurotoxicity in human dopaminergic-like neurons - Shichen Wu; Junkai Xie; Han Zhao; Oscar Sanchez; Xihui Zhao; Jennifer L. Freeman; Chongli Yuan (Chemosphere, 2023)

Paleocurrent and paleowind direction reconstruction research progress and perspectives: a review - F. Y. Zhao; C. L. Hu; C. C. Han; Y. Q. Dong; Q. X. Yuan (Australian Journal of Earth Sciences, 2023)

Reduction in productivity of soybean plants infested with Neohyadatothrips variabilis (Thysanoptera: Thripidae) with and without soybean vein necrosis virus - Doris M. Lagos-Kutz; Michelle L. Pawlowski; Jaeyeong Han; Steven J. Clough; Glen L. Hartman (Phytoparasitica, 2023)
Soybean thrips, Neohyadatothrips variabilis (Beach), a vector of Soybean Vein Necrosis Virus (SVNV), has been recognized as a widespread pest of soybean [ Glycine max (L.) Merr.] in USA and Canada. Several experiments investigated the effect on soybean when infested with soybean thrips with and without SVNV. Experiment 1 compared soybean infested at V1 and V5 growth stages (GS) with soybean thrips without SVNV and noninfested plants. For plants infested at GS V1, plant height, number of seeds, and seed weights were reduced by 50, 80, and 75%, respectively. When plants were infested at GSs V1 and V5, the counts of soybean thrips peaked at 1,803 and 4,214 per plant 4 weeks after infestation (WAI), respectively. Experiment 2 used SVNV-infected soybean thrips and compared soybean infested versus control at GS V1 and V5. For plants infested at GS V1, plant height was reduced 77.8%, and plants died before setting pods. For plants infested at GS V5, height, number of seeds, and seed weights were reduced 56, 78, and 92%, respectively. When plants were infested at GSs V1 and V5, the counts of soybean thrips peaked at 282 and 883 per plant 2 WAI, respectively. Experiment 3, five soybean genotypes were infested with SVNV-infected thrips at GS V1. Number and weight of seeds per plant were higher and with lower visual disease ratings (progressive chlorosis, necrosis and rugosity) for the more resistant genotypes Merschman Kennedy and plant introduction (PI) 171451 than for the more susceptible genotypes: soybean breeding line LD12-12734a ( Rag1/2 ), cv Williamsfield Illini 3509N, and PI 417136.

Lead change of a HIF-2α antagonist guided by multiparameter optimization and utilization of an Olp→π*Ar interaction - Paul M. Wehn; Song Yang; Jonas A. Grina; James P. Rizzi; Stephen T. Schlachter; Bin Wang; Rui Xu; Hanbiao Yang; Xinlin Du; Guangzhou Han; Keshi Wang; Robert M. Czerwinski; et al. (Medicinal Chemistry Research, 2023)

Effects of aluminum ion on particle sizes and surface charges of exopolysaccharides from Rhizobium tropici and pH effects - Steve L. Larson; John H. Ballard; Kauri A. Runge; Huimin Zhang; Benjamin R. Breland; Zachary H. Nick; Ethan Tyler Vroman; Charles A. Weiss; Fengxiang X. Han (Rhizosphere, 2023)

Post-farming land restoration schemes exhibit higher soil aggregate stability and organic carbon: Evidence in the Three Gorges Reservoir Area, China - Chen Han; Minxin Song; Qiang Tang; Jie Wei; Xiubin He; Adrian L. Collins (CATENA, 2023)

Recent trends in management strategies for two major maize borers: Ostrinia nubilalis and Sesamia nonagrioides - Gülay Kaçar; Ana Butrón; Dimitrios Kontogiannatos; Peng Han; Maria Fernanda G. V. Peñaflor; Gema P. Farinós; Fangneng Huang; William D. Hutchison; Bruno H. S. de Souza; Rosa Ana Malvar; Anna Kourti; Ricardo Ramirez-Romero; et al. (Journal of Pest Science, 2023)

Iron oxides act as an alternative electron acceptor for aerobic methanotrophs in anoxic lake sediments - Biao Li; Ye Tao; Zhendu Mao; Qiujin Gu; Yixuan Han; Baolan Hu; Hongwei Wang; Anxing Lai; Peng Xing; Qinglong L Wu (Water Research, 2023)

Geochemical and thermodynamic constraints on Archean comagmatic volcanic and cumulate rocks from southern West Greenland - Lingyu Zhang; William R. Hyde; Christopher L. Kirkland; Yuesheng Han; Kristoffer Szilas (Geochimica et Cosmochimica Acta, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

An assessment model for mapping the susceptibility of deposits accumulation on insulators driven by remotely sensed data - G. Wen; G. Han; F. Zhou; L. Shen; Y. Ma; G. Qian; H. Pan; P. Kong; J. Luo (International Journal of Environmental Science and Technology, 2023)

The Anthropocene as an epoch is distinct from all other concepts known by this term: a reply to Swindles et al. (2023) - Martin J. Head; Colin N. Waters; Jan A. Zalasiewicz; Anthony D. Barnosky; Simon D. Turner; Alejandro Cearreta; Reinhold Leinfelder; Francine M.G. McCarthy; Daniel de B. Richter; Neil L. Rose; Yoshiki Saito; Davor Vidas; et al. (Journal of Quaternary Science, 2023)

Linking seed size and number to trait syndromes in trees - Michal Bogdziewicz; Marie‐Claire Aravena Acuña; Robert Andrus; Davide Ascoli; Yves Bergeron; Daniel Brveiller; Thomas Boivin; Raul Bonal; Thomas Caignard; Maxime Cailleret; Rafael Calama; Sergio Donoso Calderon; et al. (Global Ecology and Biogeography, 2023)
Aim Our understanding of the mechanisms that maintain forest diversity under changing climate can benefit from knowledge about traits that are closely linked to fitness. We tested whether the link between traits and seed number and seed size is consistent with two hypotheses, termed the leaf economics spectrum and the plant size syndrome, or whether reproduction represents an independent dimension related to a seed size–seed number trade‐off. Location Most of the data come from Europe, North and Central America and East Asia. A minority of the data come from South America, Africa and Australia. Time period 1960–2022. Major taxa studied Trees. Methods We gathered 12 million observations of the number of seeds produced in 784 tree species. We estimated the number of seeds produced by individual trees and scaled it up to the species level. Next, we used principal components analysis and generalized joint attribute modelling (GJAM) to map seed number and size on the tree traits spectrum. Results Incorporating seed size and number into trait analysis while controlling for environment and phylogeny with GJAM exposes relationships in trees that might otherwise remain hidden. Production of the large total biomass of seeds [product of seed number and seed size; hereafter, species seed productivity (SSP)] is associated with high leaf area, low foliar nitrogen, low specific leaf area (SLA) and dense wood. Production of high seed numbers is associated with small seeds produced by nutrient‐demanding species with softwood, small leaves and high SLA. Trait covariation is consistent with opposing strategies: one fast‐growing, early successional, with high dispersal, and the other slow‐growing, stress‐tolerant, that recruit in shaded conditions. Main conclusions Earth system models currently assume that reproductive allocation is indifferent among plant functional types. Easily measurable seed size is a strong predictor of the seed number and species seed productivity. The connection of SSP with the functional traits can form the first basis of improved fecundity prediction across global forests.

Where land meets sea: Intertidal areas as key‐habitats for sharks and rays - Guido Leurs; Brian O. Nieuwenhuis; Thije J. Zuidewind; Nadia Hijner; Han Olff; Laura L. Govers (Fish and Fisheries, 2023)
Intertidal habitats (i.e. marine habitats that are (partially) exposed during low tide) have traditionally been studied from a shorebird‐centred perspective. We show that these habitats are accessible and important to marine predators such as elasmobranchs (i.e. sharks and rays). Our synthesis shows that at least 43 shark and 45 ray species, of which 54.5% are currently threatened, use intertidal habitats. Elasmobranchs use intertidal habitats mostly for feeding and as refugia, but also for parturition and thermoregulation. However, the motivation of intertidal habitat use remains unclear due to limitations to observe elasmobranch behaviour in these dynamic habitats. We argue that elasmobranch predators can play an important role in intertidal food webs by feeding on shared resources during high tide (i.e. ‘high‐tide predators’), which are accessible and also consumed by terrestrial or avian predators during low tide (i.e. ‘low‐tide predators’). In addition, elasmobranchs are able to change the bio‐geomorphology of intertidal habitats by increasing habitat heterogeneity due to feeding activities and may also alter resource availability for other consumers. We discuss how the ecological role of elasmobranchs in intertidal habitats is being affected by the continued overexploitation of these species, and conversely, how the global loss of intertidal areas poses an additional threat to an already vulnerable taxonomic group. We conclude that studies on intertidal ecology should include both low‐tide (e.g. shorebirds) and high‐tide (e.g. elasmobranchs) predatory guilds and their ecological interactions. The global loss of elasmobranch predatory species and intertidal habitat provides additional compelling arguments for the conservation of these areas.

Group resource-holding potential: worker size, colony size and the outcome of contests in ants - Shaolin Han; Ben L. Phillips; Mark A. Elgar (Animal Behaviour, 2023)

Evaluating potential ecological risks of emerging toxic elements in lacustrine sediments: A case study in Lake Fuxian, China - Yixuan Han; Fan Xun; Cheng Zhao; Biao Li; Wenlei Luo; Muhua Feng; Di Xu; Peng Xing; Qinglong L. Wu (Environmental Pollution, 2023)

SCAview: an Intuitive Visual Approach to the Integrative Analysis of Clinical Data in Spinocerebellar Ataxias - Mischa Uebachs; Philipp Wegner; Sebastian Schaaf; Simon Kugai; Heike Jacobi; Sheng-Han Kuo; Tetsuo Ashizawa; Juliane Fluck; Sophie Tezenas du Montcel; Peter Bauer; Paola Giunti; Arron Cook; et al. (The Cerebellum, 2023)
With SCAview, we present a prompt and comprehensive tool that enables scientists to browse large datasets of the most common spinocerebellar ataxias intuitively and without technical effort. Basic concept is a visualization of data, with a graphical handling and filtering to select and define subgroups and their comparison. Several plot types to visualize all data points resulting from the selected attributes are provided. The underlying synthetic cohort is based on clinical data from five different European and US longitudinal multicenter cohorts in spinocerebellar ataxia type 1, 2, 3, and 6 (SCA1, 2, 3, and 6) comprising > 1400 patients with overall > 5500 visits. First, we developed a common data model to integrate the clinical, demographic, and characterizing data of each source cohort. Second, the available datasets from each cohort were mapped onto the data model. Third, we created a synthetic cohort based on the cleaned dataset. With SCAview, we demonstrate the feasibility of mapping cohort data from different sources onto a common data model. The resulting browser-based visualization tool with a thoroughly graphical handling of the data offers researchers the unique possibility to visualize relationships and distributions of clinical data, to define subgroups and to further investigate them without any technical effort. Access to SCAview can be requested via the Ataxia Global Initiative and is free of charge.

Comprehensive compositional assessment of bioactive compounds in diverse pea accessions - Xiumei Han; Leonid Akhov; Paula Ashe; Courteney Lewis; Leah Deibert; L. Irina Zaharia; Lily Forseille; Daoquan Xiang; Raju Datla; Matthew Nosworthy; Carol Henry; Jitao Zou; et al. (Food Research International, 2023)

Response to Merritts et al. (2023): The Anthropocene is complex. Defining it is not - Colin N. Waters; Martin J. Head; Jan Zalasiewicz; Francine M.G. McCarthy; Scott L. Wing; Peter K. Haff; Mark Williams; Anthony D. Barnosky; Barbara Fiałkiewicz-Kozieł; Reinhold Leinfelder; J.R. McNeill; Neil L. Rose; et al. (Earth-Science Reviews, 2023)

Correction: Cryopreservation of Whole Rat Livers by Vitrification and Nanowarming - Anirudh Sharma; Charles Y. Lee; Bat-Erdene Namsrai; Zonghu Han; Diane Tobolt; Joseph Sushil Rao; Zhe Gao; Michael L. Etheridge; Michael Garwood; Mark G. Clemens; John C. Bischof; Erik B. Finger (Annals of Biomedical Engineering, 2023)

Cryopreservation of Whole Rat Livers by Vitrification and Nanowarming - Anirudh Sharma; Charles Y. Lee; Bat-Erdene Namsrai; Zonghu Han; Diane Tobolt; Joseph Sushil Rao; Zhe Gao; Michael L. Etheridge; Michael Garwood; Mark G. Clemens; John C. Bischof; Erik B. Finger (Annals of Biomedical Engineering, 2023)

Responses of a semiarid grassland to recurrent drought are linked to community functional composition - Wentao Luo; Taofeek O. Muraina; Robert J. Griffin‐Nolan; Wang Ma; Lin Song; Wei Fu; Qiang Yu; Alan K. Knapp; Zhengwen Wang; Xingguo Han; Scott L. Collins (Ecology, 2023)
Recurrent droughts are an inevitable consequence of climate change, yet how grasslands respond to such events is unclear. We conducted a 6‐year rainfall manipulation experiment in a semiarid grassland that consisted of an initial 2‐year drought (2015–2016), followed by a recovery period (2017–2018) and, finally, a second 2‐year drought (2019–2020). In each year, we estimated aboveground net primary productivity (ANPP), species richness, community‐weighted mean (CWM) plant traits, and several indices of functional diversity. The initial drought led to reduced ANPP, which was primarily driven by limited growth of forbs in the first year and grasses in the second year. Total ANPP completely recovered as the rapid recovery of grass productivity compensated for the slow recovery of forb productivity. The subsequent drought led to a greater reduction in total ANPP than the initial drought due to the greater decline of both grass and forb productivity. The structural equation models revealed that soil moisture influenced ANPP responses directly during the initial drought, and indirectly during the subsequent drought by lowering functional diversity, which resulted in reduced total ANPP. Additionally, ANPP was positively influenced by CWM plant height and leaf nitrogen during the recovery period and recurrent drought, respectively. Overall, the greater impact of the second drought on ecosystem function than the initial drought, as well as the underlying differential mechanism, underscores the need for an understanding of how increased drought frequency may alter semiarid grassland functioning.

Bacterial communities exhibit apparent phosphate concentration-related patterns of community composition, alpha diversity, and phylogenetic structure in the subtropical Daya Bay - Ye Chen; Guibin Ma; Chuangfeng Wu; Yuyang Peng; Xingyu Song; Qinglong L. Wu; Bo-Ping Han; Lijuan Ren (Frontiers in Marine Science, 2023)
Increasing anthropogenic activities have caused serious environmental problems and undesirable ecological impacts on bay ecosystems. However, much remains to be learned regarding marine bacterial community assembly and its underlying mechanisms under intensive anthropogenic activities in subtropical bays. In this study, we used the community assembly theory to analyze bacterial community distributions in the subtropical Daya Bay, where the habitats are subject to serious thermal discharge and excessive nutrient load. We found the community assembly of bacterial in the Daya Bay was dominantly shaped by environmental factor of seawater phosphate, followed by temperature, and silicate. High phosphate concentration significantly increased the relative abundance of Actinobacteria , Cyanobacteria , Planctomycetes , and Gammaprotecteria , but reduced the relative abundance of Bacteroidetes and Alphaproteobacteria . Moreover, higher phosphate concentration was found significantly and positively correlated with higher bacterial alpha diversity. Compared with stochastic processes, we found higher phosphate concentration imposed stronger deterministic processes (primarily homogeneous selection) in structuring bacterial community assembly in the subtropical Daya bay, and bacterial communities tended to be higher phylogenetically clustered in higher phosphate-concentration habitats. In summary, we proposed that phosphate is a major environmental determinant in the subtropical Daya Bay and influenced the relative importance of deterministic and stochastic processes in bacterial community assembly.

Halogen (F, Cl, Br, and I) concentrations of the upper continental crust through time as recorded in ancient glacial diamictite composites - Peng-Yuan Han; Roberta L. Rudnick; Tao He; Michael A.W. Marks; Shui-Jiong Wang; Richard M. Gaschnig; Zhao-Chu Hu (Geochimica et Cosmochimica Acta, 2023)

Elastoplastic Modelling of Porous Limestones with Porosity Dependency - B. Han; Q. M. Gong; X. L. Du; Y. Gao; W. Q. Shen; S. Lin (Rock Mechanics and Rock Engineering, 2022)

Probing the nature of soil organic matter - Zhe (Han) Weng; Johannes Lehmann; Lukas Van Zwieten; Stephen Joseph; Braulio S. Archanjo; Bruce Cowie; Lars Thomsen; Mark J. Tobin; Jitraporn Vongsvivut; Annaleise Klein; Casey L. Doolette; Helen Hou; et al. (Critical Reviews in Environmental Science and Technology, 2022)

Gene Expression Analysis of Laser-Captured Purkinje Cells in the Essential Tremor Cerebellum - Regina T. Martuscello; Karthigayini Sivaprakasam; Whitney Hartstone; Sheng-Han Kuo; Genevieve Konopka; Elan D. Louis; Phyllis L. Faust (The Cerebellum, 2022)

Patient Perspectives on the Risk-Based NLST Outcomes Tool for Lung Cancer Screening - Megan C. Roberts; Elizabeth L. Seaman; William M. P. Klein; Rebecca A. Ferrer; Paul K.J. Han; Hormuzd A. Katki; Stephanie R. Land; Robert A. Liotta; Joel A. Nations; P. Gabriel Peterson (Journal of Cancer Education, 2022)

The proposed Anthropocene Epoch/Series is underpinned by an extensive array of mid‐20 th century stratigraphic event signals - Martin J. Head; Jan A. Zalasiewicz; Colin N. Waters; Simon D. Turner; Mark Williams; Anthony D. Barnosky; Will Steffen; Michael Wagreich; Peter K. Haff; Jaia Syvitski; Reinhold Leinfelder; Francine M. G. Mccarthy; et al. (Journal of Quaternary Science, 2022)
The extensive array of mid‐20 th century stratigraphic event signals associated with the ‘Great Acceleration’ enables precise and unambiguous recognition of the Anthropocene as an epoch/series within the Geological Time Scale. A mid‐20 th century inception is consistent with Earth System science analysis in which the Anthropocene term and concept arose, and would reflect the reality that our planet has sharply exited the range of natural variability characterizing the Holocene Epoch/Series, which the Anthropocene would therefore terminate. An alternative, recently proposed ‘geological event’ approach to the Anthropocene is primarily an interdisciplinary concept, encompassing historical and socio‐cultural processes and their global environmental impacts over a diachronous timeframe that extends back at least many millennia. Resembling more closely a geological episode than an event , it would decouple the Anthropocene from its chronostratigraphic delineation and association with an abrupt planetary perturbation; but separately defined and differently named it might be usefully complementary. We recommend a clear separation of epochs , events and episodes . An epoch is a formal subdivision of the Geological Time Scale, and its correlation may be assisted by one or more events ; an event is usually, and particularly in the Quaternary, a brief incident or perturbation with a sedimentary expression; and an episode is a longer, internally complex time interval that may include several events and even extend across several epochs.

Rapid changes in coastal ocean microbiomes uncoupled with shifts in environmental variables - Jessica L. Gronniger; Zhao Wang; Genevieve R. Brandt; Christopher S. Ward; Despina Tsementzi; Han Mu; Junyao Gu; Zackary I. Johnson; Konstantinos T. Konstantinidis; Dana E. Hunt (Environmental Microbiology, 2022)
Summary Disturbances, here defined as events that directly alter microbial community composition, are commonly studied in host‐associated and engineered systems. In spite of global change both altering environmental averages and increasing extreme events, there has been relatively little research into the causes, persistence and population‐level impacts of disturbance in the dynamic coastal ocean. Here, we utilize 3 years of observations from a coastal time series to identify disturbances based on the largest week‐over‐week changes in the microbiome (i.e. identifying disturbance as events that alter the community composition). In general, these microbiome disturbances were not clearly linked to specific environmental factors and responsive taxa largely differed, aside from SAR11, which generally declined. However, several disturbance metagenomes identified increased phage‐associated genes, suggesting that unexplained community shifts might be caused by increased mortality. Furthermore, a category 1 hurricane, the only event that would likely be classified a priori as an environmental disturbance, was not an outlier in microbiome composition, but did enhance a bloom in seasonally abundant phytoplankton. Thus, as extreme environmental changes intensify, assumptions of what constitutes a disturbance should be re‐examined in the context of ecological history and microbiome responses.

Pore development in terrestrial shale reservoirs: the Permian Lucaogou Formation, Junggar Basin, northwestern China - Y. Jin; J. Tian; C. Han; H. Liu; L. Dong; S. Dan (Australian Journal of Earth Sciences, 2022)

The S-Factor, a New Measure of Disease Severity in Spinocerebellar Ataxia: Findings and Implications - Louisa P. Selvadurai; Susan L. Perlman; George R. Wilmot; Sub H. Subramony; Christopher M. Gomez; Tetsuo Ashizawa; Henry L. Paulson; Chiadi U. Onyike; Liana S. Rosenthal; Haris I. Sair; Sheng-Han Kuo; Eva-Maria Ratai; et al. (The Cerebellum, 2022)

Factors associated with symptoms of poor mental health among women factory workers in China’s supply chain - K. K. Sznajder; S. D. Harlow; J. Wang; L. Tso; Y. Ashagre; C. Han (International Archives of Occupational and Environmental Health, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Species and Functional Dynamics of the Demersal Fish Community and Responses to Disturbances in the Pearl River Estuary - Zeyu Zeng; William W. L. Cheung; Han Lai; Huadong Yi; Sheng Bi; Haiyang Li; Xiaoli Chen; Yuqin Su; Xuange Liu; Qiuxian Chen; Zhilun Zhang; Xuchong Wei; et al. (Frontiers in Marine Science, 2022)
Fishery resources are threatened by environmental changes and anthropogenic pressures, particularly in coastal ecosystems. It is crucial to understand the changes of fish communities and their responses to environmental changes and human disturbances to formulate rational fisheries and ecosystem-based management. The Pearl River Estuary (PRE) is a typical sub-tropic coastal ecosystem located in the center of the Guangdong-Hong Kong-Macao Greater Bay Area in the northern South China Sea. The demersal fish in the PRE is traditionally targeted as commercial fishing and severely impacted by overexploitation and hypoxia in the last few decades. In this study, we analyze the fish survey data during the period of 2020~2021 using multivariate statistics to investigate the impacts of human disturbances on the species and functional dynamics of the demersal fish community in the PRE. The results reveal that dissolved oxygen and temperature have significant correlations with the functional traits of the demersal fish community. The impacts of hypoxia on the demersal fish vary with species and locations. We found that the mean functional redundancy of the demersal fish community in the PRE was high across three surveys, but the functional diversity was low in this region. The abundance and richness of the demersal fish community increased during the summer fishing moratorium in the South China Sea in 2021, but the functional diversity did not increase significantly. We conclude that the high functional redundancy in the PRE might not be sufficient to buffer against environmental disturbances because of its low functional diversity. Our study highlights the complicated interactions between the demersal fish community and disturbances in the PRE. Understanding the traits structure and functional diversity of the fish community can help elucidate the factors determining the dynamic responses of the fish community to disturbances.

A New Berberine Preparation Protects Pancreatic Islet Cells from Apoptosis Mediated by Inhibition of Phospholipase A2/p38 MAPK Pathway - X. J. Bi; Y. Q. Lv; X. H. Yang; Y. Ge; H. Han; J. S. Feng; M. Zhang; L. Chen; M. Z. Xu; F. Y. Guan (Bulletin of Experimental Biology and Medicine, 2022)

Gut microbiota composition does not associate with toxoplasma infection in rats - Patrick L. Taggart; Craig Liddicoat; Wen Han Tong; Martin F. Breed; Philip Weinstein; David Wheeler; Ajai Vyas (Molecular Ecology, 2022)
Toxoplasma infection in intermediate host species closely associates with inflammation. This association has led to suggestions that the behavioural changes associated with infection may be indirectly driven by the resulting sustained inflammation rather than a direct behavioural manipulation by the parasite. If this is correct, sustained inflammation in chronically infected rodents should present as widespread differences in the gastrointestinal microbiota due to the dependency between the composition of these microbiota and sustained inflammation. We conducted a randomized controlled experiment in rats that were assigned to a Toxoplasma ‐treatment, placebo‐treatment or negative control group. We euthanised rats during the chronic phase of infection, collected their caecal stool samples and sequenced the V3‐V4 region of the 16S rRNA gene to characterize the bacterial community in these samples. Toxoplasma infection did not induce widespread differences in the bacterial community composition of the gastrointestinal tract of rats. Rather, we found sex differences in the bacterial community composition of rats. We conclude that it is unlikely that sustained inflammation is the mechanism driving the highly specific behavioural changes observed in Toxoplasma ‐positive rats.

Cerebellar Oscillations in Familial and Sporadic Essential Tremor - Shi-Bing Wong; Yi-Mei Wang; Chih-Chun Lin; Scott Kun Geng; Nora Vanegas-Arroyave; Seth L. Pullman; Sheng-Han Kuo; Ming-Kai Pan (The Cerebellum, 2022)

FDA Approaches in Monitoring Drug Quality, Forces Impacting the Drug Quality, and Recent Alternative Strategies to Assess Quality in the US Drug Supply - Philip J. Almeter; James T. Isaacs; Aaron N. Hunter; Bradley S. Henderson; Thomas Platt; Billie J. Mitchell; David Do; Alyssa B. Brainard; Joshua E. Brown; Rachael M. Stone; Bao-Han Nguyen; Matthew F. Warren; et al. (Journal of Pharmaceutical Innovation, 2022)

Globally, tree fecundity exceeds productivity gradients - Valentin Journé; Robert Andrus; Marie‐Claire Aravena; Davide Ascoli; Roberta Berretti; Daniel Berveiller; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Rafael Calama; Jesús Julio Camarero; et al. (Ecology Letters, 2022)
Lack of tree fecundity data across climatic gradients precludes the analysis of how seed supply contributes to global variation in forest regeneration and biotic interactions responsible for biodiversity. A global synthesis of raw seedproduction data shows a 250‐fold increase in seed abundance from cold‐dry to warm‐wet climates, driven primarily by a 100‐fold increase in seed production for a given tree size. The modest (threefold) increase in forest productivity across the same climate gradient cannot explain the magnitudes of these trends. The increase in seeds per tree can arise from adaptive evolution driven by intense species interactions or from the direct effects of a warm, moist climate on tree fecundity. Either way, the massive differences in seed supply ramify through food webs potentially explaining a disproportionate role for species interactions in the wet tropics.

Trametes suaveolens-derived biochar loaded on nanoscale zero-valent iron particles for the adsorption and reduction of Cr(VI) - W.-D. Wang; H.-T. Ma; W. Lin; P. Sun; L.-K. Zhang; J.-H. Han (International Journal of Environmental Science and Technology, 2022)

Identification and Verification of the Ability of Cdk5 to Phosphorylate Deubiquitinating Enzyme BRCC3 In Vitro - C. H. Zhang; K. Qin; S. L. Tian; Y. Han; S. Y. Xu; X. Y. Shao (Bulletin of Experimental Biology and Medicine, 2022)

Dopamine D1 receptors mediate methamphetamine-induced dopaminergic damage: involvement of autophagy regulation via the AMPK/FOXO3A pathway - Tao He; Chaojun Han; Chun Liu; Jiaojiao Chen; Huicui Yang; Longtai Zheng; John L. Waddington; Xuechu Zhen (Psychopharmacology, 2022)

A Full Evaporation Static Headspace Gas Chromatography Method with Nitrogen Phosphorous Detection for Ultrasensitive Analysis of Semi-volatile Nitrosamines in Pharmaceutical Products - Jinjian Zheng; Christine L. Kirkpatrick; Daniel Lee; Xinxin Han; Ana I. Martinez; Kimberly Gallagher; Rebecca K. Evans; Sanjay V. Mudur; Xihui Liang; Jennifer Drake; Leah A. Buhler; Mark D. Mowery (The AAPS Journal, 2022)
The recent detection of potent carcinogenic nitrosamine impurities in several human medicines has triggered product recalls and interrupted the supply of critical medications for hundreds of millions of patients, illuminating the need for increased testing of nitrosamines in pharmaceutical products. However, the development of analytical methods for nitrosamine detection is challenging due to high sensitivity requirements, complex matrices, and the large number and variety of samples requiring testing. Herein, we report an analytical method for the analysis of a common nitrosamine, N-nitrosodimethylamine (NDMA), in pharmaceutical products using full evaporation static headspace gas chromatography with nitrogen phosphorous detection (FE-SHSGC-NPD). This method is sensitive, specific, accurate, and precise and has the potential to serve as a universal method for testing all semi-volatile nitrosamines across different drug products. Through elimination of the detrimental headspace-liquid partition, a quantitation limit of 0.25 ppb is achieved for NDMA, a significant improvement upon traditional LC-MS methods. The extraction of nitrosamines directly from solid sample not only simplifies the sample preparation procedure but also enables the method to be used for different products as is or with minor modifications, as demonstrated by the analysis of NDMA in 10+ pharmaceutical products. The in situ nitrosation that is commonly observed in GC methods for nitrosamine analysis was completely inhibited by the addition of a small volume solvent containing pyrogallol, phosphoric acid, and isopropanol. Employing simple procedures and low-cost instrumentation, this method can be implemented in any analytical laboratory for routine nitrosamine analysis, ensuring patient safety and uninterrupted supply of critical medications.

Tracing historical changes, degradation, and original sources of airborne polycyclic aromatic hydrocarbons (PAHs) in Jilin Province, China, by Abies holophylla and Pinus tabuliformis needle leaves - Zhao Wang; Xiangzi Jin; Han Yeong Kaw; Zakia Fatima; Maurizio Quinto; John L. Zhou; Dongri Jin; Miao He; Donghao Li (Environmental Science and Pollution Research, 2022)

Essential Tremor versus “ET-plus”: A Detailed Postmortem Study of Cerebellar Pathology - John T. Gionco; Whitney G. Hartstone; Regina T. Martuscello; Sheng-Han Kuo; Phyllis L. Faust; Elan D. Louis (The Cerebellum, 2021)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

The second wave of earthworm invasions in North America: biology, environmental impacts, management and control of invasive jumping worms - Chih-Han Chang; Marie L. C. Bartz; George Brown; Mac A. Callaham; Erin K. Cameron; Andrea Dávalos; Annise Dobson; Josef H. Görres; Bradley M. Herrick; Hiroshi Ikeda; Samuel W. James; Marie R. Johnston; et al. (Biological Invasions, 2021)

Plant traits and soil fertility mediate productivity losses under extreme drought in C 3 grasslands - Wentao Luo; Robert J. Griffin‐Nolan; Wang Ma; Bo Liu; Xiaoan Zuo; Chong Xu; Qiang Yu; Yahuang Luo; Pierre Mariotte; Melinda D. Smith; Scott L. Collins; Alan K. Knapp; et al. (Ecology, 2021)
Extreme drought decreases aboveground net primary production (ANPP) in most grasslands, but the magnitude of ANPP reductions varies especially in C 3 ‐dominated grasslands. Because the mechanisms underlying such differential ecosystem responses to drought are not well resolved, we experimentally imposed an extreme 4‐yr drought (2015–2018) in two C 3 grasslands that differed in aridity. These sites had similar annual precipitation and dominant grass species ( Leymus chinensis ) but different annual temperatures and thus water availability. Drought treatments differentially affected these two semiarid grasslands, with ANPP of the drier site reduced more than at the wetter site. Structural equation modeling revealed that community‐weighted means for some traits modified relationships between soil moisture and ANPP, often due to intraspecific variation. Specifically, drought reduced community mean plant height at both sites, resulting in a reduction in ANPP beyond that attributable to reduced soil moisture alone. Higher community mean leaf carbon content enhanced the negative effects of drought on ANPP at the drier site, and ANPP–soil‐moisture relationships were influenced by soil C:N ratio at the wetter site. Importantly, neither species richness nor functional dispersion were significantly correlated with ANPP at either site. Overall, as expected, soil moisture was a dominant, direct driver of ANPP response to drought, but differential sensitivity to drought in these two grasslands was also related to soil fertility and plant traits.

Eutrophication and Hypoxia in Tropical Negombo Lagoon, Sri Lanka - Hsueh-Han Hsieh; Ming-Hsiu Chuang; Yung-Yen Shih; W. Sanjaya Weerakkody; Wei-Jen Huang; Chin-Chang Hung; François L. L. Muller; R. R. M. K. P. Ranatunga; D. S. Wijethunga (Frontiers in Marine Science, 2021)
Hypoxic events are becoming frequent in some estuaries and coastal waters due to over-enrichment of anthropogenic nutrients, organic matter, and/or due to restricted water circulation. The coastal lagoons and estuaries of Sri Lanka are facing high population pressure and lacking sufficient infrastructure. Coastal lagoons may receive high anthropogenic inputs of natural or untreated nitrogen and phosphorus wastes, and consequently result in hypoxic conditions while sluggish circulation occurred. In this study, we examined the spatiotemporal variability of eutrophication and hypoxia in the Negombo Lagoon, one of the most productive and sensitive coastal ecosystems in Sri Lanka. Based on seasonal measurements of dissolved oxygen, nutrients, chlorophyll- a (Chl- a ), particulate and dissolved organic carbon (POC and DOC), we concluded that eutrophication and hypoxia occurred in both the dry and wet seasons. The main contributing factors were high seawater temperature and poor water circulation in the dry season and high nutrient loading combined with elevated POC and DOC inputs in the wet season.

Uranium Adsorption on Three Nanohydroxyapatites Under Various Biogeochemical Conditions - Precious Cooper; Jing Nie; Steven L. Larson; John H. Ballard; Heather M. Knotek-Smith; Ahmet Celik; Shaloam Dasari; Xianchun Zhu; Fengxiang X. Han (Water, Air, & Soil Pollution, 2021)

Synthesis of a novel ZnFe2O4/porous biochar magnetic composite for Th(IV) adsorption in aqueous solutions - W. D. Wang; Y. X. Cui; L. K. Zhang; Y. M. Li; P. Sun; J. H. Han (International Journal of Environmental Science and Technology, 2021)

Statistical upscaling of ecosystem CO 2 fluxes across the terrestrial tundra and boreal domain: Regional patterns and uncertainties - Anna‐Maria Virkkala; Juha Aalto; Brendan M. Rogers; Torbern Tagesson; Claire C. Treat; Susan M. Natali; Jennifer D. Watts; Stefano Potter; Aleksi Lehtonen; Marguerite Mauritz; Edward A. G. Schuur; John Kochendorfer; et al. (Global Change Biology, 2021)
The regional variability in tundra and boreal carbon dioxide (CO 2 ) fluxes can be high, complicating efforts to quantify sink‐source patterns across the entire region. Statistical models are increasingly used to predict (i.e., upscale) CO 2 fluxes across large spatial domains, but the reliability of different modeling techniques, each with different specifications and assumptions, has not been assessed in detail. Here, we compile eddy covariance and chamber measurements of annual and growing season CO 2 fluxes of gross primary productivity (GPP), ecosystem respiration (ER), and net ecosystem exchange (NEE) during 1990–2015 from 148 terrestrial high‐latitude (i.e., tundra and boreal) sites to analyze the spatial patterns and drivers of CO 2 fluxes and test the accuracy and uncertainty of different statistical models. CO 2 fluxes were upscaled at relatively high spatial resolution (1 km 2 ) across the high‐latitude region using five commonly used statistical models and their ensemble, that is, the median of all five models, using climatic, vegetation, and soil predictors. We found the performance of machine learning and ensemble predictions to outperform traditional regression methods. We also found the predictive performance of NEE‐focused models to be low, relative to models predicting GPP and ER. Our data compilation and ensemble predictions showed that CO 2 sink strength was larger in the boreal biome (observed and predicted average annual NEE −46 and −29 g C m −2 yr −1 , respectively) compared to tundra (average annual NEE +10 and −2 g C m −2 yr −1 ). This pattern was associated with large spatial variability, reflecting local heterogeneity in soil organic carbon stocks, climate, and vegetation productivity. The terrestrial ecosystem CO 2 budget, estimated using the annual NEE ensemble prediction, suggests the high‐latitude region was on average an annual CO 2 sink during 1990–2015, although uncertainty remains high.

Use of Moringa oleifera seeds powder as bio-coagulants for the surface water treatment - H. T. Nhut; N. T. Q. Hung; B. Q. Lap; L. T. N. Han; T. Q. Tri; N. H. K. Bang; N. T. Hiep; N. M. Ky (International Journal of Environmental Science and Technology, 2021)

Self-reported experiences of discrimination in older black adults are associated with insula functional connectivity - S. Duke Han; Melissa Lamar; Debra Fleischman; Namhee Kim; David A. Bennett; Tené T. Lewis; Konstantinos Arfanakis; Lisa L. Barnes (Brain Imaging and Behavior, 2021)

Correction to: Identification and molecular characterization of tea‑oil camellia‑associated totivirus 1 - Z.-Y. Zhang; H. Huang; X. X. Han; R. Li; L.-P. Wu; L. Wu (Archives of Virology, 2021)

Identification and molecular characterization of tea-oil camellia-associated totivirus 1 - Z.-Y. Zhang; H. Huang; X. X. Han; R. Li; L.-P. Wu; L. Wu (Archives of Virology, 2021)

Microbially Induced Carbonate Precipitation Techniques for the Remediation of Heavy Metal and Trace Element–Polluted Soils and Water - Xue Chen; Dan Zhang; Steven L. Larson; John H. Ballard; Heather M. Knotek-Smith; Jing Nie; Nan Hu; Dexin Ding; Fengxiang X. Han (Water, Air, & Soil Pollution, 2021)

Genetic diversity and population genetic structure in native Ethiopian donkeys (Equus asinus) inferred from equine microsatellite markers - E. Kefena; S. Rosenbom; A. Beja-Pereira; M. Yusuf Kurtu; J. L. Han; T. Dessie (Tropical Animal Health and Production, 2021)

Editorial: Designing a Protocol Adopting an Artificial Intelligence (AI)–Driven Approach for Early Diagnosis of Late-Onset Alzheimer’s Disease - Victor O. K. Li; Jacqueline C. K. Lam; Yang Han; Lawrence Y. L. Cheung; Jocelyn Downey; Tushar Kaistha; Illana Gozes (Journal of Molecular Neuroscience, 2021)

Potential Micro-Plastics Dispersal and Accumulation in the North Sea, With Application to the MSC Zoe Incident - Johan van der Molen; Sonja M. van Leeuwen; Laura L. Govers; Tjisse van der Heide; Han Olff (Frontiers in Marine Science, 2021)
The fate and effects of microplastics in the marine environment are an increasingly important area of research, policy and legislation. To manage and reduce microplastics in the seas and oceans, and to help understand causes and effects, we need improved understanding of transport patterns, transit times and accumulation areas. In this paper, we use a particle tracking model to investigate the differences in dispersal and accumulation of microplastics with different properties (floating and sinking) in the North Sea. In these simulations, particles were released with a uniform horizontal distribution, and also from rivers at rates proportional to the river runoff. The results showed that floating particles can accumulate temporarily on salinity fronts and in gyres, and are deposited predominantly on west-facing beaches. Sinking particles moved more slowly and less far, accumulated in deeper areas associated with fine sediments, and were deposited more on west- and north-facing beaches. The model was also applied to the MSC Zoe incident of 1 January 2019, in which 342 containers were lost north of the Dutch Wadden islands in the southern North Sea, tracking two types of microplastics with similar properties (∼5mm floating HDPE pellets and ∼0.6mm sinking PS grains) to identify release locations and potential accumulation areas. We used field observations collected by a citizen science initiative ( waddenplastic.nl ) to constrain the model results. For these simulations, particles were released along the ship’s trajectory and at locations on the trajectory where debris was found. The simulations of the MSC Zoe incident showed that over 90% of floating (∼5mm) HDPE pellets beached within 3–7 weeks, and predominantly on the more eastern Dutch Wadden Islands in agreement with the field observations, and that most of the sinking (∼0.6mm) PS grains were still at sea after 6 weeks, and a large proportion may have been deposited on German shores. The work is relevant to Descriptor 10 (Marine Litter) of the EU Marine Strategy Framework Directive.

Untapped Knowledge about Water Reuse: the Roles of Direct and Indirect Educational Messaging - Jesse L. Barnes; Anjala S. Krishen; Han-fen Hu (Water Resources Management, 2021)

Can precrops uplift subsoil nutrients to topsoil? - Eusun Han; Feng Li; Ute Perkons; Paul Martin Küpper; Sara L. Bauke; Miriam Athmann; Kristian Thorup-Kristensen; Timo Kautz; Ulrich Köpke (Plant and Soil, 2021)

Warming exacerbates the impact of nutrient enrichment on microbial functional potentials important to the nutrient cycling in shallow lake mesocosms - Lijuan Ren; Yuanyuan Liu; Torben L. Lauridsen; Martin Søndergaard; Boping Han; Jianjun Wang; Erik Jeppesen; Jizhong Zhou; Qinglong L. Wu (Limnology and Oceanography, 2021)
Shallow lakes, the most numerous waterbodies on Earth, are susceptible to climate warming and nutrient enrichment whose effects on the microbial functional potentials are not yet fully understood, however. Here, we applied a microarray‐based technology termed GeoChip 5.0 to investigate microbial functional genes at the beginning of April in shallow lake ecosystems simulated in mesocosms that have been undergoing nutrient enrichment and warming for 9 yr. Our results showed that warming exacerbated the impact of nutrient enrichment on microbial metabolic potentials and significantly elevated the microbial autotrophy potentials, carbon degradation potentials (e.g., starch, hemicellulose, cellulose, and chitin), and polyphosphate mobilization potentials. We also observed that warming enhanced the impacts of nutrient enrichment on microbial functional gene structure. The combination of warming and nutrient enrichment increased the deterministic effect from phytoplankton, causing higher interlinking of microbial functional genes involved in the carbon, nitrogen, phosphorus, and sulfur cycling in correlation‐based networks. Overall, we propose that the joint effect of warming and nutrient enrichment promoted the autotrophic carbon supply and the heterotrophic carbon demand and changed the carbon fluxes in the experimental mesocosms.

Application of two-level design method on subway tunnel crossing active fault: a case study on Urumqi subway tunnel intersected by reverse fault dislocation - S. An; L. J. Tao; X. C. Han; Y. Zhang (Bulletin of Engineering Geology and the Environment, 2021)

Conservation Implications of Sabellaria spinulosa Reef Patches in a Dynamic Sandy-Bottom Environment - Karin J. van der Reijden; Leo Koop; Sebastiaan Mestdagh; Mirjam Snellen; Peter M. J. Herman; Han Olff; Laura L. Govers (Frontiers in Marine Science, 2021)
Biogenic reefs form biodiversity hotspots and are key components of marine ecosystems, making them priority habitats for nature conservation. However, the conservation status of biogenic reefs generally depends on their size and stability. Dynamic, patchy reefs may therefore be excluded from protection. Here, we studied epibenthos and epifauna density, richness, and community composition of patchy, dynamic Sabellaria spinulosa (ross worm) reefs in the North Sea. This study was conducted by comparing boxcore (endobenthos) and video transect (epifauna) data from two research campaigns in 2017 and 2019 to the Brown Bank area on the Dutch Continental Shelf, where S. spinulosa reefs were first discovered in 2017. The Brown Bank area is characterized by dynamic, migratory bedforms at multiple scales which potentially affect biogenic reef stability. We showed that S. spinulosa habitats had a patchy distribution and alternated with habitats comprised of plain sand. Average S. spinulosa habitat patch size was 5.57 ± 0.99 m and 3.94 ± 0.22 m in 2017 and 2019, respectively (mean ± SE), which especially in 2019 closely resembled the small-scale megaripple bedforms. Contrary to the endobenthos communities that were unaffected by S. spinulosa , epifauna density and species richness were at least two times higher in S. spinulosa habitats compared to sandy habitats, resulting in different community compositions between the two habitat types. We showed that S. spinulosa persisted in the area for almost 2 years. Although the stability of individual patches remained unclear, we demonstrated that even patchy biogenic reefs may promote density and local biodiversity of mobile, epibenthic species, very likely as a result of increased habitat heterogeneity provided by reef habitat patches. This indicates that patchy biogenic reefs that occur in dynamic environments may also have high ecological value and their conservation status should be (re)considered to ensure their protection.

Coordinating Global Multi-Site Studies of Military-Relevant Traumatic Brain Injury: Opportunities, Challenges, and Harmonization Guidelines - David F Tate; Emily L Dennis; John T Adams; Maheen M Adamson; Heather G Belanger; Erin D Bigler; Heather C Bouchard; Alexandra L Clark; Lisa M Delano-Wood; Seth G Disner; Blessen C Eapen; Carol E Franz; et al. (Brain Imaging and Behavior, 2021)

NABat: A top-down, bottom-up solution to collaborative continental-scale monitoring - Brian E. Reichert; Mylea Bayless; Tina L. Cheng; Jeremy T. H. Coleman; Charles M. Francis; Winifred F. Frick; Benjamin S. Gotthold; Kathryn M. Irvine; Cori Lausen; Han Li; Susan C. Loeb; Jonathan D. Reichard; et al. (Ambio, 2021)
Collaborative monitoring over broad scales and levels of ecological organization can inform conservation efforts necessary to address the contemporary biodiversity crisis. An important challenge to collaborative monitoring is motivating local engagement with enough buy-in from stakeholders while providing adequate top-down direction for scientific rigor, quality control, and coordination. Collaborative monitoring must reconcile this inherent tension between top-down control and bottom-up engagement. Highly mobile and cryptic taxa, such as bats, present a particularly acute challenge. Given their scale of movement, complex life histories, and rapidly expanding threats, understanding population trends of bats requires coordinated broad-scale collaborative monitoring. The North American Bat Monitoring Program (NABat) reconciles top-down, bottom-up tension with a hierarchical master sample survey design, integrated data analysis, dynamic data curation, regional monitoring hubs, and knowledge delivery through web-based infrastructure. NABat supports collaborative monitoring across spatial and organizational scales and the full annual lifecycle of bats.

EmhR is an indole‐sensing transcriptional regulator responsible for the indole‐induced antibiotic tolerance in Pseudomonas fluorescens - Jian‐Ting Han; Di‐Yin Li; Meng‐Yuan Zhang; Xiao‐Quan Yu; Xiang‐Xue Jia; Hang Xu; Xu Yan; Wen‐Juan Jia; Shaomin Niu; Megan L. Kempher; Xuanyu Tao; Yong‐Xing He (Environmental Microbiology, 2021)
Summary Indole is well known as an interspecies signalling molecule to modulate bacterial physiology; however, it is not clear how the indole signal is perceived and responded to by plant growth promoting rhizobacteria (PGPR) in the rhizosphere. Here, we demonstrated that indole enhanced the antibiotic tolerance of Pseudomonas fluorescens 2P24, a PGPR well known for its biocontrol capacity. Proteomic analysis revealed that indole influenced the expression of multiple genes including the emhABC operon encoding a major multidrug efflux pump. The expression of emhABC was regulated by a TetR‐family transcription factor EmhR, which was demonstrated to be an indole‐responsive regulator. Molecular dynamics simulation showed that indole allosterically affected the distance between the two DNA‐recognizing helices within the EmhR dimer, leading to diminished EmhR–DNA interaction. It was further revealed the EmhR ortholog in Pseudomonas syringae was also responsible for indole‐induced antibiotic tolerance, suggesting this EmhR‐dependent, indole‐induced antibiotic tolerance is likely to be conserved among Pseudomonas species. Taken together, our results elucidated the molecular mechanism of indole‐induced antibiotic tolerance in Pseudomonas species and had important implications on how rhizobacteria sense and respond to indole in the rhizosphere.

Industrial Fishing Near West African Marine Protected Areas and Its Potential Effects on Mobile Marine Predators - Guido Leurs; Karin J. van der Reijden; Sidi Yahya Cheikhna Lemrabott; Iça Barry; Diosnes Manuel Nonque; Han Olff; Samuel Ledo Pontes; Aissa Regalla; Laura L. Govers (Frontiers in Marine Science, 2021)
Marine Protected Areas (MPAs) are increasingly implemented to facilitate the conservation of marine biodiversity and key habitats. However, these areas are often less effective to conserve mobile marine species like elasmobranchs (i.e., sharks and rays). Industrial fishing near MPA borders possibly impacts vulnerable species utilizing these protected areas. Hence, we aimed to study spatiotemporal patterns of industrial fisheries near MPAs, in relation to the bycatch of elasmobranchs. Specifically, we analyzed the spatiotemporal fishing effort within the West African region, mapped fishing effort in the direct vicinity of the Parc National du Banc d’Arguin (PNBA, Mauritania) and the Bijagós Archipelago (BA, Guinea Bissau), and compared the seasonal overlap between elasmobranch bycatch and fishing effort near these MPAs. We combined Automatic Identification System (AIS) data and local fisheries observer data, and determined fishing effort for each gear type and compared this with bycatch of elasmobranchs. We found that industrial fishing effort was dominated by trawling, drifting longlines, and fixed gear types. Although no industrial fishing was observed within both MPAs, 72 and 78% of the buffer zones surrounding the MPAs were fished for the Banc d’Arguin and Bijagós, respectively. Within the Banc d’Arguin buffer zone, trawling and drifting longlines dominated, with longlines mainly being deployed in fall. In the Bijagós buffer zone, trawling and fixed gears were most prevalent. Fisheries observer data for Mauritania showed that elasmobranch catches increased during the most recent sampling years (2016–2018). Elasmobranch catches within the waters of Guinea Bissau peaked in 2016 and decreased in the following two years. Seasonal patterns in elasmobranch bycatch within the waters of both countries are likely caused by increased catches of migratory species. Catches of rays peaked in May and June for Mauritania, and in October for Guinea Bissau. Shark catches were highest in February and July in Mauritanian waters, and in May and October in the waters of Guinea Bissau. Our study indicates that industrial fisheries near the border of ecologically important MPAs may have potentially major implications for ecosystem functioning by the removal of (migratory) predatory species.

Docosahexaenoic Acid (DHA) Supplementation Alters Phospholipid Species and Lipid Peroxidation Products in Adult Mouse Brain, Heart, and Plasma - Grace Y. Sun; Michael K. Appenteng; Runting Li; Taeseon Woo; Bo Yang; Chao Qin; Meixia Pan; Magdalena Cieślik; Jiankun Cui; Kevin L. Fritsche; Zezong Gu; Matthew Will; et al. (NeuroMolecular Medicine, 2021)

Gga-miR-181a modulates ANP32A expression and inhibits MDCC-MSB-1 cell - X. Li; C. Zhao; B. Han; L. Qu; C. Liu; N. Yang; L. Lian (In Vitro Cellular & Developmental Biology - Animal, 2021)

Slingshot spiders build tensed, underdamped webs for ultrafast launches and speedy halts - Elio J. Challita; Symone L. M. Alexander; Sarah I. Han; Todd A. Blackledge; Jonathan A. Coddington; Sunghwan Jung; M. Saad Bhamla (Journal of Comparative Physiology A, 2021)

A chemical structure-based approach for estimating the added levels of flavourings to foods for the purpose of assessing consumer intake - Maria Bastaki; Michel Aubanel; Heidi Bialk; Christopher Choi; Jan Demyttenaere; Malick Maodo Diop; Sylvain Etter; Xing Han; Mihoko Koyanagi; Gerhard Krammer; Jürgen Schnabel; Cody L. Wilson; et al. (Food Additives & Contaminants: Part A, 2021)

Plasma Isolation in a Syringe by Conformal Integration of Inertial Microfluidics - Jung Y. Han; Don L. DeVoe (Annals of Biomedical Engineering, 2021)

Dissociable dopaminergic and pavlovian influences in goal-trackers and sign-trackers on a model of compulsive checking in OCD - D. M. Eagle; C. Schepisi; S. Chugh; S. Desai; S. Y. S. Han; T. Huang; J. J. Lee; C. Sobala; W. Ye; A. L. Milton; T. W. Robbins (Psychopharmacology, 2020)
Rationale Checking is a functional behaviour that provides information to guide behaviour. However, in obsessive-compulsive disorder (OCD), checking may escalate to dysfunctional levels. The processes underpinning the transition from functional to dysfunctional checking are unclear but may be associated with individual differences that support the development of maladaptive behaviour. We examined one such predisposition, sign-tracking to a pavlovian conditioned stimulus, which we previously found associated with dysfunctional checking. How sign-tracking interacts with another treatment with emerging translational validity for OCD-like checking, chronic administration of the dopamine D 2 receptor agonist quinpirole, is unknown. Objectives We tested how functional and dysfunctional checking in the rat observing response task (ORT) was affected by chronic quinpirole administration in non-autoshaped controls and autoshaped animals classified as sign-trackers or goal-trackers. Methods Sign-trackers or goal-trackers were trained on the ORT before the effects of chronic quinpirole administration on checking were assessed. Subsequently, the effects on checking of different behavioural challenges, including reward omission and the use of unpredictable reinforcement schedules, were tested. Results Prior autoshaping increased checking. Sign-trackers and goal-trackers responded differently to quinpirole sensitization, reward omission and reinforcement uncertainty. Sign-trackers showed greater elevations in dysfunctional checking, particularly during uncertainty. By contrast, goal-trackers predominantly increased functional checking responses, possibly in response to reduced discrimination accuracy in the absence of cues signalling which lever was currently active. Conclusions The results are discussed in terms of how pavlovian associations influence behaviour that becomes compulsive in OCD and how this may be dependent on striatal dopamine D 2 receptors.

Downregulation of Adhesion Molecule CHL1 in B Cells but Not T Cells of Patients with Major Depression and in the Brain of Mice with Chronic Stress - C. R. Yang; L. Ning; F. H. Zhou; Q. Sun; H. P. Meng; Z. Han; Y. Liu; W. Huang; S. Liu; X. H. Li; B. Zheng; Dong Ming; et al. (Neurotoxicity Research, 2020)

DNA Polyplexes of a Phosphorylcholine-Based Zwitterionic Polymer for Gene Delivery - Kandarp M. Dave; Linjiang Han; Meredith A. Jackson; Lindsay Kadlecik; Craig L. Duvall; Devika S Manickam (Pharmaceutical Research, 2020)

The effect of enrichment media on the stimulation of native ureolytic bacteria in calcareous sand - Y.-J. Wang; X.-L. Han; N.-J. Jiang; J. Wang; J. Feng (International Journal of Environmental Science and Technology, 2020)

Stem Cell Mechanosensation on Gelatin Methacryloyl (GelMA) Stiffness Gradient Hydrogels - Claire Kim; Jennifer L. Young; Andrew W. Holle; Kwanghee Jeong; Luke G. Major; Ji Hoon Jeong; Zachary M. Aman; Dong-Wook Han; Yongsung Hwang; Joachim P. Spatz; Yu Suk Choi (Annals of Biomedical Engineering, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Current Opinions and Consensus for Studying Tremor in Animal Models - Sheng-Han Kuo; Elan D. Louis; Phyllis L. Faust; Adrian Handforth; Su-youne Chang; Billur Avlar; Eric J. Lang; Ming-Kai Pan; Lauren N. Miterko; Amanda M. Brown; Roy V. Sillitoe; Collin J. Anderson; et al. (The Cerebellum, 2019)

Involvement of Interferon Regulatory Factor 7 in Nicotine’s Suppression of Antiviral Immune Responses - Haijun Han; Wenfei Huang; Wenjuan Du; Quan Shen; Zhongli Yang; Ming D. Li; Sulie L. Chang (Journal of Neuroimmune Pharmacology, 2019)

The protective effects of echinochrome A structural analogs against oxidative stress and doxorubicin in AC16 cardiomyocytes - Chang Shin Yoon; Hyoung Kyu Kim; Natalia P. Mishchenko; Elena A. Vasileva; Sergey A. Fedoreyev; Olga P. Shestak; Nadezhda N. Balaneva; Vyacheslav L. Novikov; Valentin A. Stonik; Jin Han (Molecular & Cellular Toxicology, 2019)

An improved supported vector regression algorithm with application to predict aftershocks - Maofa Wang; J. Shen; Z. A. Pan; D. L. Han (Journal of Seismology, 2019)

Rapid Increases in Bat Activity and Diversity after Wetland Construction in an Urban Ecosystem - Kevin A. Parker; Brian T. Springall; Reuben A. Garshong; Ashley N. Malachi; Lauren E. Dorn; Alicia Costa-Terryll; Rachael A. Mathis; Alayna N. Lewis; Cassandra L. MacCheyne; Tronjay T. Davis; Alexis D. Rice; Nyla Y. Varh; et al. (Wetlands, 2019)

Increased Diagnostic Yield of Spastic Paraplegia with or Without Cerebellar Ataxia Through Whole-Genome Sequencing - Aryun Kim; Kishore R. Kumar; Ryan L. Davis; Amali C. Mallawaarachchi; Velimir Gayevskiy; Andre E. Minoche; Zachary Walls; Han-Joon Kim; Mihee Jang; Mark J. Cowley; Ji-Hyun Choi; Chaewon Shin; et al. (The Cerebellum, 2019)

Seagrass Sensitivity to Collapse Along a Hydrodynamic Gradient: Evidence from a Pristine Subtropical Intertidal Ecosystem - El-Hacen M. El-Hacen; Tjeerd J. Bouma; Laura L. Govers; Theunis Piersma; Han Olff (Ecosystems, 2019)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Towards Comprehensive Observing and Modeling Systems for Monitoring and Predicting Regional to Coastal Sea Level - Rui M. Ponte; Mark Carson; Mauro Cirano; Catia M. Domingues; Svetlana Jevrejeva; Marta Marcos; Gary Mitchum; R. S. W. van de Wal; Philip L. Woodworth; Michaël Ablain; Fabrice Ardhuin; Valérie Ballu; et al. (Frontiers in Marine Science, 2019)

Requirements for a Coastal Hazards Observing System - Jérôme Benveniste; Anny Cazenave; Stefano Vignudelli; Luciana Fenoglio-Marc; Rashmi Shah; Rafael Almar; Ole Andersen; Florence Birol; Pascal Bonnefond; Jérôme Bouffard; Francisco Calafat; Estel Cardellach; et al. (Frontiers in Marine Science, 2019)

A Sustained Ocean Observing System in the Indian Ocean for Climate Related Scientific Knowledge and Societal Needs - J. C. Hermes; Y. Masumoto; L. M. Beal; M. K. Roxy; J. Vialard; M. Andres; H. Annamalai; S. Behera; N. D’Adamo; T. Doi; M. Feng; W. Han; et al. (Frontiers in Marine Science, 2019)

The antitoxin MqsA homologue in Pseudomonas fluorescens 2P24 has a rewired regulatory circuit through evolution - Yong Wang; Si‐Ping Zhang; Meng‐Yuan Zhang; Megan L. Kempher; Ding‐Ding Guo; Jian‐Ting Han; Xuanyu Tao; Yi Wu; Li‐Qun Zhang; Yong‐Xing He (Environmental Microbiology, 2019)
Summary The mqsRA operon encodes a toxin–antitoxin pair that was characterized to participate in biofilm and persister cell formation in Escherichia coli . Notably, the antitoxin MqsA possesses a C‐terminal DNA‐binding domain that recognizes the [5’‐AACCT(N) 2‐4 AGGTT‐3′] motif and acts as a transcriptional regulator controlling multiple genes including the general stress response regulator RpoS. However, it is unknown how the transcriptional circuits of MqsA homologues have changed in bacteria over evolutionary time. Here, we found mqsA in Pseudomonas fluorescens ( PfmqsA ) is acquired through horizontal gene transfer and binds to a slightly different motif [5′‐TACCCT(N) 3 AGGGTA‐3′], which exists upstream of the PfmqsRA operon. Interestingly, an adjacent GntR‐type transcriptional regulator, which was termed AgtR, is under negative control of PfMqsA. It was further demonstrated that PfMqsA reduces production of biofilm components through AgtR, which directly regulates the pga and fap operons involved in the synthesis of extracellular polymeric substances. Moreover, through quantitative proteomics analysis, we showed AgtR is a highly pleiotropic regulator that influences up to 252 genes related to diverse processes including chemotaxis, oxidative phosphorylation and carbon and nitrogen metabolism. Taken together, our findings suggest the rewired regulatory circuit of PfMqsA influences diverse physiological aspects of P. fluorescens 2P24 via the newly characterized AgtR.

A high production of flavonoids and anthraquinones via adventitious root culture of Oplopanax elatus and evaluating antioxidant activity - L. Han; X. C. Piao; J. Jiang; X. L. Jiang; C. R. Yin; M. L. Lian (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

High frequency and diversity of parechovirus A in a cohort of Malawian children - Lieke Brouwer; Eveliina Karelehto; Alvin X. Han; Xiomara V. Thomas; Andrea H. L. Bruning; Job C. J. Calis; Michaël Boele van Hensbroek; Brenda M. Westerhuis; Darsha Amarthalingam; Sylvie M. Koekkoek; Sjoerd P. H. Rebers; Kamija S. Phiri; et al. (Archives of Virology, 2019)

Global photosynthetic capacity is optimized to the environment - Nicholas G. Smith; Trevor F. Keenan; I. Colin Prentice; Han Wang; Ian J. Wright; Ülo Niinemets; Kristine Y. Crous; Tomas F. Domingues; Rossella Guerrieri; F. Yoko Ishida; Jens Kattge; Eric L. Kruger; et al. (Ecology Letters, 2019)

Direct and indirect effects of climate on richness drive the latitudinal diversity gradient in forest trees - Chengjin Chu; James A. Lutz; Kamil Král; Tomáš Vrška; Xue Yin; Jonathan A. Myers; Iveren Abiem; Alfonso Alonso; Norm Bourg; David F.R.P. Burslem; Min Cao; Hazel Chapman; et al. (Ecology Letters, 2019)
Climate is widely recognised as an important determinant of the latitudinal diversity gradient. However, most existing studies make no distinction between direct and indirect effects of climate, which substantially hinders our understanding of how climate constrains biodiversity globally. Using data from 35 large forest plots, we test hypothesised relationships amongst climate, topography, forest structural attributes (stem abundance, tree size variation and stand basal area) and tree species richness to better understand drivers of latitudinal tree diversity patterns. Climate influences tree richness both directly, with more species in warm, moist, aseasonal climates and indirectly, with more species at higher stem abundance. These results imply direct limitation of species diversity by climatic stress and more rapid (co‐)evolution and narrower niche partitioning in warm climates. They also support the idea that increased numbers of individuals associated with high primary productivity are partitioned to support a greater number of species.

Modulatory Effects of Nicotine on neuroHIV/neuroAIDS - Haijun Han; Zhongli Yang; Sulie L. Chang; Ming D. Li (Journal of Neuroimmune Pharmacology, 2018)

Detecting hydrological consistency between soil moisture and precipitation and changes of soil moisture in summer over the Tibetan Plateau - X. Meng; R. Li; L. Luan; S. Lyu; T. Zhang; Y. Ao; B. Han; L. Zhao; Y. Ma (Climate Dynamics, 2018)

Influences of U Sources and Forms on Its Bioaccumulation in Indian Mustard and Sunflower - Fande Meng; Decheng Jin; Kai Guo; Steven L. Larson; John H. Ballard; Liangmei Chen; Zikri Arslan; Guodong Yuan; Jeremy R. White; Lixiang Zhou; Youhua Ma; Charles A. Waggoner; et al. (Water, Air, & Soil Pollution, 2018)

Optimization of culture medium components and culture period for production of adventitious roots of Echinacea pallida (Nutt.) Nutt - Y. Gao; C. H. Wu; X. C. Piao; L. Han; R. Gao; M. L. Lian (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

SegAN: Adversarial Network with Multi-scale L1 Loss for Medical Image Segmentation - Yuan Xue; Tao Xu; Han Zhang; L. Rodney Long; Xiaolei Huang (Neuroinformatics, 2018)

Litter quality, dispersal and invasion drive earthworm community dynamics and forest soil development - Katalin Szlavecz; Chih-Han Chang; Michael J. Bernard; Scott L. Pitz; Lijun Xia; Yini Ma; Melissa K. McCormick; Timothy Filley; Stephanie A. Yarwood; Ian D. Yesilonis; Csaba Csuzdi (Oecologia, 2018)

Classifying clinical notes with pain assessment using machine learning - Samah Jamal Fodeh; Dezon Finch; Lina Bouayad; Stephen L. Luther; Han Ling; Robert D. Kerns; Cynthia Brandt (Medical & Biological Engineering & Computing, 2018)

Winter hatching in New England populations of invasive pheretimoid earthworms Amynthas agrestis and Amynthas tokioensis: a limit on population growth, or aid in peripheral expansion? - Josef H. Görres; Samantha T. Connolly; Chih-Han Chang; Nell R. Carpenter; Erin L. Keller; Maryam Nouri-Aiin; Joseph J. Schall (Biological Invasions, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Inhibition of the Voltage-Dependent K+ Current by the Tricyclic Antidepressant Desipramine in Rabbit Coronary Arterial Smooth Muscle Cells - Sung Eun Shin; Hongliang Li; Jin Ryeol An; Mi Seon Seo; Sung Hun Na; Won-Kyo Jung; Amy L. Firth; Kwon-Soo Ha; Eun-Taek Han; Seok-Ho Hong; Il-Whan Choi; Won Sun Park (Cardiovascular Toxicology, 2018)

Improved soil water deficit estimation through the integration of canopy temperature measurements into a soil water balance model - Ming Han; Huihui Zhang; José L. Chávez; Liwang Ma; Thomas J. Trout; Kendall C. DeJonge (Irrigation Science, 2018)

De novo mutations in MED13, a component of the Mediator complex, are associated with a novel neurodevelopmental disorder - Lot Snijders Blok; Susan M. Hiatt; Kevin M. Bowling; Jeremy W. Prokop; Krysta L. Engel; J. Nicholas Cochran; E. Martina Bebin; Emilia K. Bijlsma; Claudia A. L. Ruivenkamp; Paulien Terhal; Marleen E. H. Simon; Rosemarie Smith; et al. (Human Genetics, 2018)

Novel Magnetic Nanocarbon and Its Adsorption of Hg and Pb from Water - Kai Guo; Steven L. Larson; John H. Ballard; Zikri Arslan; Rong Zhang; Yong Ran; Yi Su; Fengxiang X. Han (Water, Air, & Soil Pollution, 2018)

Heterotopic Purkinje Cells: a Comparative Postmortem Study of Essential Tremor and Spinocerebellar Ataxias 1, 2, 3, and 6 - Elan D. Louis; Sheng-Han Kuo; William J. Tate; Geoffrey C. Kelly; Jesus Gutierrez; Etty P. Cortes; Jean-Paul G. Vonsattel; Phyllis L. Faust (The Cerebellum, 2018)

Rhizosphere‐associated Pseudomonas induce systemic resistance to herbivores at the cost of susceptibility to bacterial pathogens - Cara H. Haney; Christina L. Wiesmann; Lori R. Shapiro; Ryan A. Melnyk; Lucy R. O'Sullivan; Sophie Khorasani; Li Xiao; Jiatong Han; Jenifer Bush; Juli Carrillo; Naomi E. Pierce; Frederick M. Ausubel (Molecular Ecology, 2018)
Plant‐associated soil microbes are important mediators of plant defence responses to diverse above‐ground pathogen and insect challengers. For example, closely related strains of beneficial rhizosphere Pseudomonas spp. can induce systemic resistance ( ISR ), systemic susceptibility ( ISS ) or neither against the bacterial foliar pathogen Pseudomonas syringae pv. tomato DC 3000 ( Pto DC 3000). Using a model system composed of root‐associated Pseudomonas spp. strains, the foliar pathogen Pto DC 3000 and the herbivore Trichoplusia ni (cabbage looper), we found that rhizosphere‐associated Pseudomonas spp. that induce either ISS and ISR against Pto DC 3000 all increased resistance to herbivory by T. ni . We found that resistance to T. ni and resistance to Pto DC 3000 are quantitative metrics of the jasmonic acid ( JA )/salicylic acid ( SA ) trade‐off and distinct strains of rhizosphere‐associated Pseudomonas spp. have distinct effects on the JA / SA trade‐off. Using genetic analysis and transcriptional profiling, we provide evidence that treatment of Arabidopsis with Pseudomonas sp. CH 267, which induces ISS against bacterial pathogens, tips the JA / SA trade‐off towards JA ‐dependent defences against herbivores at the cost of a subset of SA ‐mediated defences against bacterial pathogens. In contrast, treatment of Arabidopsis with the ISR strain Pseudomonas sp. WCS 417 disrupts JA / SA antagonism and simultaneously primes plants for both JA ‐ and SA ‐mediated defences. Our findings show that ISS against the bacterial foliar pathogens triggered by Pseudomonas sp. CH 267 , which is a seemingly deleterious phenotype, may in fact be an adaptive consequence of increased resistance to herbivory. Our work shows that pleiotropic effects of microbiome modulation of plant defences are important to consider when using microbes to modify plant traits in agriculture.

Visco-elastic–Plastic Creep Constitutive Relation of Tunnels in Soft Schist - Y. Y. Zuo; L. Han; H. Hu; S. Y. Luo; Y. Zhang; X. M. Chen (Geotechnical and Geological Engineering, 2018)

African origin and global distribution patterns: Evidence inferred from phylogenetic and biogeographical analyses of ectomycorrhizal fungal genus Strobilomyces - Li H. Han; Bang Feng; Gang Wu; Roy E. Halling; Bart Buyck; Nourou S. Yorou; Sydney T. N. Ebika; Zhu L. Yang (Journal of Biogeography, 2018)
Aim The ectomycorrhizal genus Strobilomyces is widely distributed throughout many parts of the world, but its origin, divergence and distribution patterns remain largely unresolved. In this study, we aim to explore the species diversity, distribution and evolutionary patterns of Strobilomyces on a global scale by establishing a general phylogenetic framework with extensive sampling. Location Africa, Australasia, East Asia, Europe, North America, Central America and Southeast Asia. Methods The genealogical concordance phylogenetic species recognition method was used to delimit phylogenetic species. Divergence times were estimated using a Bayesian uncorrelated lognormal relaxed molecular clock. The ancestral area and host of Strobilomyces were inferred via the programs rasp and mesquite . The change of diversification rate over time was estimated using Ape, Laser and Bammtools software packages. Results We recognize a novel African clade and 49 phylogenetic species with morphological evidence, including 18 new phylogenetic species and 23 previously described ones. Strobilomyces probably originated in Africa, in association with Detarioideae/Phyllanthaceae/Monotoideae during the early Eocene. The dispersal to Southeast Asia can be explained by Wolfe's “Boreotropical migration” hypothesis. East Asia, Australasia, Europe and North/Central America are primarily the recipients of immigrant taxa during the Oligocene or later. A rapid radiation implied by one diversification shift was inferred within Strobilomyces during the Miocene. Main conclusions An unexpected phylogenetic species diversity within Strobilomyces was uncovered. The highest diversity, resulting probably from a rapid radiation, was found in East Asia. Dispersal played an important role in the current distribution pattern of Strobilomyces . The Palaeotropical disjunction is explained by species dispersal from Africa to Southeast Asia through boreotropical forests during the early Eocene. Species from the Northern Hemisphere and Australasia are largely derived from immigrant ancestors from Southeast Asia.

Fungal Denitrification Activity in Vertical Flow Constructed Wetlands as Impacted by Plant Species Richness, Carbon, Nitrogen and pH Amendments - W. L. Liu; C. B. Zhang; W. J. Han; M. Guan; S. Y. Liu; Y. Ge; J. Chang (Bulletin of Environmental Contamination and Toxicology, 2017)

Sexually dimorphic distribution of Prokr2 neurons revealed by the Prokr2-Cre mouse model - Zaid Mohsen; Hosung Sim; David Garcia-Galiano; Xingfa Han; Nicole Bellefontaine; Thomas L. Saunders; Carol F. Elias (Brain Structure and Function, 2017)

Signatures of polygenic adaptation associated with climate across the range of a threatened fish species with high genetic connectivity - Katherine A. Harrisson; Stephen J. Amish; Alexandra Pavlova; Shawn R. Narum; Marina Telonis‐Scott; Meaghan L. Rourke; Jarod Lyon; Zeb Tonkin; Dean M. Gilligan; Brett A. Ingram; Mark Lintermans; Han Ming Gan; et al. (Molecular Ecology, 2017)
Adaptive differences across species’ ranges can have important implications for population persistence and conservation management decisions. Despite advances in genomic technologies, detecting adaptive variation in natural populations remains challenging. Key challenges in gene–environment association studies involve distinguishing the effects of drift from those of selection and identifying subtle signatures of polygenic adaptation. We used paired‐end restriction site‐associated DNA sequencing data (6,605 biallelic single nucleotide polymorphisms; SNP s) to examine population structure and test for signatures of adaptation across the geographic range of an iconic Australian endemic freshwater fish species, the Murray cod Maccullochella peelii . Two univariate gene–association methods identified 61 genomic regions associated with climate variation. We also tested for subtle signatures of polygenic adaptation using a multivariate method (redundancy analysis; RDA ). The RDA analysis suggested that climate (temperature‐ and precipitation‐related variables) and geography had similar magnitudes of effect in shaping the distribution of SNP genotypes across the sampled range of Murray cod. Although there was poor agreement among the candidate SNP s identified by the univariate methods, the top 5% of SNP s contributing to significant RDA axes included 67% of the SNP s identified by univariate methods. We discuss the potential implications of our findings for the management of Murray cod and other species generally, particularly in relation to informing conservation actions such as translocations to improve evolutionary resilience of natural populations. Our results highlight the value of using a combination of different approaches, including polygenic methods, when testing for signatures of adaptation in landscape genomic studies.

Soil Organic Carbon Dynamics Responses to Soil Fertility in the Agricultural Regions of China - D. L. Han; X. P. Zhu; H. T. Jia; P. J. Yu (Agricultural Research, 2017)

Cerebellar Pathology in Familial vs. Sporadic Essential Tremor - Elan D. Louis; Sheng-Han Kuo; Jie Wang; William J. Tate; Ming-Kai Pan; Geoffrey C. Kelly; Jesus Gutierrez; Etty P. Cortes; Jean-Paul G. Vonsattel; Phyllis L. Faust (The Cerebellum, 2017)

Study on the application of an activator for steel slag powder–cement in muddy soil - Y. K. Wu; X. S. Hu; R. Hu; T. Han; J. L. Yu (European Journal of Environmental and Civil Engineering, 2017)

Site Selection: a Case Study in the Identification of Optimal Cysteine Engineered Antibody Drug Conjugates - L. Nathan Tumey; Fengping Li; Brian Rago; Xiaogang Han; Frank Loganzo; Sylvia Musto; Edmund I. Graziani; Sujiet Puthenveetil; Jeffrey Casavant; Kimberly Marquette; Tracey Clark; Jack Bikker; et al. (The AAPS Journal, 2017)

Metabolites from the co-culture of nigranoic acid and Umbelopsis dimorpha SWUKD3.1410, an endophytic fungus from Kadsura angustifolia - L. Wang; D. Qin; K. Zhang; Q. Huang; S. Liu; M. J. Han; J. Y. Dong (Natural Product Research, 2017)

New Korean isolates of Pepper mild mottle virus (PMMoV) differ in symptom severity and subcellular localization of the 126 kDa protein - Sang-Hyuk Han; Jong-Seo Park; Jae-Yeong Han; Jun-Su Gong; Chan-Hwan Park; Jung-Kyu Kim; Eun-Young Seo; Leslie L. Domier; John Hammond; Hyoun-Sub Lim (Virus Genes, 2017)

Global Mammal Parasite Database version 2.0 - Patrick R. Stephens; Paula Pappalardo; Shan Huang; James E. Byers; Maxwell J. Farrell; Alyssa Gehman; Ria R. Ghai; Sarah E. Haas; Barbara Han; Andrew W. Park; John P. Schmidt; Sonia Altizer; et al. (Ecology, 2017)
Illuminating the ecological and evolutionary dynamics of parasites is one of the most pressing issues facing modern science, and is critical for basic science, the global economy, and human health. Extremely important to this effort are data on the disease‐causing organisms of wild animal hosts (including viruses, bacteria, protozoa, helminths, arthropods, and fungi). Here we present an updated version of the Global Mammal Parasite Database, a database of the parasites of wild ungulates (artiodactyls and perissodactyls), carnivores, and primates, and make it available for download as complete flat files. The updated database has more than 24,000 entries in the main data file alone, representing data from over 2700 literature sources. We include data on sampling method and sample sizes when reported, as well as both “reported” and “corrected” (i.e., standardized) binomials for each host and parasite species. Also included are current higher taxonomies and data on transmission modes used by the majority of species of parasites in the database. In the associated metadata we describe the methods used to identify sources and extract data from the primary literature, how entries were checked for errors, methods used to georeference entries, and how host and parasite taxonomies were standardized across the database. We also provide definitions of the data fields in each of the four files that users can download.

Cerebellar Pathology in Early Onset and Late Onset Essential Tremor - Sheng-Han Kuo; Jie Wang; William J. Tate; Ming-Kai Pan; Geoffrey C. Kelly; Jesus Gutierrez; Etty P. Cortes; Jean-Paul G. Vonsattel; Elan D. Louis; Phyllis L. Faust (The Cerebellum, 2017)

IGF-1 has sexually dimorphic, pleiotropic, and time-dependent effects on healthspan, pathology, and lifespan - Nicole M. Ashpole; Sreemathi Logan; Andriy Yabluchanskiy; Matthew C. Mitschelen; Han Yan; Julie A. Farley; Erik L. Hodges; Zoltan Ungvari; Anna Csiszar; Sixia Chen; Constantin Georgescu; Gene B. Hubbard; et al. (GeroScience, 2017)

The Next Decade of Big Data in Ecosystem Science - S. L. LaDeau; B. A. Han; E. J. Rosi-Marshall; K. C. Weathers (Ecosystems, 2017)

Sequence variants of the LCORL gene and its association with growth and carcass traits in Qinchuan cattle in China - Y. J. HAN; Y. CHEN; Y. LIU; X. L. LIU (Journal of Genetics, 2017)

Anchoring climate change communications - Adam J. L. Harris; Han-Hui Por; Stephen B. Broomell (Climatic Change, 2017)

Structuraland antigenic analysis of a new Rhoptry Pseudokinase Gene (ROP54) in Toxoplasma gondii - Jian Zhou; Gang Lu; Lin Wang; Aihua H. Zhou; Yali L. Han; Jingjing J. Guo; Pengxia X. Song; Huaiyu Y. Zhou; Hua Cong; Ming Hou; Shenyi Y. He (Acta Parasitologica, 2017)
is defined as an obligate intracellular apicomplexan parasite and influences approximatelyone-third of the human all over the world. ROP54 protein is expressed in the rhoptry of

Mapping Purkinje Cell Placement Along the Purkinje Cell Layer: an Analysis of Postmortem Tissue from Essential Tremor Patients vs. Controls - Elan D. Louis; Daniel Rabinowitz; Matthew Choe; William J. Tate; Geoffrey C. Kelly; Sheng-Han Kuo; Phyllis L. Faust (The Cerebellum, 2016)

Selective serotonin reuptake inhibitor sertraline inhibits voltage-dependent K+ channels in rabbit coronary arterial smooth muscle cells - Han Sol Kim; Hongliang Li; Hye Won Kim; Sung Eun Shin; Il-Whan Choi; Amy L Firth; Hyoweon Bang; Young Min Bae; Won Sun Park (Journal of Biosciences, 2016)

Microsatellite records for volume 8, issue 4 - Alejandra Paola Ojeda; Alexandre Wagner Silva Hilsdorf; Ana Caroline Leite; Ao-ao Yang; Ayako Izuno; Chongbo He; Chun-ya Zhou; Daisuke Kyogoku; Danilo Caneppele; Dongmei Zhu; Fernando Stopato da Fonseca; Hao Yin; et al. (Conservation Genetics Resources, 2016)

Evaluation of dynamically downscaled extreme temperature using a spatially-aggregated generalized extreme value (GEV) model - Jiali Wang; Yuefeng Han; Michael L. Stein; Veerabhadra R. Kotamarthi; Whitney K. Huang (Climate Dynamics, 2016)

Microstructure and Ultrastructure Alterations in the Pallium of Immature Mice Exposed to Cadmium - X. F. Yang; Q. G. Han; D. Y. Liu; H. T. Zhang; G. Y. Fan; J. Y. Ma; Z. L. Wang (Biological Trace Element Research, 2016)

The macroecology of infectious diseases: a new perspective on global‐scale drivers of pathogen distributions and impacts - Patrick R. Stephens; Sonia Altizer; Katherine F. Smith; A. Alonso Aguirre; James H. Brown; Sarah A. Budischak; James E. Byers; Tad A. Dallas; T. Jonathan Davies; John M. Drake; Vanessa O. Ezenwa; Maxwell J. Farrell; et al. (Ecology Letters, 2016)
Identifying drivers of infectious disease patterns and impacts at the broadest scales of organisation is one of the most crucial challenges for modern science, yet answers to many fundamental questions remain elusive. These include what factors commonly facilitate transmission of pathogens to novel host species, what drives variation in immune investment among host species, and more generally what drives global patterns of parasite diversity and distribution? Here we consider how the perspectives and tools of macroecology, a field that investigates patterns and processes at broad spatial, temporal and taxonomic scales, are expanding scientific understanding of global infectious disease ecology. In particular, emerging approaches are providing new insights about scaling properties across all living taxa, and new strategies for mapping pathogen biodiversity and infection risk. Ultimately, macroecology is establishing a framework to more accurately predict global patterns of infectious disease distribution and emergence.

Determinants of cancer screening in Asian-Americans - Quoc-Dien Trinh; Hanhan Li; Christian P. Meyer; Julian Hanske; Toni K. Choueiri; Gally Reznor; Stuart R. Lipsitz; Adam S. Kibel; Paul K. Han; Paul L. Nguyen; Mani Menon; Jesse D. Sammon (Cancer Causes & Control, 2016)

The class III anti-arrhythmic agent, amiodarone, inhibits voltage-dependent K+ channels in rabbit coronary arterial smooth muscle cells - Hongliang Li; Han Sol Kim; Hye Won Kim; Sung Eun Shin; Won-Kyo Jung; Kwon-Soo Ha; Eun-Taek Han; Seok-Ho Hong; Amy L. Firth; Young Min Bae; Il-Whan Choi; Won Sun Park (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Strong inhibition of betanodavirus replication by ribavirin targeting RNA ‐dependent RNA polymerase - Y‐C Huang; T‐S Lin; C Peng; N‐L Chan; Y‐S Han (Journal of Fish Diseases, 2016)

Biocontrol potential of antagonist Bacillus subtilis Tpb55 against tobacco black shank - T. Han; C. You; L. Zhang; C. Feng; C. Zhang; J. Wang; F. Kong (BioControl, 2016)

Colored Sticky Traps to Selectively Survey Thrips in Cowpea Ecosystem - L D Tang; H Y Zhao; B L Fu; Y Han; K Liu; J H Wu (Neotropical Entomology, 2016)

Belowground competition among invading detritivores - Chih‐Han Chang; Katalin Szlavecz; Timothy Filley; Jeffrey S. Buyer; Michael J. Bernard; Scott L. Pitz (Ecology, 2016)
The factors regulating soil animal communities are poorly understood. Current theory favors niche complementarity and facilitation over competition as the primary forms of non‐trophic interspecific interaction in soil fauna; however, competition has frequently been suggested as an important community‐structuring factor in earthworms, ecosystem engineers that influence belowground processes. To date, direct evidence of competition in earthworms is lacking due to the difficulty inherent in identifying a limiting resource for saprophagous animals. In the present study, we offer the first direct evidence of interspecific competition for food in this dominant soil detritivore group by combining field observations with laboratory mesocosm experiments using 13 C and 15 N double‐enriched leaf litter to track consumption patterns. In our experiments, the Asian invasive species Amynthas hilgendorfi was a dominant competitor for leaf litter against two European species currently invading the temperate deciduous forests in North America. This competitive advantage may account for recent invasion success of A. hilgendorfi in forests with established populations of European species, and we hypothesize that specific phenological differences play an important role in determining the outcome of the belowground competition. In contrast, Eisenoides lonnbergi , a common native species in the Eastern United States, occupied a unique trophic position with limited interactions with other species, which may contribute to its persistence in habitats dominated by invasive species. Furthermore, our results supported neither the hypothesis that facilitation occurs between species of different functional groups nor the hypothesis that species in the same group exhibit functional equivalency in C and N translocation in the soil. We propose that species identity is a more powerful approach to understand earthworm invasion and its impacts on belowground processes.

Cognition and Depression Following Deep Brain Stimulation of the Subthalamic Nucleus and Globus Pallidus Pars Internus in Parkinson’s Disease: A Meta-Analysis - Hannah L. Combs; Bradley S. Folley; David T. R. Berry; Suzanne C. Segerstrom; Dong Y. Han; Amelia J. Anderson-Mooney; Brittany D. Walls; Craig van Horne (Neuropsychology Review, 2015)

Speciation processes in putative island endemic sister bat species: false impressions from mitochondrial DNA and microsatellite data - Hao‐Chih Kuo; Shiang‐Fan Chen; Yin‐Ping Fang; James A. Cotton; Joe D. Parker; Gábor Csorba; Burton K. Lim; Judith L. Eger; Chia‐Hong Chen; Cheng‐Han Chou; Stephen J. Rossiter (Molecular Ecology, 2015)
Cases of geographically restricted co‐occurring sister taxa are rare and may point to potential divergence with gene flow. The two bat species Murina gracilis and Murina recondita are both endemic to Taiwan and are putative sister species. To test for nonallopatric divergence and gene flow in these taxa, we generated sequences using Sanger and next‐generation sequencing, and combined these with microsatellite data for coalescent‐based analyses. Mt DNA phylogenies supported the reciprocally monophyletic sister relationship between M. gracilis and M. recondita ; however, clustering of microsatellite genotypes revealed several cases of species admixture suggesting possible introgression. Sequencing of microsatellite flanking regions revealed that admixture signatures stemmed from microsatellite allele homoplasy rather than recent introgressive hybridization, and also uncovered an unexpected sister relationship between M. recondita and the continental species Murina eleryi , to the exclusion of M. gracilis . To dissect the basis of these conflicts between nc DNA and mt DNA , we analysed sequences from 10 anonymous nc DNA loci with * beast and isolation‐with‐migration and found two distinct clades of M. eleryi , one of which was sister to M. recondita . We conclude that Taiwan was colonized by the ancestor of M. gracilis first, followed by the ancestor of M. recondita after a period of allopatric divergence. After colonization, the mitochondrial genome of M. recondita was replaced by that of the resident M. gracilis . This study illustrates how apparent signatures of sympatric divergence can arise from complex histories of allopatric divergence, colonization and hybridization, thus highlighting the need for rigorous analyses to distinguish between such scenarios.

Roles of the Fibrous Superficial Zone in the Mechanical Behavior of TMJ Condylar Cartilage - Leonardo Ruggiero; Brandon K. Zimmerman; Miri Park; Lin Han; Liyun Wang; David L. Burris; X. Lucas Lu (Annals of Biomedical Engineering, 2015)

QTL mapping of adult-plant resistance to stripe rust in wheat line P9897 - X. L. Zhou; D. J. Han; X. M. Chen; J. M. Mu; W. B. Xue; Q. D. Zeng; Q. L. Wang; L. L. Huang; Z. S. Kang (Euphytica, 2015)

Genetic polymorphism of APOB is associated with diabetes mellitus in sickle cell disease - Xu Zhang; Wei Zhang; Santosh L. Saraf; Mehdi Nouraie; Jin Han; Michel Gowhari; Johara Hassan; Galina Miasnikova; Adelina Sergueeva; Sergei Nekhai; Rick Kittles; Roberto F. Machado; et al. (Human Genetics, 2015)

Identification of QTL for adult plant resistance to stripe rust in Chinese wheat landrace Caoxuan 5 - X. L. Zhou; Y. Zhang; Q. D. Zeng; X. M. Chen; D. J. Han; L. L. Huang; Z. S. Kang (Euphytica, 2015)

Erratum to: Mutations of HNRNPA0 and WIF1 predispose members of a large family to multiple cancers - Chongjuan Wei; Bo Peng; Younghun Han; Wei V. Chen; Joshua Rother; Gail E. Tomlinson; C. Richard Boland; Damien Chaussabel; Marsha L. Frazier; Christopher I. Amos (Familial Cancer, 2015)

Mutations of HNRNPA0 and WIF1 predispose members of a large family to multiple cancers - Chongjuan Wei; Bo Peng; Younghun Han; Wei V. Chen; Joshua Rother; Gail E. Tomlinson; C. Richard Boland; Marc Chaussabel; Marsha L. Frazier; Christopher I. Amos (Familial Cancer, 2015)

Profiling the Role of Deacylation-Reacylation in the Lymphatic Transport of a Triglyceride-Mimetic Prodrug - Sifei Han; Luojuan Hu; Tim Quach; Jamie S. Simpson; Natalie L. Trevaskis; Christopher J. H. Porter (Pharmaceutical Research, 2015)

Sensitivity of Alternaria solani to boscalid and control of boscalid resistance with commonly-used fungicides in Shanxi, China - X. J. Shi; L. Ren; Y. Q. Song; J. C. Han; H. P. Liu; Y. J. Zhang (Australasian Plant Pathology, 2015)

Influence of Constant Temperature on Development and Reproduction of Encarsia guadeloupae Viggiani (Hymenoptera: Aphelinidae), a Parasitoid of the Spiraling Whitefly Aleurodicus dispersus Russell (Hemiptera: Aleyrodidae) - J Y Chen; L M Niu; L Li; D Y Han; Y G Fu (Neotropical Entomology, 2015)

Gastric cancer in three relatives of a patient with a biallelic IL12RB1 mutation - Ingrid P. Vogelaar; Rachel S. van der Post; Esther van de Vosse; J. Han J. M. van Krieken; Nicoline Hoogerbrugge; Marjolijn J. L. Ligtenberg; Encarna Gómez García (Familial Cancer, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Functionality and prevalence of trehalose‐based oligosaccharides as novel compatible solutes in ascospores of N eosartorya fischeri ( A spergillus fischeri ) and other fungi - Timon T. Wyatt; M. Richard van Leeuwen; Elena A. Golovina; Folkert A. Hoekstra; Eric J. Kuenstner; Edward A. Palumbo; Nicole L. Snyder; Cobus Visagie; Alex Verkennis; John E. Hallsworth; Han A.B. Wösten; Jan Dijksterhuis (Environmental Microbiology, 2015)
Summary Ascospores of N eosartorya , B yssochlamys and T alaromyces can be regarded as the most stress‐resistant eukaryotic cells. They can survive exposure at temperatures as high as 85° C for 100 min or more. N eosartorya fischeri ascospores are more viscous and more resistant to the combined stress of heat and desiccation than the ascospores of T alaromyces macrosporus which contain predominantly trehalose. These ascospores contain trehalose‐based oligosaccharides ( TOS ) that are novel compatible solutes, which are accumulated to high levels. These compounds are also found in other members of the genus N eosartorya and in some other genera within the order Eurotiales that also include B yssochlamys and T alaromyces . The presence of oligosaccharides was observed in species that had a relatively high growth temperature. TOS glasses have a higher glass transition temperature ( T g ) than trehalose, and they form a stable glass with crystallizing molecules, such as mannitol. Our data indicate that TOS are important for prolonged stabilization of cells against stress. The possible unique role of these solutes in protection against dry heat conditions is discussed.

Evaluating the causal basis of ecological success within the scleractinia: an integral projection model approach - Peter J. Edmunds; Scott C. Burgess; Hollie M. Putnam; Marissa L. Baskett; Lorenzo Bramanti; Nick S. Fabina; Xueying Han; Michael P. Lesser; Joshua S. Madin; Christopher B. Wall; Denise M. Yost; Ruth D. Gates (Marine Biology, 2014)

Health Literacy and Pap Testing in Insured Women - K. M. Mazor; A. E. Williams; D. W. Roblin; B. Gaglio; S. L. Cutrona; M. E. Costanza; P. K. J. Han; J. L. Wagner; H. Fouayzi; T. S. Field (Journal of Cancer Education, 2014)

Differential Aortic and Mitral Valve Interstitial Cell Mineralization and the Induction of Mineralization by Lysophosphatidylcholine In Vitro - Dena C. Wiltz; Richard I. Han; Reid L. Wilson; Aditya Kumar; Joel D. Morrisett; K. Jane Grande-Allen (Cardiovascular Engineering and Technology, 2014)

Characterization and molecular mapping of stripe rust resistance gene Yr61 in winter wheat cultivar Pindong 34 - X. L. Zhou; D. J. Han; X. M. Chen; H. L. Gou; S. J. Guo; L. Rong; Q. L. Wang; L. L. Huang; Z. S. Kang (Theoretical and Applied Genetics, 2014)

Transplantation of mesenchymal stem cells into the renal medulla attenuated salt-sensitive hypertension in Dahl S rat - Junping Hu; Qing Zhu; Min Xia; Tai L. Guo; Zhengchao Wang; Pin-Lan Li; Wei-Qing Han; Fan Yi; Ningjun Li (Journal of Molecular Medicine, 2014)

Gray-matter macrostructure in cognitively healthy older persons: associations with age and cognition - Debra A. Fleischman; Sue Leurgans; Konstantinos Arfanakis; Zoe Arvanitakis; Lisa L. Barnes; Patricia A. Boyle; S. Duke Han; David A. Bennett (Brain Structure and Function, 2014)

Trajectory of overall health from self-report and factors contributing to health declines among cancer survivors - Jessica L. Petrick; Randi E. Foraker; Anna M. Kucharska-Newton; Bryce B. Reeve; Elizabeth A. Platz; Sally C. Stearns; Xuesong Han; B. Gwen Windham; Debra E. Irwin (Cancer Causes & Control, 2014)

Torpedo Formation and Purkinje Cell Loss: Modeling their Relationship in Cerebellar Disease - Elan D. Louis; Sheng-Han Kuo; Jean-Paul G. Vonsattel; Phyllis L. Faust (The Cerebellum, 2014)

Alterations in Mouse Brain Lipidome after Disruption of CST Gene: A Lipidomics Study - Chunyan Wang; Miao Wang; Yunhua Zhou; Jeffrey L. Dupree; Xianlin Han (Molecular Neurobiology, 2014)

Erratum to: Rapid Determination of Mercury in Contaminated Soil and Plant Samples Using Portable Mercury Direct Analyzer Without Sample Preparation, a Comparative Study - John G. Kelly; Fengxiang X. Han; Yi Su; Yunjun Xia; Valerie Philips; Zhiqi Shi; David L. Monts; Sergio T. Pichardo; Kang Xia (Water, Air, & Soil Pollution, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Molecular mapping of a stripe rust resistance gene in wheat cultivar Wuhan 2 - X. L. Zhou; D. J. Han; H. L. Gou; Q. L. Wang; Q. D. Zeng; F. P. Yuan; G. M. Zhan; L. L. Huang; Z. S. Kang (Euphytica, 2014)
Stripe rust (or yellow rust), caused by Puccinia striiformis f. sp. tritici , is one of the most destructive diseases of wheat worldwide. Growing resistant cultivars is the best approach to control the disease. To identify and map genes for stripe rust resistance in wheat cultivar ‘Wuhan 2', an F 2 population was developed from a cross between the cultivar and susceptible cultivar Mingxian 169. The parents, 179 F 2 plants and their derived F 2:3 lines were evaluated for responses to Chinese races CYR30 and CYR31 of the pathogen in a greenhouse. A recessive gene for resistance was identified. DNA bulked segregant analysis was applied and resistance gene analog polymorphism (RGAP) and simple sequence repeat (SSR) techniques were used to identify molecular markers linked to the resistance gene. A genetic map consisting of five RGAP and six SSR markers was constructed. The recessive gene, designated Yrwh2 , was located on the short arm of chromosome 3B and flanked by SSR markers Xwmc540 and Xgwm566 at 5.9 and 10.0 cM, respectively. The chromosomal location of the resistance gene and its close marker suggest that the locus is different from previously reported stripe rust resistance genes Yr30 , QYr.ucw - 3BS , Yrns - B1 , YrRub and QYrex.wgp - 3BL previously mapped to chromosome 3B. Yrwh2 and its closely linked markers are potentially useful for developing stripe rust resistance wheat cultivars if used in combination with other genes.

Preliminary Study on the Physiological Characteristics of Transgenic Wheat with Maize C 4 - pepc Gene in Field Conditions - L.L. Han; W.G. Xu; L. Hu; Y. Li; X.L. Qi; J.H. Zhang; H.F. Zhang; Y.X. Wang (Cereal Research Communications, 2014)

Molecular characterisation and evolution of HMW glutenin subunit genes in Brachypodium distachyon L. - Saminathan Subburaj; Guanxing Chen; Caixia Han; Dongwen Lv; Xiaohui Li; Friedrich J. Zeller; Sai L. K. Hsam; Yueming Yan (Journal of Applied Genetics, 2014)

Effects of Stocking Rate on the Variability of Peak Standing Crop in a Desert Steppe of Eurasia Grassland - Zhongwu Wang; Shuying Jiao; Guodong Han; Mengli Zhao; Haijun Ding; Xinjie Zhang; Xiaoliang Wang; Eldon L. Ayers; Walter D. Willms; Kris Havsatad; Lata A; Yongzhi Liu (Environmental Management, 2014)

Isolation and characterization of two VpYABBY genes from wild Chinese Vitis pseudoreticulata - J. Xiang; R. Q. Liu; T. M. Li; L. J. Han; Y. Zou; T. F. Xu; J. Y. Wei; Y. J. Wang; Y. Xu (Protoplasma, 2013)

Comprehensive hormone profiling of the developing seeds of four grain legumes - Susan M. H. Slater; Hai Ying Yuan; Monika M. Lulsdorf; Albert Vandenberg; L. Irina Zaharia; Xiumei Han; Suzanne R. Abrams (Plant Cell Reports, 2013)

Effects of total replacement of dietary fish oil on growth performance and fatty acid compositions of hybrid tilapia (Oreochromis niloticus × O. aureus) - C.-Y. Han; Q.-M. Zheng; L.-N. Feng (Aquaculture International, 2013)

Proton transport facilitating water-oxidation: the role of second sphere ligands surrounding the catalytic metal cluster - Han Bao; Preston L. Dilbeck; Robert L. Burnap (Photosynthesis Research, 2013)

Diabetes and prostate cancer screening in black and white men - Maureen Sanderson; Jay H. Fowke; Loren Lipworth; Xijing Han; Flora Ukoli; Ann L. Coker; William J. Blot; Margaret K. Hargreaves (Cancer Causes & Control, 2013)

More breast cancer patients prefer BRCA-mutation testing without prior face-to-face genetic counseling - Aisha S. Sie; Wendy A. G. van Zelst-Stams; Liesbeth Spruijt; Arjen R. Mensenkamp; Marjolijn J. L. Ligtenberg; Han G. Brunner; Judith B. Prins; Nicoline Hoogerbrugge (Familial Cancer, 2013)

Utilization of Hyperinsulinemia Euglycemia and Intravenous Fat Emulsion Following Poison Center Recommendations - Michael A. Darracq; Stephen L. Thornton; Han M. Do; Dennis Bok; Richard F. Clark; F. Lee Cantrell (Journal of Medical Toxicology, 2013)

Numerical Analysis of Seismic Dynamic Response of Saturated Porous Seabed Around a Buried Pipeline - X. L. Zhang; Y. Han (Marine Georesources & Geotechnology, 2013)

Erratum to: Regulation of Phytohormone Biosynthesis and Accumulation in Arabidopsis Following Treatment with Commercial Extract from the Marine Macroalga Ascophyllum nodosum - Owen S. D. Wally; Alan T. Critchley; David Hiltz; James S. Craigie; Xiumei Han; L. Irina Zaharia; Suzanne R. Abrams; Balakrishnan Prithiviraj (Journal of Plant Growth Regulation, 2013)

Regulation of Phytohormone Biosynthesis and Accumulation in Arabidopsis Following Treatment with Commercial Extract from the Marine Macroalga Ascophyllum nodosum - Owen S. D. Wally; Alan T. Critchley; David Hiltz; James S. Craigie; Xiumei Han; L. Irina Zaharia; Suzanne R. Abrams; Balakrishnan Prithiviraj (Journal of Plant Growth Regulation, 2013)

Quantification of TRPV1 Protein Levels in Rat Tissues to Understand its Physiological Roles - Ping Han; Alla V. Korepanova; Melissa H. Vos; Robert B. Moreland; Mark L. Chiu; Connie R. Faltynek (Journal of Molecular Neuroscience, 2013)

Reconstructing the origin and dispersal patterns of village chickens across E ast A frica: insights from autosomal markers - J. M. Mwacharo; K. Nomura; H. Hanada; J. L. Han; T. Amano; O. Hanotte (Molecular Ecology, 2013)
Unravelling the genetic history of any livestock species is central to understanding the origin, development and expansion of agricultural societies and economies. Domestic village chickens are widespread in Africa. Their close association with, and reliance on, humans for long‐range dispersal makes the species an important biological marker in tracking cultural and trading contacts between human societies and civilizations across time. Archaezoological and linguistic evidence suggest a complex history of arrival and dispersion of the species on the continent, with mitochondrial DNA (mt DNA ) D‐loop analysis revealing the presence of five distinct haplogroups in East African village chickens. It supports the importance of the region in understanding the history of the species and indirectly of human interactions. Here, through a detailed analysis of 30 autosomal microsatellite markers genotyped in 657 village chickens from four East African countries (Kenya, Uganda, Ethiopia and Sudan), we identify three distinct autosomal gene pools ( I , II and III ). Gene pool I is predominantly found in Ethiopia and Sudan, while II and III occur in both Kenya and Uganda. A gradient of admixture for gene pools II and III between the Kenyan coast and Uganda's hinterland ( P = 0.001) is observed, while gene pool I is clearly separated from the other two. We propose that these three gene pools represent genetic signatures of separate events in the history of the continent that relate to the arrival and dispersal of village chickens and humans across the region. Our results provide new insights on the history of chicken husbandry which has been shaped by terrestrial and maritime contacts between ancient and modern civilizations in Asia and East Africa.

Study of chloropropanols in soy sauce by gas chromatography-triple quadrupole mass spectrometry with coupled column separation without derivatisation - X.-M. Xu; H.-W. Wu; H.-L. He; B.-F. Huang; J.-L. Han; Y.-P. Ren (Food Additives & Contaminants: Part A, 2013)

Clustering of place of birth for women with breast cancer: differences by tumor characteristics - Daikwon Han; Jing Nie; Matthew R. Bonner; Christine Ambrosone; Catalin Marian; Peter Shields; Maurizio Trevisan; Stephen B. Edge; Jo L. Freudenheim (Cancer Causes & Control, 2013)

Absence of induced resistance in Agaricus bisporus against Lecanicillium fungicola - Roeland L. Berendsen; Niek Schrier; Stefanie I. C. Kalkhove; Luis G. Lugones; Johan J. P. Baars; Carolien Zijlstra; Marjanne de Weerdt; Han A. B. Wösten; Peter A. H. M. Bakker (Antonie van Leeuwenhoek, 2013)

Erratum to: The interaction of carbon dioxide and hypoxia in the control of cerebral blood flow - Alexandra Mardimae; Dahlia Y. Balaban; Matthew A. Machina; Anne Battisti-Charbonney; Jay S. Han; Rita Katznelson; Leonid L. Minkovich; Ludwik Fedorko; Patricia M. Murphy; Marcin Wasowicz; Finola Naughton; Massimiliano Meineri; et al. (Pflügers Archiv - European Journal of Physiology, 2013)

Effect of cholesterol on lipogenesis and VLDL–TG assembly and secretion in goose primary hepatocytes - C. C. Han; J. W. Wang; Z. X. Pan; H. Tang; S. X. Xiang; J. Wang; L. Li; F. Xu; S. H. Wei (Molecular and Cellular Biochemistry, 2013)

Choice of microsatellite markers for identifying homozygosity of mitotic gynogenetic diploids in Japanese flounder Paralichthys olivaceus - Y. X. Liu; H. Z. Han; Q. L. Wang; L. Jiang; S. L. Wang; X. Y. Zhang; Y. Liu; Y. F. Wang; Y. J. Liu; H. J. Liu (Journal of Fish Biology, 2013)
A set of 72 microsatellite markers distributed evenly among 24 linkage groups were selected from the published genetic linkage maps of Japanese flounder Paralichthys olivaceus . In two normal diploid full‐sib families, the test for Mendelian inheritance showed that genotypic segregation deviations were not significant at all analysed loci. To estimate microsatellite‐centromere map distances, four meiotic gynogenetic diploid lines were produced by the activation of eggs using UV irradiated sperm of red seabream Pagrus major and cold‐shock treatment to block the extrusion of the second polar body. Under the assumption of complete interference, 21 markers were located in the centromeric region, 39 in the telomeric region and the rest in the intermediate region of linkage groups. A total of 192 mitotic gynogenetic diploids from one spawn were identified by these markers. Genotype analysis showed that the number of homozygous individuals decreased as microsatellite‐centromere map distance increased on each linkage group.

Water Maze Spatial Learning Enhances Social Recognition Ability in Aged Rats - Q. Zeng; J. Han; B. Wang; Sh. An; Y. Duan; S. Dong; J. Ma; L. Yang; X. Cao (Neurophysiology, 2012)

The interaction of carbon dioxide and hypoxia in the control of cerebral blood flow - Alexandra Mardimae; Dahlia Y. Balaban; Matthew A. Machina; Jay S. Han; Rita Katznelson; Leonid L. Minkovich; Ludwik Fedorko; Patricia M. Murphy; Marcin Wasowicz; Finola Naughton; Massimiliano Meineri; Joseph A. Fisher; et al. (Pflügers Archiv - European Journal of Physiology, 2012)

Specific herbivore‐induced volatiles defend plants and determine insect community composition in the field - Y. Xiao; Q. Wang; M. Erb; T. C. J. Turlings; L. Ge; L. Hu; J. Li; X. Han; T. Zhang; J. Lu; G. Zhang; Y. Lou (Ecology Letters, 2012)
In response to insect attack, plants release complex blends of volatile compounds. These volatiles serve as foraging cues for herbivores, predators and parasitoids, leading to plant‐mediated interactions within and between trophic levels. Hence, plant volatiles may be important determinants of insect community composition. To test this, we created rice lines that are impaired in the emission of two major signals, S‐ linalool and ( E )‐β‐caryophyllene. We found that inducible S‐ linalool attracted predators and parasitoids as well as chewing herbivores, but repelled the rice brown planthopper Nilaparvata lugens , a major pest. The constitutively produced ( E )‐β‐caryophyllene on the other hand attracted both parasitoids and planthoppers, resulting in an increased herbivore load. Thus, silencing either signal resulted in specific insect assemblages in the field, highlighting the importance of plant volatiles in determining insect community structures. Moreover, the results imply that the manipulation of volatile emissions in crops has great potential for the control of pest populations.

Agronomic Considerations for Sweet Sorghum Biofuel Production in the South-Central USA - K. J. Han; W. D. Pitman; M. W. Alison; D. L. Harrell; H. P. Viator; M. E. McCormick; K. A. Gravois; M. Kim; D. F. Day (BioEnergy Research, 2012)

Inhibition of ARNT severely compromises endothelial cell viability and function in response to moderate hypoxia - Yu Han; Ke Yang; Aaron Proweller; Guangjin Zhou; Mukesh K. Jain; Diana L. Ramirez-Bergeron (Angiogenesis, 2012)

Androgenesis-inducing stress treatments change phytohormone levels in anthers of three legume species (Fabaceae) - Monika Lulsdorf; Hai Ying Yuan; Susan Slater; Albert Vandenberg; Xiumei Han; L. Irina Zaharia (Plant Cell Reports, 2012)

Adsorption of bisphenol A on lignin: effects of solution chemistry - W. Han; L. Luo; S. Zhang (International Journal of Environmental Science and Technology, 2012)

Multi-scale Structural and Tensile Mechanical Response of Annulus Fibrosus to Osmotic Loading - Woojin M. Han; Nandan L. Nerurkar; Lachlan J. Smith; Nathan T. Jacobs; Robert L. Mauck; Dawn M. Elliott (Annals of Biomedical Engineering, 2012)

Rapid Determination of Mercury in Contaminated Soil and Plant Samples Using Portable Mercury Direct Analyzer without Sample Preparation, a Comparative Study - John G. Kelly; Fengxiang X. Han; Yi Su; Yunjun Xia; Valerie Philips; Zhiqi Shi; David L. Monts; Sergio T. Pichardo; Kang Xia (Water, Air, & Soil Pollution, 2012)

Isolation, mapping, SNP detection and association with backfat traits of the porcine CTNNBL1 and DGAT2 genes - Q. Yin; H. -W. Yang; X. -L. Han; B. Fan; B. Liu (Molecular Biology Reports, 2012)

Integrating pathway analysis and genetics of gene expression for genome-wide association study of basal cell carcinoma - Mingfeng Zhang; Liming Liang; Nilesh Morar; Anna L. Dixon; G. Mark Lathrop; Jun Ding; Miriam F. Moffatt; William O. C. Cookson; Peter Kraft; Abrar A. Qureshi; Jiali Han (Human Genetics, 2012)

Case report: a p.C618S RET proto-oncogene germline mutation in a large Chinese pedigree with familial medullary thyroid carcinoma - X.-P. Qi; R.-B. Ying; J.-M. Ma; W.-T. Liu; Z.-F. Du; J. Fei; C.-P. Yang; Q.-Z. Song; H.-Y. Jin; Z.-G. Chen; J.-S. Han; J.-Q. Wang; et al. (Familial Cancer, 2012)

Post-entrainment mineral-magma interaction in mantle xenoliths from inner Mongolia, western North China craton - Yamei Wang; Baofu Han; William L. Griffin; Lei Zhang; Guiming Shu (Journal of Earth Science, 2012)

Inhibition of phosphodiesterase-4 decreases ethanol intake in mice - Wei Hu; Tina Lu; Alan Chen; Ying Huang; Rolf Hansen; L. Judson Chandler; Han-Ting Zhang (Psychopharmacology, 2011)

Parallel synthesis of novel antitumor agents: 1,2,3-triazoles bearing biologically active sulfonamide moiety and their 3D-QSAR - Lili Ou; Shuang Han; Wenbo Ding; Ping Jia; Bo Yang; Jose L. Medina-Franco; Marc A. Giulianotti; Jian-Zhong Chen; Yongping Yu (Molecular Diversity, 2011)

Individual and combined effects of multiple pathogens on Pacific treefrogs - John M. Romansic; Pieter T. J. Johnson; Catherine L. Searle; James E. Johnson; Tate S. Tunstall; Barbara A. Han; Jason R. Rohr; Andrew R. Blaustein (Oecologia, 2011)

Species-level correlates of susceptibility to the pathogenic amphibian fungus Batrachochytrium dendrobatidis in the United States - Betsy A. Bancroft; Barbara A. Han; Catherine L. Searle; Lindsay M. Biga; Deanna H. Olson; Lee B. Kats; Joshua J. Lawler; Andrew R. Blaustein (Biodiversity and Conservation, 2011)

Health Risk Assessment of Organochlorine Contaminants in Fish from a Major Lake (Baiyangdian Lake) in North China - G. H. Dai; X. H. Liu; G. Liang; M. Z. Xu; X. Han; L. Shi (Bulletin of Environmental Contamination and Toxicology, 2011)

The spatial and temporal subsidence variability of the East Mesa Geothermal Field, California, USA, and its potential impact on the All American Canal System - Joo-Yup Han; R. R. Forster; D. E. Moser; A. L. J. Ford; J. Ramírez-Hernández; K. F. Tiampo (International Journal of Remote Sensing, 2011)

A new total volume model of debris flows with intermittent surges: based on the observations at Jiangjia Valley, southwest China - N. Sh. Chen; Ch. L. Yang; W. Zhou; F. Q. Wei; Z. L. Li; D. Han; G. Sh. Hu (Natural Hazards, 2011)

Soybean peroxidase propeptides are functional signal peptides and increase the yield of a foreign protein - Jaimie A. Schnell; Shuyou Han; Brian L. Miki; Douglas A. Johnson (Plant Cell Reports, 2010)

Master donor viruses A/Leningrad/134/17/57 (H2N2) and B/USSR/60/69 and derived reassortants used in live attenuated influenza vaccine (LAIV) do not display neurovirulent properties in a mouse model - J. Theo M. Voeten; Irina V. Kiseleva; Harrie L. Glansbeek; Stephanie M. C. Basten; Sandra K. M. Drieszen-van der Cruijsen; Larisa G. Rudenko; Han van den Bosch; Jacco G. M. Heldens (Archives of Virology, 2010)

Analytical solution for katabatic flow induced by an isolated cold strip - Simon L. Axelsen; Alan Shapiro; Evgeni Fedorovich; Han van Dop (Environmental Fluid Mechanics, 2010)

Age-period-cohort analysis of cancers not related to tobacco, screening, or HIV: sex and race differences - Yueh-Ying Han; Gregg E. Dinse; David M. Umbach; Devra L. Davis; Joel L. Weissfeld (Cancer Causes & Control, 2010)

Does larval duration contribute to population genetic isolation of the Japanese eel Anguilla japonica ? - Y. S. HAN; C. L. HUNG; Y. IIZUKA; H. C. CHANG; B. J. CHANG; H. C. HO; J. C. SHIAO (Fisheries Management and Ecology, 2010)

The genome of Syntrophomonas wolfei : new insights into syntrophic metabolism and biohydrogen production - Jessica R. Sieber; David R. Sims; Cliff Han; Edwin Kim; Athanasios Lykidis; Alla L. Lapidus; Erin McDonnald; Lars Rohlin; David E. Culley; Robert Gunsalus; Michael J. McInerney (Environmental Microbiology, 2010)
Summary Syntrophomonas wolfei is a specialist, evolutionarily adapted for syntrophic growth with methanogens and other hydrogen‐ and/or formate‐using microorganisms. This slow‐growing anaerobe has three putative ribosome RNA operons, each of which has 16S rRNA and 23S rRNA genes of different length and multiple 5S rRNA genes. The genome also contains 10 RNA‐directed, DNA polymerase genes. Genomic analysis shows that S. wolfei relies solely on the reduction of protons, bicarbonate or unsaturated fatty acids to re‐oxidize reduced cofactors. Syntrophomonas wolfei lacks the genes needed for aerobic or anaerobic respiration and has an exceptionally limited ability to create ion gradients. An ATP synthase and a pyrophosphatase were the only systems detected capable of creating an ion gradient. Multiple homologues for β‐oxidation genes were present even though S. wolfei uses a limited range of fatty acids from four to eight carbons in length . Syntrophomonas wolfei , other syntrophic metabolizers with completed genomic sequences, and thermophilic anaerobes known to produce high molar ratios of hydrogen from glucose have genes to produce H 2 from NADH by an electron bifurcation mechanism. Comparative genomic analysis also suggests that formate production from NADH may involve electron bifurcation. A membrane‐bound, iron–sulfur oxidoreductase found in S. wolfei and Syntrophus aciditrophicus may be uniquely involved in reverse electron transport during syntrophic fatty acid metabolism. The genome sequence of S. wolfei reveals several core reactions that may be characteristic of syntrophic fatty acid metabolism and illustrates how biological systems produce hydrogen from thermodynamically difficult reactions.

Female BRCA mutation carriers with a preference for prophylactic mastectomy are more likely to participate an educational-support group and to proceed with the preferred intervention within 2 years - Karin M. Landsbergen; Judith B. Prins; Yvonne J. L. Kamm; Han G. Brunner; Nicoline Hoogerbrugge (Familial Cancer, 2010)

Comparison of reproductive development in triploid and diploid female rainbow trout Oncorhynchus mykiss - Y. Han; M. Liu; L. Lan Zhang; B. Simpson; G. Xue Zhang (Journal of Fish Biology, 2010)
The diploid rainbow trout Oncorhynchus mykiss reached sexual maturity 3 years after hatching and its oogenesis underwent four stages, which were oogonia, primary oocyte, secondary oocyte and egg. Reproductive development and hormone changes of 4 to 35 month‐old female O. mykiss were investigated using histological and radioimmunoassay methods in order to provide a theoretical and practical basis for the use of triploid female O. mykiss . The oogonium of the triploid female could develop into the oocytes of the prophase with abortion occurring later; the oogonium was surrounded by stroma cells to form the oogonium cluster and the gonads showed a virilescent tendency when the oogonium clusters were gradually replaced by spermatogenic‐like cytocysts. After 13 months, amounts of gonadotropic hormone (GtH‐I, GtH‐II) and oestradiol (17 β ‐E 2 ) in triploid females were lower than in diploid fish at corresponding time periods, but the amounts of testosterone (T) increased consistently after 21 months and were more than in diploid fish in the corresponding time periods ( P > 0·05). The infertility of triploid females resulted from meiosis failure, which caused developmental abortion of oocytes and oogonium formed cytocysts before the prophase oocytes. The cytocyst formation was due to the lack of the normal interaction of ovum and follicular cells, the development of follicular cells producing steroids were inhibited, the arylate path from T to 17 β ‐E 2 was interrupted, concentration of 17 β ‐E 2 decreased and concentration of T increased in the blood, the content of vitellogenin (Vg) decreased in the liver with a low 17 β ‐E 2 and high T caused to ovaries to show a tendency to be virilescent.

A novel single-nucleotide polymorphism of thevisfatin gene and its associations with performance traits in the chicken - R. L. Han; X. Y. Lan; L. Z. Zhang; G. Ren; Y. J. Jing; M. J. Li; B. Zhang; M. Zhao; Y. K. Guo; X. T. Kang; H. Chen (Journal of Applied Genetics, 2010)

Rejecting strictly allopatric speciation on a continental island: prolonged postdivergence gene flow between Taiwan ( Leucodioptron taewanus , Passeriformes Timaliidae) and Chinese ( L. canorum canorum ) hwameis - JING-WEN LI; CAROL K. L. YEUNG; PI-WEN TSAI; RONG-CHIEN LIN; CHIA-FEN YEH; CHENG-TE YAO; LIANXIAN HAN; LE MANH HUNG; PING DING; QISHAN WANG; SHOU-HSIEN LI (Molecular Ecology, 2010)

Application of an Improved Flow-Stress-Damage Model to the Criticality Assessment of Water Inrush in a Mine: a Case Study - H. Q. Zhang; Y. N. He; C. A. Tang; Bashir Ahmad; L. J. Han (Rock Mechanics and Rock Engineering, 2009)

Large-eddy simulation of katabatic winds. Part 1: Comparison with observations - Simon L. Axelsen; Han van Dop (Acta Geophysica, 2009)

Large-eddy simulation of katabatic winds. Part 2: Sensitivity study and comparison with analytical models - Simon L. Axelsen; Han van Dop (Acta Geophysica, 2009)

Prothoracic Gland Semiochemicals of Green Lacewings - Jeffrey Richard Aldrich; Thanh C. Le; Qing-He Zhang; Jorge Torres; Shaun L. Winterton; Baoyu Han; Gary L. Miller; Kamlesh R. Chauhan (Journal of Chemical Ecology, 2009)

Luminescent Donor-Acceptor β-Diketones: Modulation of Emission by Solvent Polarity and Group II Metal Binding - Guoqing Zhang; Shin Han Kim; Ruffin E. Evans; Byeong Hyo Kim; J. N. Demas; Cassandra L. Fraser (Journal of Fluorescence, 2009)

End-Permian to mid-Triassic termination of the accretionary processes of the southern Altaids: implications for the geodynamic evolution, Phanerozoic continental growth, and metallogeny of Central Asia - W. J. Xiao; B. F. Windley; B. C. Huang; C. M. Han; C. Yuan; H. L. Chen; M. Sun; S. Sun; J. L. Li (International Journal of Earth Sciences, 2009)

End-Permian to mid-Triassic termination of the accretionary processes of the southern Altaids: implications for the geodynamic evolution, Phanerozoic continental growth, and metallogeny of Central Asia - W. J. Xiao; B. F. Windley; B. C. Huang; C. M. Han; C. Yuan; H. L. Chen; M. Sun; S. Sun; J. L. Li (International Journal of Earth Sciences, 2009)

Improved Sugar Conversion and Ethanol Yield for Forage Sorghum (Sorghum bicolor L. Moench) Lines with Reduced Lignin Contents - Bruce S. Dien; Gautam Sarath; Jeffrey F. Pedersen; Scott E. Sattler; Han Chen; Deanna L. Funnell-Harris; Nancy N. Nichols; Michael A. Cotta (BioEnergy Research, 2009)

Genetic relationships between preharvest sprouting and dormancy in barley - S. E. Ullrich; H. Lee; J. A. Clancy; I. A. del Blanco; V. A. Jitkov; A. Kleinhofs; F. Han; D. Prada; I. Romagosa; J. L. Molina-Cano (Euphytica, 2009)

Molecular characterization and physico-chemical analysis of a new giant embryo mutant allele (ge t) in rice (Oryza sativa L.) - Dong-Soo Park; Soo-Kwon Park; Bong-Chun Lee; Song-Yi Song; Nam-Soo Jun; Norvie L. Manigbas; Jun-Hyun Cho; Min-Hee Nam; Jong-Seong Jeon; Chang-Deok Han; Kyung-Jin Choi; Doh-Hoon Kim; et al. (Genes & Genomics, 2009)

Arsenic levels in ground water and cancer incidence in Idaho: an ecologic study - Yueh-Ying Han; Joel L. Weissfeld; Devra L. Davis; Evelyn O. Talbott (International Archives of Occupational and Environmental Health, 2009)

International patterns and trends in thyroid cancer incidence, 1973–2002 - Briseis A. Kilfoy; Tongzhang Zheng; Theodore R. Holford; Xuesong Han; Mary H. Ward; Andreas Sjodin; Yaqun Zhang; Yana Bai; Cairong Zhu; Grace L. Guo; Nathaniel Rothman; Yawei Zhang (Cancer Causes & Control, 2009)

Physicochemical and Immunological Characterization of N,N,N-Trimethyl Chitosan-Coated Whole Inactivated Influenza Virus Vaccine for Intranasal Administration - Niels Hagenaars; Enrico Mastrobattista; Rolf J. Verheul; Imke Mooren; Harrie L. Glansbeek; Jacco G. M. Heldens; Han van den Bosch; Wim Jiskoot (Pharmaceutical Research, 2009)

Characterization and Identification of Hepatic mRNA Related to Copper Metabolism and Homeostasis in Cattle - Hyungchul Han; Shawn L. Archibeque; Terry E. Engle (Biological Trace Element Research, 2009)

Development of Quantum Dot-Mediated Fluorescence Thermometry for Thermal Therapies - Bumsoo Han; Willard L. Hanson; Karim Bensalah; Altug Tuncel; Joshua M. Stern; Jeffrey A. Cadeddu (Annals of Biomedical Engineering, 2009)

Taking species abundance distributions beyond individuals - Hélène Morlon; Ethan P. White; Rampal S. Etienne; Jessica L. Green; Annette Ostling; David Alonso; Brian J. Enquist; Fangliang He; Allen Hurlbert; Anne E. Magurran; Brian A. Maurer; Brian J. McGill; et al. (Ecology Letters, 2009)
The species abundance distribution (SAD) is one of the few universal patterns in ecology. Research on this fundamental distribution has primarily focused on the study of numerical counts, irrespective of the traits of individuals. Here we show that considering a set of Generalized Species Abundance Distributions (GSADs) encompassing several abundance measures, such as numerical abundance, biomass and resource use, can provide novel insights into the structure of ecological communities and the forces that organize them. We use a taxonomically diverse combination of macroecological data sets to investigate the similarities and differences between GSADs. We then use probability theory to explore, under parsimonious assumptions, theoretical linkages among them. Our study suggests that examining different GSADs simultaneously in natural systems may help with assessing determinants of community structure. Broadening SADs to encompass multiple abundance measures opens novel perspectives in biodiversity research and warrants future empirical and theoretical developments.

Sailing through the Late Pleistocene: unusual historical demography of an East Asian endemic, the Chinese Hwamei ( Leucodioptron canorum canorum ), during the last glacial period - SHOU‐HSIEN LI; CAROL K‐L. YEUNG; JULIE FEINSTEIN; LIANXIAN HAN; MANH HUNG LE; CHI‐XAN WANG; PING DING (Molecular Ecology, 2009)
Pleistocene climate fluctuations shaped the patterns of genetic diversity observed in extant species. In contrast to Europe and North America where the effects of recent glacial cycles on genetic diversity have been well studied, the genetic legacy of the Late Pleistocene for East Asia, a region of great topographical complexity and presumably milder historical climate, remains poorly understood. We analysed 3.86 kb of the mitochondrial genome of 186 Chinese Hwamei birds, Leucodioptron canorum canorum , and found that contrary to the conventional expectation of population decline during cold periods (stadials), the demographic history of this species shows continuous population growth since the penultimate glacial period (about 170 000 years ago). Refugia were identified in the south, coastal regions, and northern inland areas, implying that topographic complexity played a substantial role in providing suitable habitats for the Chinese Hwamei during cold periods. Intermittent gene flow between these refugia during the warmer periods (interstadials) might have resulted in a large effective population of this bird through the last glacial period.

Bioaccumulation and physiological effects of mercury in Pteris vittata and Nephrolepis exaltata - Jian Chen; Safwan Shiyab; Fengxiang X. Han; David L. Monts; Charles A. Waggoner; Zhimin Yang; Yi Su (Ecotoxicology, 2009)

Extractability and Bioavailability of Mercury from a Mercury Sulfide Contaminated Soil in Oak Ridge, Tennessee, USA - Fengxiang X. Han; Safwan Shiyab; Jian Chen; Yi Su; David L. Monts; Charles A. Waggoner; Frank B. Matta (Water, Air, & Soil Pollution, 2008)

Sources and Properties of Natural Organic Matter (NOM) in Water Along the Dongjiang River (the Source of Hong Kong’s Drinking Water) and Toxicological Assay of Its Chlorination By-Products - Y. Liang; H. C. Hong; L. H. Dong; C. Y. Lan; B. P. Han; M. H. Wong (Archives of Environmental Contamination and Toxicology, 2008)

Changes in Chlorophyll Fluorescence in Maize Plants with Imposed Rapid Dehydration at Different Leaf Ages - Z. Z. Xu; G. S. Zhou; Y. L. Wang; G. X. Han; Y. J. Li (Journal of Plant Growth Regulation, 2008)

Ultrastructural and cytochemical studies on the infection process of Sclerotinia sclerotiorum in oilseed rape - L. Huang; H. Buchenauer; Q. Han; X. Zhang; Z. Kang (Journal of Plant Diseases and Protection, 2008)

Exposure to traffic emissions throughout life and risk of breast cancer: the Western New York Exposures and Breast Cancer (WEB) study - Jing Nie; Jan Beyea; Matthew R. Bonner; Daikwon Han; John E. Vena; Peter Rogerson; Dominica Vito; Paola Muti; Maurizio Trevisan; Stephen B. Edge; Jo L. Freudenheim (Cancer Causes & Control, 2007)

Utilization of seagrass habitats by juvenile groupers and snappers in Banten Bay, Banten Province, Indonesia - Siti Nuraini; Eira C. Carballo; Wim L. T. van Densen; Marcel A. M. Machiels; Han J. Lindeboom; Leopold A. J. Nagelkerke (Hydrobiologia, 2007)

Changes of chemical and nutrient composition of porcine blood during fermentation by Aspergillus oryzae - J. Z. Wang; M. Zhang; F. Z. Ren; B. Z. Han; L. Wang; S. W. Chen; A. Humera (World Journal of Microbiology and Biotechnology, 2007)

Terrestrial carbon pools in southeast and south-central United States - Fengxiang X. Han; M. John Plodinec; Yi Su; David L. Monts; Zhongpei Li (Climatic Change, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Spectral reflectance and leaf internal structure changes of barley plants due to phytoextraction of zinc and cadmium - B. B. Maruthi Sridhar; F. X. Han; S. V. Diehl; D. L. Monts; Y. Su (International Journal of Remote Sensing, 2007)

Monitoring the effects of arsenic and chromium accumulation in Chinese brake fern ( Pteris vittata ) - Maruthi B. B. Sridhar; F. X. Han; S. V. Diehl; D. L. Monts; Y. Su (International Journal of Remote Sensing, 2007)

Spatial analysis for spring bloom and nutrient limitation in Xiangxi bay of three Gorges Reservoir - L. Ye; X. Q. Han; Y. Y. Xu; Q. H. Cai (Environmental Monitoring and Assessment, 2007)

Effect of Bioaccumulation of Cs and Sr Natural Isotopes on Foliar Structure and Plant Spectral Reflectance of Indian Mustard (Brassica Juncea) - Yi Su; B. B. Maruthi Sridhar; F. X. Han; S. V. Diehl; D. L. Monts (Water, Air, & Soil Pollution, 2007)

Intratumoral cytokines/chemokines/growth factors and tumor infiltrating dendritic cells: friends or enemies? - Michael R. Shurin; Galina V. Shurin; Anna Lokshin; Zoya R. Yurkovetsky; Dmitry W. Gutkin; Gurkamal Chatta; Hua Zhong; Baohui Han; Robert L. Ferris (Cancer and Metastasis Reviews, 2006)

Pacemaker currents modulated by C-type natriuretic peptide in interstitial cells of Cajal from murine small intestine - Y. Zhang; L. Hua Piao; X. Huang; Y. Fei Han; P. Zhao; L. Gao; Y. Kim; W. X. Xu (Journal of Physiology and Biochemistry, 2006)

Soil Nitrification and Denitrification Potentials in a Wheat Field Soil as Affected by Elevated Atmospheric CO2 and Rice Straw Incorporation - Y. Shi; S. Y. Wang; L. Han; J. Yue; L. X. Yang; Y. L. Wang; J. G. Zhu (Bulletin of Environmental Contamination and Toxicology, 2006)

Detection and identification of avian, duck, and goose reoviruses by RT-PCR: goose and duck reoviruses are part of the same genogroup in the genus Orthoreovirus - Y. Zhang; M. Liu; O. Shuidong; Q. L. Hu; D. C. Guo; H. Y. Chen; Z. Han (Archives of Virology, 2006)

Genetic diversity of avian infectious bronchitis coronavirus strains isolated in China between 1995 and 2004 - S. W. Liu; Q. X. Zhang; J. D. Chen; Z. X. Han; X. Liu; L. Feng; Y. H. Shao; J. G. Rong; X. G. Kong; G. Z. Tong (Archives of Virology, 2006)

Radon distribution in groundwater of Taiwan - Y. L. Han; M. C. Tom Kuo; K. C. Fan; C. J. Chiang; Y. P. Lee (Hydrogeology Journal, 2006)

Meprin β metalloprotease gene polymorphisms associated with diabetic nephropathy in the Pima Indians - Alexander R. Red Eagle; Robert L. Hanson; Weiping Jiang; Xiaoli Han; Gail L. Matters; Giuseppina Imperatore; William C. Knowler; Judith S. Bond (Human Genetics, 2005)

The Oryza Map Alignment Project: The Golden Path to Unlocking the Genetic Potential of Wild Rice Species - Rod A. Wing; Jetty S. S. Ammiraju; Meizhong Luo; HyeRan Kim; Yeisoo Yu; Dave Kudrna; Jose L. Goicoechea; Wenming Wang; Will Nelson; Kiran Rao; Darshan Brar; Dave J. Mackill; et al. (Plant Molecular Biology, 2005)

Seed coats: Structure, development, composition, and biotechnology - Jaimie A. Moïse; Shuyou Han; Loreta Gudynaitę-Savitch; Douglas A. Johnson; Brian L. A. Miki (In Vitro Cellular & Developmental Biology - Plant, 2005)

Arsenic, Cadmium, Chromium, Cobalt, and Copper in Different Types of Chinese Tea - W.-Y. Han; Y.-Z. Shi; L.-F. Ma; J.-Y. Ruan (Bulletin of Environmental Contamination and Toxicology, 2005)

Secondhand smoke exposure in early life and the risk of breast cancer among never smokers (United States) - Matthew R. Bonner; Jing Nie; Daikwon Han; John E. Vena; Peter Rogerson; Paola Muti; Maurizio Trevisan; Stephen B. Edge; Jo L. Freudenheim (Cancer Causes & Control, 2005)

Molecular analysis of congenital scoliosis: a candidate gene approach - Melissa K. Maisenbacher; Ji-Soo Han; Megan L. O’Brien; Michael R. Tracy; Bülent Erol; Alyssa A. Schaffer; John P. Dormans; Elaine H. Zackai; Kenro Kusumi (Human Genetics, 2005)

Mutational analysis of OGG1, MYH, MTH1 in FAP, HNPCC and sporadic colorectal cancer patients: R154H OGG1 polymorphism is associated with sporadic colorectal cancer patients - I.-J. Kim; J.-L. Ku; H. C. Kang; J.-H. Park; K.-A. Yoon; Y. Shin; H.-W. Park; S. G. Jang; S.-K. Lim; S. Y. Han; Y.-K. Shin; M. R. Lee; et al. (Human Genetics, 2004)

Geographic clustering of residence in early life and subsequent risk of breast cancer (United States) - Daikwon Han; Peter A. Rogerson; Jing Nie; Matthew R. Bonner; John E. Vena; Dominica Vito; Paola Muti; Maurizio Trevisan; Stephen B. Edge; Jo L. Freudenheim (Cancer Causes & Control, 2004)

Genetic mapping of EST-derived microsatellites from the diploid Gossypium arboreum in allotetraploid cotton - Z.-G. Han; W.-Z. Guo; X.-L. Song; T.-Z. Zhang (Molecular Genetics and Genomics, 2004)

Use of Pi5(t) markers in marker-assisted selection to screen for cultivars with resistance to Magnaporthe grisea - G. Yi; S.-K. Lee; Y.-K. Hong; Y.-C. Cho; M.-H. Nam; S.-C. Kim; S.-S. Han; G.-L. Wang; T.-R. Hahn; P.C. Ronald; J.-S. Jeon (Theoretical and Applied Genetics, 2004)

Experimental investigation of the mammary gland tumour phantom for multifrequency microwave radio-thermometers - J. W. Lee; S. M. Lee; K. S. Kim; W. T. Han; G. Yoon; L. A. Pasmanik; I. A. Ulyanichev; A. V. Troitsky (Medical & Biological Engineering & Computing, 2004)

Fine mapping of a malting-quality QTL complex near the chromosome 4H S telomere in barley - W. Gao; J. A. Clancy; F. Han; B. L. Jones; A. Budde; D. M. Wesenberg; A. Kleinhofs; S. E. Ullrich (Theoretical and Applied Genetics, 2004)

Distribution, transformation and bioavailability of trivalent and hexavalent chromium in contaminated soil - Fengxiang X. Han; Yi Su; B. B. Maruthi Sridhar; David L. Monts (Plant and Soil, 2004)

Identification and molecular modelling of a mutation in the motor head domain of myosin VIIA in a family with autosomal dominant hearing impairment (DFNA11) - Mirjam W. J. Luijendijk; Erwin van Wijk; Anne M. L. C. Bischoff; Elmar Krieger; Patrick L. M. Huygen; Ronald J. E. Pennings; Han G. Brunner; Cor W. R. J. Cremers; Frans P. M. Cremers; Hannie Kremer (Human Genetics, 2004)

Activation of a rice endogenous retrotransposon Tos17 in tissue culture is accompanied by cytosine demethylation and causes heritable alteration in methylation pattern of flanking genomic regions - Z. L. Liu; F. P. Han; M. Tan; X. H. Shan; Y. Z. Dong; X. Z. Wang; G. Fedak; S. Hao; Bao Liu (Theoretical and Applied Genetics, 2004)

Mid-Century Ensemble Regional Climate Change Scenarios for the Western United States - L. Ruby Leung; Yun Qian; Xindi Bian; Warren M. Washington; Jongil Han; John O. Roads (Climatic Change, 2004)

A Fluorescent hPept1 Transporter Substrate for Uptake Screening - Christopher P. Landowski; Hyo-kyung Han; Kyung-Dall Lee; Gordon L. Amidon (Pharmaceutical Research, 2003)

Determination of Semivolatile Compounds in Drinking Water by Tandem Mass Spectrometric Detection - L. Wang; Z. Huang; W. Zhou; C. Zhou; S. Han; A. Zhang; F. Feng; C. Liu (Bulletin of Environmental Contamination and Toxicology, 2003)

Assessment of global industrial-age anthropogenic arsenic contamination - Fengxiang X. Han; Yi Su; David L. Monts; M. John Plodinec; Amos Banin; Glover E. Triplett (The Science of Nature, 2003)

Conservation and divergence of ASK1 and ASK2 gene functions during male meiosis in Arabidopsis thaliana - Dazhong Zhao; Tianfu Han; Eddy Risseeuw; William L. Crosby; Hong Ma (Plant Molecular Biology, 2003)

Novel types of mutation in the choroideremia (CHM) gene: a full-length L1 insertion and an intronic mutation activating a cryptic exon - José A. J. M. van den Hurk; Dorien J. R. van de Pol; Bernd Wissinger; Marc A. van Driel; Lies H. Hoefsloot; Ilse J. de Wijs; L. Ingeborgh van den Born; John R. Heckenlively; Han G. Brunner; Eberhart Zrenner; Hans-Hilger Ropers; Frans P. M. Cremers (Human Genetics, 2003)

Recognition and implication of tectonic loading-induced reheating in the northern Variscan front (Belgium and northern France), based on an illite Kbler index and oxygen isotope study - G. Han; J. Yans; M. Goudalier; F. Lacquement; R. M. Corfield; J. L. Mansy; F. Boulvain; A. Prat (International Journal of Earth Sciences, 2003)

New designs for cancer vaccine and artificial veto cells - Mark L. Tykocinski; Aoshuan Chen; Jui-Han Huang; Matthew C. Weber; Guoxing Zheng (Immunologic Research, 2003)

Predicting atmospheric biases for real-time ambiguity resolution in GPS/GLONASS reference station networks - L. Dai; J. Wang; C. Rizos; S. Han (Journal of Geodesy, 2003)

Industrial age anthropogenic inputs of heavy metals into the pedosphere - Fengxiang X. Han; Amos Banin; Yi Su; David L. Monts; John M. Plodinec; William L. Kingery; Glover E. Triplett (The Science of Nature, 2002)

Response-Surface Analysis for the Inhibition Toxicity of Benzene Derivatives to Yeast Saccharomyces cerevisiae - X. Wang; Y. Wang; X. Dai; L. Wang; S. Han (Bulletin of Environmental Contamination and Toxicology, 2002)

Comparative Inhibition and Quantitative Structure-Activity Relationships (QSARs) of Substituted Phenols to Germination Rate of Cucumis sativus - X. Wang; X. Yang; Y. Wang; L. Wang; S. Han (Bulletin of Environmental Contamination and Toxicology, 2002)

Birth characteristics, maternal reproductive history, hormone use during pregnancy, and risk of childhood acute lymphocytic leukemia by immunophenotype (United States) - Xiao Ou Shu; Dehui Han; Richard K. Severson; Zhi Chen; Joseph P. Neglia; Gregory H. Reaman; Jonathan D. Buckley; Leslie L. Robison (Cancer Causes & Control, 2002)

Correlation of Reversed-Phase Retention Factors for α-Branched Phenylsulfonyl Acetates with Octanol/Water Partition Coefficients and Quantum Chemical Descriptors - X. Liu; D. Wei; C. Wu; S. Han; L. Wang (Bulletin of Environmental Contamination and Toxicology, 2001)

Workshop on Bioanalytical Methods Validation for Macromolecules: Summary Report - Krys J. Miller; Ronald R. Bowsher; Abbie Celniker; Jacqueline Gibbons; Shalini Gupta; Jean W. Lee; Steve J. Swanson; Wendell C. Smith; Russell S. Weiner; Daan J. A. Crommelin; Ira Das; Binodh S. DeSilva; et al. (Pharmaceutical Research, 2001)

Field evaluation of insect-resistant transgenic Populus nigra trees - J.J. Hu; Y.C. Tian; Y.F. Han; L. Li; B.E. Zhang (Euphytica, 2001)

Sequence variants and functional analysis of human papillomavirus type 16 E5 gene in clinical specimens - C.-H. Hsieh; Y.-P. Tsao; C.-H. Wang; C.-P. Han; J.-L. Chang; J.-Y. Lee; S.-L. Chen (Archives of Virology, 2000)

Adaptive filtering of continuous GPS results - L. Ge; H.-Y. Chen; S. Han; C. Rizos (Journal of Geodesy, 2000)

Structure-phytotoxicity relationship: Comparative inhibition of selected nitrogen containing aromatics to root elongation of Cucumis sativus - X. Wang; Y. Dong; S. Han; L. Wang (Bulletin of Environmental Contamination and Toxicology, 2000)

Microsatellites from the South American Coruro, Spalacopus cyanus - James W. Schroeder; Rodney L. Honeycutt; Alejandro P. Rooney; George Han; Sabine Begall; Milton H. Gallardo (Molecular Ecology, 2000)

Quantitative Structure-Activity Relationships for the Toxicity to the Tadpole Rana japonica of Selected Phenols - X. Wang; Y. Dong; S. Xu; L. Wang; S. Han (Bulletin of Environmental Contamination and Toxicology, 2000)

An integrated genetic map of Populus deltoides based on amplified fragment length polymorphisms - R. L. Wu; Y. F. Han; J. J. Hu; J. J. Fang; L. Li; M. L. Li; Z. -B. Zeng (Theoretical and Applied Genetics, 2000)

Quantitative Structure-Activity Relationships for the Toxicity to the Tadpole Rana japonica of Selected Phenols - X. Wang; Y. Dong; S. Xu; L. Wang; S. Han (Bulletin of Environmental Contamination and Toxicology, 2000)

Palaeovegetation of China: a pollen data‐based synthesis for the mid‐Holocene and last glacial maximum - G. Yu; X. Chen; J. Ni; R. Cheddadi; J. Guiot; H. Han; S. P. Harrison; C. Huang; M. Ke; Z. Kong; S. Li; W. Li; et al. (Journal of Biogeography, 2000)
Pollen data from China for 6000 and 18,000 14 C yr bp were compiled and used to reconstruct palaeovegetation patterns, using complete taxon lists where possible and a biomization procedure that entailed the assignment of 645 pollen taxa to plant functional types. A set of 658 modern pollen samples spanning all biomes and regions provided a comprehensive test for this procedure and showed convincing agreement between reconstructed biomes and present natural vegetation types, both geographically and in terms of the elevation gradients in mountain regions of north‐eastern and south‐western China. The 6000 14 C yr bp map confirms earlier studies in showing that the forest biomes in eastern China were systematically shifted northwards and extended westwards during the mid‐Holocene. Tropical rain forest occurred on mainland China at sites characterized today by either tropical seasonal or broadleaved evergreen/warm mixed forest. Broadleaved evergreen/warm mixed forest occurred further north than today, and at higher elevation sites within the modern latitudinal range of this biome. The northern limit of temperate deciduous forest was shifted c. 800 km north relative to today. The 18,000 14 C yr bp map shows that steppe and even desert vegetation extended to the modern coast of eastern China at the last glacial maximum, replacing today’s temperate deciduous forest. Tropical forests were excluded from China and broadleaved evergreen/warm mixed forest had retreated to tropical latitudes, while taiga extended southwards to c . 43°N.

The nucleotide sequence of a Chinese isolate of wheat yellow mosaic virus and its comparison with a Japanese isolate - D. Li; L. Yan; N. Su; C. Han; Z. Hou; J. Yu; Y. Liu (Archives of Virology, 1999)

Ionizing radiation stimulates octamer factor DNA binding activity in human carcinoma cells - Rachel L. Meighan-Mantha; Anna T. Riegel; Simeng Suy; Violaine Harris; Fuh-Han Wang; Christopher Lozano; Theresa L. Whiteside; Usha Kasid (Molecular and Cellular Biochemistry, 1999)

QSAR for Polychlorinated Organic Compounds (PCOCs). I. Prediction of Partition Properties for PCOCs Using Quantum Chemical Parameters - J. Dai; C. Sun; S. Han; L. Wang (Bulletin of Environmental Contamination and Toxicology, 1999)

Molecular characterization of germline mutations in the BRCA1 and BRCA2 genes from breast cancer families in Taiwan - Steven Shoei-Lung Li; H.-M. Tseng; Tsui-Ping Yang; Chia-Han Liu; Shiuh-Jen Teng; Hung-Wen Huang; L.-M. Chen; Hsiao-Wei Kao; Jimmy H. Chen; Jau-Neng Tseng; Angela Chen; Ming-Feng Hou; et al. (Human Genetics, 1999)

Evidence for Overlapping Substrate Specificity Between Large Neutral Amino Acid (LNAA) and Dipeptide (hPEPTl) Transporters for PD 158473, an NMDA Antagonist - Narayanan Surendran; Kuang-Ming Y. Covitz; Hyo-kyung Han; Wolfgang Sadee; Doo-Man Oh; Gordon L. Amidon; Rufus M. Williamson; Christopher F. Bigge; Barbra H. Stewart (Pharmaceutical Research, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Refined mapping of the gene for autosomal dominant retinitis pigmentosa (RP17) on chromosome 17q22 - A. I. den Hollander; S. D. van der Velde-Visser; Alfred J. L. G. Pinckers; Carel B. Hoyng; Han G. Brunner; Frans P. M. Cremers (Human Genetics, 1999)

Ocular Absorption of Pz-Peptide and Its Effect on the Ocular and Systemic Pharmacokinetics of Topically Applied Drugs in the Rabbit - Youn Bok Chung; Kun Han; Akio Nishiura; Vincent H. L. Lee (Pharmaceutical Research, 1998)

Estimation of Target Hazard Quotients and Potential Health Risks for Metals by Consumption of Seafood in Taiwan - B.-C. Han; W. L. Jeng; R. Y. Chen; G. T. Fang; T. C. Hung; R. J. Tseng (Archives of Environmental Contamination and Toxicology, 1998)

Cellular Uptake Mechanism of Amino Acid Ester Prodrugs in Caco-2/hPEPT1 Cells Overexpressing a Human Peptide Transporter - Hyo-kyung Han; Doo-Man Oh; Gordon L. Amidon (Pharmaceutical Research, 1998)

5′-Amino Acid Esters of Antiviral Nucleosides, Acyclovir, and AZT Are Absorbed by the Intestinal PEPT1 Peptide Transporter - Hyo-kyung Han; Remco L. A. de Vrueh; Julie K. Rhie; Kuang-Ming Y. Covitz; Philip L. Smith; Chao-Pin Lee; Doo-Man Oh; Wolfgang Sadee; Gordon L. Amidon1 (Pharmaceutical Research, 1998)

Interleukin-13 increases prostaglandin E2 (PGE2) production by normal human polymorphonuclear neutrophils by enhancing cyclooxygenase 2 (COX-2) gene expression - C.-L. Yu; M.-H. Huang; Y.-Y. Kung; C.-Y. Tsai; Y.-Y. Tsai; S.-T. Tsai; D.-F. Huang; K.-H. Sun; S.-H. Han; H.-S. Yu (Inflammation Research, 1998)

Response of The Lacewing Chrysopa cognata to Pheromones of its Aphid Prey - K. S. Boo; I. B. Chung; K. S. Han; J. A. Pickett; L. J. Wadhams (Journal of Chemical Ecology, 1998)

Rock-Shells ( Thais clavigera ) as an Indicator of As, Cu, and Zn Contamination on the Putai Coast of the Black-Foot Disease Area in Taiwan - B. C. Han; W. L. Jeng; M. S. Jeng; L. T. Kao; P. J. Meng; Y. L. Huang (Archives of Environmental Contamination and Toxicology, 1997)

Fine structure mapping of the barley chromosome-1 centromere region containing malting-quality QTLs - F. Han; S. E. Ullrich; A. Kleinhofs; B. L. Jones; P. M. Hayes; D. M. Wesenberg (Theoretical and Applied Genetics, 1997)

Murine Hn1 on Chromosome 11 is expressed in hemopoietic and brain tissues - Wozhan Tang; Yong-Hong Lai; Xiao-Dong Han; Peter M. C. Wong; Luanne L. Peters; David H. K. Chui (Mammalian Genome, 1997)

Ionizing radiation and TNF-a stimulate gene expression of a Thr/Tyr -protein phosphatase HVH1 and inhibitory factor IkBa in human squamous carcinoma cells - Usha Kasid; Fun-Han Wang; Theresa L. Whiteside (Molecular and Cellular Biochemistry, 1997)

Human Papillomavirus is More Prevalent in First Trimester Spontaneously Aborted Products of Conception Compared to Elective Specimens - P L Hermonat; L Han; P J Wendel; J G Quirk; S Stern; C L Lowery; T M Rechtin (Virus Genes, 1997)

Numerical bifurcation analysis of distance-dependent on-center off-surround shunting neural networks - Maartje E. J. Raijmakers; Han L. J. van der Maas; Peter C. M. Molenaar (Biological Cybernetics, 1996)

Developmental patterns of aluminum and five essential mineral elements in the central nervous system of the fetal and infant guinea pig - Mari S. Golub; Bin Han; Carl L. Keen (Biological Trace Element Research, 1996)

Monitoring lead pollution near a storage battery recycling plant in Taiwan, Republic of China - C. -Y. Yeh; H. -Y. Chiou; R. -Y. Chen; K. -H. Yeh; W. -L. Jeng; B. -C. Han (Archives of Environmental Contamination and Toxicology, 1996)

Monitoring Lead Pollution Near a Storage Battery Recycling Plant in Taiwan, Republic of China - C.-Y. Yeh; H.-Y. Chiou; R.-Y. Chen; K.-H. Yeh; W.-L. Jeng, B.-C. Han (Archives of Environmental Contamination and Toxicology, 1996)

Mirex in human milk in upstate New York - B. Bush; J. Snow; S. Connor; L. Rueckert; Y. Han; P. Dymerski; D. Hilker (Archives of Environmental Contamination and Toxicology, 1983)

Regulation of amidase formation in mutants from Pseudomonas aeruginosa PAO lacking glutamine synthetase activity - Dick B. Janssen; Patricia M. Herst; Han M. L. J. Joosten; Chris van der Drift (Archives of Microbiology, 1982)

Nitrogen control in Pseudomonas aeruginosa: A role for glutamine in the regulation of the synthesis of NADP-dependent glutamate dehydrogenase, urease and histidase - Dick B. Janssen; Patricia M. Herst; Han M. L. J. Joosten; Chris van der Drift (Archives of Microbiology, 1981)